Diatom Energy Storage Device

JP7642040B2Active Publication Date: 2025-03-07AVERY INT CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023194350
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-20
Filing Date
2023-11-15
Publication Date
2025-03-07
Estimated Expiration
2039-03-14

AI Technical Summary

Benefits of technology

【0214】 以下、本開示のこれら及び他の特徴、態様及び利点を、特定の実施形態を例示するものであって本発明を限定するものではない特定の実施形態の図面を参照して説明する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642040000001
    Figure 0007642040000001
  • Figure 0007642040000002
    Figure 0007642040000002
  • Figure 0007642040000003
    Figure 0007642040000003
Patent Text Reader

Abstract

To provide a diatom energy storage device including a diatom putamen.SOLUTION: A supercapacitor 1400 includes a pair of electrodes 1440, 1450 and an electrolyte 1460, with at least one of the electrodes including a plurality of shells having a surface active material formed thereon. The surface active material includes nanostructures and includes one or more of zinc oxide, manganese oxide, and carbon nanotubes.SELECTED DRAWING: Figure 14A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application is a continuation-in-part of U.S. Provisional Application No. 13 / 944,211 entitled "Diatomaceous Energy Storage Devices" filed on July 17, 2013, which claims priority to U.S. Provisional Application No. 61 / 862,469 entitled "High Surface Area Nanoporous Energy Storage Devices" filed on August 5, 2013, which claims priority to U.S. Provisional Application No. 61 / 750,757 entitled "Diatomaceous Energy Storage Devices" filed on January 9, 2013, and U.S. Provisional Application No. 61 / 673,149 entitled "Diatomaceous Energy Storage Devices" filed on July 18, 2012, which claims priority to U.S. Provisional Application No. 14 / 161,658 entitled "Diatomaceous Energy Storage Devices" filed on January 22, 2014, which claims priority to U.S. Provisional Application No. 61 / 862,469 entitled "High Surface Area Nanoporous Energy Storage Devices" filed on August 5, 2013, which claims priority to U.S. Provisional Application No. 61 / 862,469 entitled "Diatomace ... July 17, 2013, and U.S. Provisional Application No. 61 / 673,149 entitled "Diatomaceous Energy Storage Devices" filed on July 17, 2013, which claims priority to U.S. Provisional Application No This application claims priority to a continuation-in-part of U.S. patent application Ser. No. 15 / 808,757, filed Nov. 9, 2017, entitled "Diatomaceous Energy Storage Devices," which is a continuation-in-part of U.S. patent application Ser. No. 15 / 406,407, filed Jan. 13, 2017, entitled "Diatomaceous Energy Storage Devices," which is a continuation-in-part of U.S. patent application Ser. No. 14 / 745,709, filed Jan. 13, 2017, entitled "Diatomaceous Energy Storage Devices," each of which is incorporated herein by reference in its entirety.

[0002] The present application relates to an energy storage device, and in particular to an energy storage device comprising diatom frustules. [Background technology]

[0003] Diatoms typically include unicellular eukaryotes, such as unicellular algae. Diatoms are abundant in nature and can be found in both freshwater and marine environments. Diatoms are typically encased in a frustule, which has two shells joined together via a connecting region comprising a band. Diatomaceous earth (also known as diatomite) is the source of the frustules. Diatomaceous earth, which contains fossilized frustules, can be used in a variety of applications, such as filtration agents, paint and plastic fillers, adsorbents, cat litter, and abrasives.

[0004] The frustules often contain significant amounts of silica (SiO2) along with alumina, iron oxide, titanium oxide, phosphate, lime, sodium, and / or potassium. The frustules are typically electrically insulating. The frustules can have a variety of sizes, surface features, shapes, and other characteristics. For example, the frustules can have a variety of shapes, including, but not limited to, cylindrical, spherical, discoidal, and prismatic. The frustules can have symmetrical or asymmetrical shapes. Diatoms can be classified according to the shape and / or symmetry of their frustules, for example, frustules classified based on the presence or absence of radial symmetry. The frustules can have dimensions ranging from approximately less than 1 micrometer to approximately several hundred micrometers. The frustules can also have a variety of porosities, with numerous pores or slits. The pores or slits in the frustules can vary in shape, size, and / or density. For example, the frustules can have pores with dimensions ranging from approximately 5 nm to approximately 1000 nm.

[0005] The frustule may have significant mechanical strength and shear stress resistance due to, for example, the frustule size, frustule shape, porosity, and / or material composition. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2014 / 106088 [Patent Document 2] US Patent Application Publication No. 2012 / 0161195 [Patent Document 3] US Patent Application Publication No. 2014 / 0302373 Summary of the Invention [Means for solving the problem]

[0007] Energy storage devices, such as batteries (e.g., rechargeable batteries), fuel cells, capacitors, and / or supercapacitors (e.g., electric double-layer capacitors (EDLCs), pseudocapacitors, symmetric capacitors), can be fabricated with a frustule embedded in at least one layer of the energy storage device. The frustules can be classified to have selected shapes, dimensions, porosity, materials, surface features, and / or other suitable frustule characteristics (which can be uniform, substantially uniform, or different). The frustules can include frustule surface-modified structures and / or materials. The energy storage device can include layers such as electrodes, separators, and / or current collectors. For example, a separator can be located between a first electrode and a second electrode, a first current collector can be coupled to the first electrode, and a second current collector can be coupled to the second electrode. At least one of the separator, first electrode, and second electrode can include a frustule. Including a frustule in at least a portion of the energy storage device can facilitate fabricating the energy storage device using printing techniques (e.g., screen printing, roll-to-roll printing, inkjet printing, and / or other suitable printing processes). The frustule provides structural support for the energy storage device layer and can help the energy storage device layer maintain a uniform or substantially uniform thickness during fabrication and / or use. A porous frustule allows for unimpeded or substantially unimpeded flow of electrons or ionic species. A frustule containing surface structures or materials can increase the electrical conductivity of the layer.

[0008] In some embodiments, the printed energy storage device comprises a first electrode, a second electrode, and a separator between the first electrode and the second electrode, wherein at least one of the first electrode, the second electrode, and the separator comprises a frustule.

[0009] In some embodiments, the separator comprises a frustule. In some embodiments, the first electrode comprises a frustule. In some embodiments, the separator and the first electrode comprise a frustule. In some embodiments, the second electrode comprises a frustule. In some embodiments, the separator and the second electrode comprise a frustule. In some embodiments, the first electrode and the second electrode comprise a frustule. In some embodiments, the separator, the first electrode, and the second electrode comprise a frustule.

[0010] In some embodiments, the frustule has a substantially uniform property. In some embodiments, the property comprises a shape, e.g., a cylinder, a sphere, a disk, or a prism, etc. In some embodiments, the property comprises a dimension, e.g., a diameter, a length, a longest axis, etc. In some embodiments, the property comprises porosity. In some embodiments, the property comprises mechanical strength.

[0011] In some embodiments, the frustule comprises a surface-modified structure. In some embodiments, the surface-modified structure comprises a conductive material. In some embodiments, the conductive material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface-modified structure comprises zinc oxide (ZnO). In some embodiments, the surface-modified structure comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface-modified structure comprises at least one of a nanowire, a nanoparticle, and a rosette-shaped structure. In some embodiments, the surface-modified structure is present on an outer surface of the frustule. In some embodiments, the surface-modified structure is present on an inner surface of the frustule. In some embodiments, the surface-modified structure is present on both the inner and outer surfaces of the frustule.

[0012] In some embodiments, the frustule comprises a surface modification material. In some embodiments, the surface modification material comprises a conductive material. In some embodiments, the surface modification material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface modification material comprises ZnO. In some embodiments, the surface modification material comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface modification material is present on an exterior surface of the frustule. In some embodiments, the surface modification material is present on an interior surface of the frustule. In some embodiments, the surface modification material is present on both the interior and exterior surfaces of the frustule.

[0013] In some embodiments, the first electrode comprises a conductive filler. In some embodiments, the second electrode comprises a conductive filler. In some embodiments, the first electrode and the second electrode comprise a conductive filler. In some embodiments, the conductive filler comprises graphitic carbon. In some embodiments, the conductive filler comprises graphene. In some embodiments, the conductive filler comprises carbon nanotubes.

[0014] In some embodiments, the first electrode comprises an adhesive material. In some embodiments, the second electrode comprises an adhesive material. In some embodiments, the first electrode and the second electrode comprise an adhesive material. In some embodiments, the separator comprises an adhesive material. In some embodiments, the first electrode and the separator comprise an adhesive material. In some embodiments, the second electrode and the separator comprise an adhesive material. In some embodiments, the first electrode, the second electrode, and the separator comprise an adhesive material. In some embodiments, the adhesive material comprises a polymer.

[0015] In some embodiments, the separator comprises an electrolyte. In some embodiments, the electrolyte comprises at least one of an ionic liquid, an acid, a base, and a salt. In some embodiments, the electrolyte comprises an electrolyte gel.

[0016] In some embodiments, the device comprises a first current collector in electrical communication with the first electrode, hi some embodiments, the device comprises a second current collector in electrical communication with the second electrode, hi some embodiments, the device comprises a first current collector in electrical communication with the first electrode and a second current collector in electrical communication with the second electrode.

[0017] In some embodiments, the printing energy storage device comprises a capacitor. In some embodiments, the printing energy storage device comprises a supercapacitor. In some embodiments, the printing energy storage device comprises a battery.

[0018] In some embodiments, a system comprises a plurality of the above-described printing energy storage devices stacked on top of each other. In some embodiments, an electrical device comprises the above-described printing energy storage device or the above-described system.

[0019] In some embodiments, a membrane for a printed energy storage device comprises a furring shell.

[0020] In some embodiments, the frustule has a substantially uniform property. In some embodiments, the property comprises a shape, e.g., a cylinder, a sphere, a disk, or a prism, etc. In some embodiments, the property comprises a dimension, e.g., a diameter, a length, a longest axis, etc. In some embodiments, the property comprises porosity. In some embodiments, the property comprises mechanical strength.

[0021] In some embodiments, the frustule comprises a surface-modified structure. In some embodiments, the surface-modified structure comprises a conductive material. In some embodiments, the conductive material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface-modified structure comprises zinc oxide (ZnO). In some embodiments, the surface-modified structure comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface-modified structure comprises at least one of a nanowire, a nanoparticle, and a rosette-shaped structure. In some embodiments, the surface-modified structure is present on an outer surface of the frustule. In some embodiments, the surface-modified structure is present on an inner surface of the frustule. In some embodiments, the surface-modified structure is present on both the inner and outer surfaces of the frustule.

[0022] In some embodiments, the frustule comprises a surface modification material. In some embodiments, the surface modification material comprises a conductive material. In some embodiments, the surface modification material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface modification material comprises ZnO. In some embodiments, the surface modification material comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface modification material is present on an exterior surface of the frustule. In some embodiments, the surface modification material is present on an interior surface of the frustule. In some embodiments, the surface modification material is present on both the interior and exterior surfaces of the frustule.

[0023] In some embodiments, the membrane further comprises a conductive filler. In some embodiments, the conductive filler comprises graphitic carbon. In some embodiments, the conductive filler comprises graphene.

[0024] In some embodiments, the membrane further comprises an adhesive material, hi some embodiments, the adhesive material comprises a polymer.

[0025] In some embodiments, the membrane further comprises an electrolyte. In some embodiments, the electrolyte comprises at least one of an ionic liquid, an acid, a base, and a salt. In some embodiments, the electrolyte comprises an electrolyte gel.

[0026] In some embodiments, an energy storage device comprises the film described above. In some embodiments, the printed energy storage device comprises a capacitor. In some embodiments, the printed energy storage device comprises a supercapacitor. In some embodiments, the printed energy storage device comprises a battery. In some embodiments, a system comprises a plurality of the energy storage devices described above stacked on top of each other. In some embodiments, an electrical device comprises the printed energy storage device or the system described above.

[0027] In some embodiments, a method of manufacturing a printed energy storage device comprises forming a first electrode, forming a second electrode, and forming a separator between the first electrode and the second electrode, wherein at least one of the first electrode, the second electrode, and the separator comprises a frustule.

[0028] In some embodiments, the separator comprises a frustule. In some embodiments, forming the separator comprises forming a dispersion of the frustule. In some embodiments, forming the separator comprises screen printing the separator. In some embodiments, forming the separator comprises forming a film of the frustule. In some embodiments, forming the separator comprises roll-to-roll printing a film comprising the separator.

[0029] In some embodiments, the first electrode comprises a frustule. In some embodiments, forming the first electrode comprises forming a dispersion of the frustule. In some embodiments, forming the first electrode comprises screen printing the first electrode. In some embodiments, forming the first electrode comprises forming a film of the frustule. In some embodiments, forming the first electrode comprises roll-to-roll printing a film comprising the first electrode.

[0030] In some embodiments, the second electrode comprises a frustule. In some embodiments, forming the second electrode comprises forming a dispersion of the frustule. In some embodiments, forming the second electrode comprises screen printing the second electrode. In some embodiments, forming the second electrode comprises forming a film of the frustule. In some embodiments, forming the second electrode comprises roll-to-roll printing a film comprising the second electrode.

[0031] In some embodiments, the method further comprises classifying the frustules according to properties, which in some embodiments comprise at least one of shape, size, material, and porosity.

[0032] In some embodiments, the ink comprises a solution and frustules dispersed in the solution.

[0033] In some embodiments, the frustule has a substantially uniform property. In some embodiments, the property comprises a shape, e.g., a cylinder, a sphere, a disk, or a prism, etc. In some embodiments, the property comprises a dimension, e.g., a diameter, a length, a longest axis, etc. In some embodiments, the property comprises porosity. In some embodiments, the property comprises mechanical strength.

[0034] In some embodiments, the frustule comprises a surface-modified structure. In some embodiments, the surface-modified structure comprises a conductive material. In some embodiments, the conductive material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface-modified structure comprises zinc oxide (ZnO). In some embodiments, the surface-modified structure comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface-modified structure comprises at least one of a nanowire, a nanoparticle, and a rosette-shaped structure. In some embodiments, the surface-modified structure is present on an outer surface of the frustule. In some embodiments, the surface-modified structure is present on an inner surface of the frustule. In some embodiments, the surface-modified structure is present on both the inner and outer surfaces of the frustule.

[0035] In some embodiments, the frustule comprises a surface modification material. In some embodiments, the surface modification material comprises a conductive material. In some embodiments, the surface modification material comprises at least one of silver, aluminum, tantalum, copper, lithium, magnesium, and brass. In some embodiments, the surface modification material comprises ZnO. In some embodiments, the surface modification material comprises a semiconductor. In some embodiments, the semiconductor comprises at least one of silicon, germanium, silicon germanium, and gallium arsenide. In some embodiments, the surface modification material is present on an exterior surface of the frustule. In some embodiments, the surface modification material is present on an interior surface of the frustule. In some embodiments, the surface modification material is present on both the interior and exterior surfaces of the frustule.

[0036] In some embodiments, the ink further comprises a conductive filler. In some embodiments, the conductive filler comprises graphitic carbon. In some embodiments, the conductive filler comprises graphene.

[0037] In some embodiments, the ink further comprises an adhesive material, hi some embodiments, the adhesive material comprises a polymer.

[0038] In some embodiments, the ink further comprises an electrolyte. In some embodiments, the electrolyte comprises at least one of an ionic liquid, an acid, a base, and a salt. In some embodiments, the electrolyte comprises an electrolyte gel.

[0039] In some embodiments, the device comprises at least one of the above inks. In some embodiments, the device comprises a printing energy storage device. In some embodiments, the printing energy storage device comprises a capacitor. In some embodiments, the printing energy storage device comprises a supercapacitor. In some embodiments, the printing energy storage device comprises a battery.

[0040] The method for extracting diatom frustule portions may comprise dispersing a plurality of diatom frustule portions in a dispersing solvent. At least one of organic and inorganic contaminants may be removed. The method for extracting diatom frustule portions may further comprise dispersing the plurality of diatom frustule portions in a surfactant, wherein the surfactant reduces aggregation of the plurality of diatom frustule portions. The method may comprise extracting a plurality of diatom frustule portions having at least one common characteristic using a disc stack centrifuge.

[0041] In some embodiments, the at least one common characteristic may include at least one of a size, a shape, a material, and a degree of breakage. The size may include at least one of a length and a diameter.

[0042] In some embodiments, the solid mixture may comprise a plurality of diatom frustule portions. The method of extracting diatom frustule portions may comprise reducing the particle size of the solid mixture. The particle size reduction may occur prior to dispersing the plurality of diatom frustule portions in a dispersing solvent. In some embodiments, the particle size reduction may comprise grinding the solid mixture. Grinding the solid mixture may include applying the solid mixture to at least one of a mortar and pestle, a jar mill, and a rock crusher.

[0043] In some embodiments, components of the solid mixture having a longest component dimension greater than the longest frustule portion dimension of the plurality of diatom frustule portions may be extracted. Extracting the components of the solid mixture may comprise sieving the solid mixture. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 15 micrometers to about 25 micrometers. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 10 micrometers to about 25 micrometers.

[0044] In some embodiments, the method for extracting diatom frustule portions can comprise sorting a plurality of diatom frustule portions to separate a first diatom frustule portion having a larger longest dimension from a second diatom frustule portion. For example, the first diatom frustule portion can comprise a plurality of unbroken diatom frustule portions. The second diatom frustule portion can comprise a plurality of broken diatom frustule portions.

[0045] In some embodiments, sorting the plurality of diatom frustule portions may comprise filtering the plurality of diatom frustule portions. Filtering may comprise inhibiting aggregation of the plurality of diatom frustule portions. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise agitation. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise shaking. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise bubbling.

[0046] Filtering can include sieving a plurality of diatom frustule portions. For example, the sieve can have a mesh size of about 5 micrometers to about 10 micrometers (e.g., about 7 micrometers).

[0047] In some embodiments, a method for extracting diatom frustule portions can include obtaining washed diatom frustule portions. Obtaining the washed diatom frustule portions can comprise washing a plurality of diatom frustule portions with a washing solvent after removing at least one of organic and inorganic contaminants. In some embodiments, obtaining the washed diatom frustule portions can comprise washing diatom frustule portions having at least one common characteristic with a washing solvent.

[0048] The wash solvent may be removed. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions after removing at least one of the organic and inorganic contaminants. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions having at least one common characteristic. Settling the plurality of diatom frustule portions may comprise centrifugation. In some embodiments, the centrifugation may comprise applying a centrifuge suitable for large-scale processing. In some embodiments, the centrifugation may comprise applying at least one of a disc stack centrifuge, a decanter centrifuge, and a tubular bowl centrifuge.

[0049] In some embodiments, at least one of the dispersion solvent and the wash solvent may comprise water.

[0050] In some embodiments, at least one of dispersing the plurality of diatom frustule portions in a wash solvent and dispersing the plurality of diatom frustule portions in a surfactant may comprise sonicating the plurality of diatom frustules.

[0051] The surfactant may comprise a cationic surfactant, for example, the cationic surfactant may comprise at least one of benzalkonium chloride, cetrimonium bromide, laurylmethylgluceth-10 hydroxypropyldimonium chloride, benzethonium chloride, bronidox, dimethyldioctadecylammonium chloride, and tetramethylammonium hydroxide.

[0052] The surfactant may comprise a non-ionic surfactant, for example, at least one of cetyl alcohol, stearyl alcohol, cetostearyl alcohol, oleyl alcohol, polyoxyethylene glycol alkyl ether, octaethylene glycol monododecyl ether, glucoside alkyl ether, decyl glucoside, polyoxyethylene glycol octylphenol ether, octylphenol ethoxylate (Triton X-100®), nonoxynol-9, glyceryl laurate, polysorbate, and poloxymer.

[0053] In some embodiments, the method for extracting diatom frustule portions may comprise dispersing a plurality of diatom frustules in an additive component. Dispersing the plurality of diatom frustules in the additive component may be prior to dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be after dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be at least partially simultaneous with dispersing the plurality of diatom frustules in a surfactant. The additive component may include at least one of potassium chloride, ammonium chloride, ammonium hydroxide, and sodium hydroxide.

[0054] In some embodiments, dispersing the plurality of diatom frustule portions can comprise obtaining a dispersion comprising from about 1 weight percent to about 5 weight percent of the plurality of diatom frustule portions.

[0055] In some embodiments, removing organic contaminants may comprise heating the plurality of diatom frustule portions in the presence of a bleaching agent. The bleaching agent may include at least one of hydrogen peroxide and nitric acid. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions in a container comprising an amount of oxygenated water in a range from about 10 volume percent to about 20 volume percent. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions for a duration of from about 5 minutes to about 15 minutes.

[0056] In some embodiments, removing organic contaminants may comprise annealing the plurality of diatom frustule portions. In some embodiments, removing inorganic contaminants may comprise mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid. Mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid may include mixing the plurality of diatom frustule portions in a solution comprising about 15 volume percent to about 25 volume percent hydrochloric acid. For example, mixing may be for a duration of about 20 minutes to about 40 minutes.

[0057] The method of extracting a plurality of diatom frustule portions can include using a disc stack centrifuge to extract a plurality of diatom frustule portions having at least one common characteristic.

[0058] In some embodiments, the method for extracting diatom frustule portions may comprise dispersing a plurality of diatom frustule portions in a dispersing solvent. In some embodiments, the method may comprise removing at least one of organic and inorganic contaminants. In some embodiments, the method may comprise dispersing a plurality of diatom frustule portions in a surfactant, wherein the surfactant reduces aggregation of the plurality of diatom frustule portions.

[0059] The at least one common characteristic may include at least one of a size, a shape, a material, and a degree of breakage. The size may include at least one of a length and a diameter.

[0060] In some embodiments, the solid mixture may comprise a plurality of diatom frustule portions. The method of extracting diatom frustule portions may comprise reducing the particle size of the solid mixture. Reducing the particle size of the solid mixture may occur prior to dispersing the plurality of diatom frustule portions in a dispersing solvent. In some embodiments, reducing the particle size may comprise grinding the solid mixture. Grinding the solid mixture may include applying the solid mixture to at least one of a mortar and pestle, a jar mill, and a rock crusher.

[0061] In some embodiments, components of the solid mixture having a longest component dimension greater than the longest frustule portion dimension of the plurality of diatom frustule portions may be extracted. Extracting the components of the solid mixture may comprise sieving the solid mixture. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 15 micrometers to about 25 micrometers. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 10 micrometers to about 25 micrometers.

[0062] In some embodiments, the method for extracting diatom frustule portions can comprise sorting a plurality of diatom frustule portions to separate a first diatom frustule portion having a larger longest dimension from a second diatom frustule portion. For example, the first diatom frustule portion can comprise a plurality of unbroken diatom frustule portions. The second diatom frustule portion can comprise a plurality of broken diatom frustule portions.

[0063] In some embodiments, sorting the plurality of diatom frustule portions may comprise filtering the plurality of diatom frustule portions. Filtering may comprise inhibiting aggregation of the plurality of diatom frustule portions. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise agitation. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise shaking. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise bubbling.

[0064] Filtering can include sieving a plurality of diatom frustule portions. For example, the sieve can have a mesh size of about 5 micrometers to about 10 micrometers (e.g., about 7 micrometers).

[0065] In some embodiments, a method for extracting diatom frustule portions can include obtaining washed diatom frustule portions. Obtaining the washed diatom frustule portions can comprise washing a plurality of diatom frustule portions with a washing solvent after removing at least one of organic and inorganic contaminants. In some embodiments, obtaining the washed diatom frustule portions can comprise washing diatom frustule portions having at least one common characteristic with a washing solvent.

[0066] The wash solvent may be removed. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions after removing at least one of the organic and inorganic contaminants. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions having at least one common characteristic. Settling the plurality of diatom frustule portions may comprise centrifugation. In some embodiments, the centrifugation may comprise applying a centrifuge suitable for large-scale processing. In some embodiments, the centrifugation may comprise applying at least one of a disc stack centrifuge, a decanter centrifuge, and a tubular bowl centrifuge.

[0067] In some embodiments, at least one of the dispersion solvent and the wash solvent may comprise water.

[0068] In some embodiments, at least one of dispersing the plurality of diatom frustule portions in a wash solvent and dispersing the plurality of diatom frustule portions in a surfactant may comprise sonicating the plurality of diatom frustules.

[0069] The surfactant may comprise a cationic surfactant, for example, the cationic surfactant may comprise at least one of benzalkonium chloride, cetrimonium bromide, laurylmethylgluceth-10 hydroxypropyldimonium chloride, benzethonium chloride, bronidox, dimethyldioctadecylammonium chloride, and tetramethylammonium hydroxide.

[0070] The surfactant may comprise a non-ionic surfactant, for example, at least one of cetyl alcohol, stearyl alcohol, cetostearyl alcohol, oleyl alcohol, polyoxyethylene glycol alkyl ether, octaethylene glycol monododecyl ether, glucoside alkyl ether, decyl glucoside, polyoxyethylene glycol octylphenol ether, octylphenol ethoxylate (Triton X-100®), nonoxynol-9, glyceryl laurate, polysorbate, and poloxymer.

[0071] In some embodiments, the method for extracting diatom frustule portions may comprise dispersing a plurality of diatom frustules in an additive component. Dispersing the plurality of diatom frustules in the additive component may be prior to dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be after dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be at least partially simultaneous with dispersing the plurality of diatom frustules in a surfactant. The additive component may include at least one of potassium chloride, ammonium chloride, ammonium hydroxide, and sodium hydroxide.

[0072] In some embodiments, dispersing the plurality of diatom frustule portions can comprise obtaining a dispersion comprising from about 1 weight percent to about 5 weight percent of the plurality of diatom frustule portions.

[0073] In some embodiments, removing organic contaminants may comprise heating the plurality of diatom frustule portions in the presence of a bleaching agent. The bleaching agent may include at least one of hydrogen peroxide and nitric acid. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions in a container comprising an amount of oxygenated water in a range from about 10 volume percent to about 20 volume percent. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions for a duration of from about 5 minutes to about 15 minutes.

[0074] In some embodiments, removing organic contaminants may comprise annealing the plurality of diatom frustule portions. In some embodiments, removing inorganic contaminants may comprise mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid. Mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid may include mixing the plurality of diatom frustule portions in a solution comprising about 15 volume percent to about 25 volume percent hydrochloric acid. For example, mixing may be for a duration of about 20 minutes to about 40 minutes.

[0075] The method of extracting diatom frustule portions can include dispersing the plurality of diatom frustule portions with a surfactant, where the surfactant reduces aggregation of the plurality of diatom frustule portions.

[0076] The method for extracting diatom frustule portions may include extracting a plurality of diatom frustule portions having at least one common characteristic using a disc stack centrifuge. In some embodiments, the method for extracting diatom frustule portions may comprise dispersing the plurality of diatom frustule portions in a dispersing solvent. In some embodiments, at least one of organic contaminants and inorganic contaminants may be removed.

[0077] In some embodiments, the at least one common characteristic may include at least one of a size, a shape, a material, and a degree of breakage. The size may include at least one of a length and a diameter.

[0078] In some embodiments, the solid mixture may comprise a plurality of diatom frustule portions. The method of extracting diatom frustule portions may comprise reducing the particle size of the solid mixture. Reducing the particle size of the solid mixture may occur prior to dispersing the plurality of diatom frustule portions in a dispersing solvent. In some embodiments, reducing the particle size may comprise grinding the solid mixture. Grinding the solid mixture may include applying the solid mixture to at least one of a mortar and pestle, a jar mill, and a rock crusher.

[0079] In some embodiments, components of the solid mixture having a longest component dimension greater than the longest frustule portion dimension of the plurality of diatom frustule portions may be extracted. Extracting the components of the solid mixture may comprise sieving the solid mixture. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 15 micrometers to about 25 micrometers. Sieving the solid mixture may comprise processing the solid mixture through a sieve having a mesh size of about 10 micrometers to about 25 micrometers.

[0080] In some embodiments, the method for extracting diatom frustule portions can comprise sorting a plurality of diatom frustule portions to separate a first diatom frustule portion having a larger longest dimension from a second diatom frustule portion. For example, the first diatom frustule portion can comprise a plurality of unbroken diatom frustule portions. The second diatom frustule portion can comprise a plurality of broken diatom frustule portions.

[0081] In some embodiments, sorting the plurality of diatom frustule portions may comprise filtering the plurality of diatom frustule portions. Filtering may comprise inhibiting aggregation of the plurality of diatom frustule portions. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise agitation. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise shaking. In some embodiments, inhibiting aggregation of the plurality of diatom frustule portions may comprise bubbling.

[0082] Filtering can include sieving a plurality of diatom frustule portions. For example, the sieve can have a mesh size of about 5 micrometers to about 10 micrometers (e.g., about 7 micrometers).

[0083] In some embodiments, a method for extracting diatom frustule portions can include obtaining washed diatom frustule portions. Obtaining the washed diatom frustule portions can comprise washing a plurality of diatom frustule portions with a washing solvent after removing at least one of organic and inorganic contaminants. In some embodiments, obtaining the washed diatom frustule portions can comprise washing diatom frustule portions having at least one common characteristic with a washing solvent.

[0084] The wash solvent may be removed. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions after removing at least one of the organic and inorganic contaminants. For example, removing the wash solvent may comprise settling the plurality of diatom frustule portions having at least one common characteristic. Settling the plurality of diatom frustule portions may comprise centrifugation. In some embodiments, the centrifugation may comprise applying a centrifuge suitable for large-scale processing. In some embodiments, the centrifugation may comprise applying at least one of a disc stack centrifuge, a decanter centrifuge, and a tubular bowl centrifuge.

[0085] In some embodiments, at least one of the dispersion solvent and the wash solvent may comprise water.

[0086] In some embodiments, at least one of dispersing the plurality of diatom frustule portions in a wash solvent and dispersing the plurality of diatom frustule portions in a surfactant may comprise sonicating the plurality of diatom frustules.

[0087] The surfactant may comprise a cationic surfactant, for example, the cationic surfactant may comprise at least one of benzalkonium chloride, cetrimonium bromide, laurylmethylgluceth-10 hydroxypropyldimonium chloride, benzethonium chloride, bronidox, dimethyldioctadecylammonium chloride, and tetramethylammonium hydroxide.

[0088] The surfactant may comprise a non-ionic surfactant, for example, at least one of cetyl alcohol, stearyl alcohol, cetostearyl alcohol, oleyl alcohol, polyoxyethylene glycol alkyl ether, octaethylene glycol monododecyl ether, glucoside alkyl ether, decyl glucoside, polyoxyethylene glycol octylphenol ether, octylphenol ethoxylate (Triton X-100®), nonoxynol-9, glyceryl laurate, polysorbate, and poloxymer.

[0089] In some embodiments, the method for extracting diatom frustule portions may comprise dispersing a plurality of diatom frustules in an additive component. Dispersing the plurality of diatom frustules in the additive component may be prior to dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be after dispersing the plurality of diatom frustules in a surfactant. Dispersing the plurality of diatom frustules in the additive component may be at least partially simultaneous with dispersing the plurality of diatom frustules in a surfactant. The additive component may include at least one of potassium chloride, ammonium chloride, ammonium hydroxide, and sodium hydroxide.

[0090] In some embodiments, dispersing the plurality of diatom frustule portions can comprise obtaining a dispersion comprising from about 1 weight percent to about 5 weight percent of the plurality of diatom frustule portions.

[0091] In some embodiments, removing organic contaminants may comprise heating the plurality of diatom frustule portions in the presence of a bleaching agent. The bleaching agent may include at least one of hydrogen peroxide and nitric acid. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions in a container comprising an amount of oxygenated water in a range from about 10 volume percent to about 20 volume percent. Heating the plurality of diatom frustule portions may comprise heating the plurality of diatom frustule portions for a duration of from about 5 minutes to about 15 minutes.

[0092] In some embodiments, removing organic contaminants may comprise annealing the plurality of diatom frustule portions. In some embodiments, removing inorganic contaminants may comprise mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid. Mixing the plurality of diatom frustule portions with at least one of hydrochloric acid and sulfuric acid may include mixing the plurality of diatom frustule portions in a solution comprising about 15 volume percent to about 25 volume percent hydrochloric acid. For example, mixing may be for a duration of about 20 minutes to about 40 minutes.

[0093] A method for forming silver nanostructures on a diatom frustule portion can include forming a silver seed layer on a surface of the diatom frustule portion. The method can include forming the nanostructures on the seed layer.

[0094] In some embodiments, the nanostructures may comprise at least one of a coating, a nanowire, a nanoplate, a dense nanoparticle array, a nanobelt, and a nanodisk. In some embodiments, the nanostructures may comprise silver.

[0095] Forming the silver seed layer may comprise applying a cyclic heating regime to the first silver contributing component and the diatom frustule portion. In some embodiments, applying the cyclic heating regime may comprise applying cyclic microwave power. Applying cyclic microwave power may comprise alternating microwave power between approximately 100 watts and 500 watts. For example, the alternation may comprise alternating microwave power every minute. In some embodiments, the alternation may comprise alternating microwave power over a duration of approximately 30 minutes. In some embodiments, the alternation may comprise alternating microwave power over a duration of approximately 20 minutes to approximately 40 minutes.

[0096] In some embodiments, forming the silver seed layer can comprise mixing the diatom frustule portion with a seed layer solution. The seed layer solution can include a first silver-contributing component and a seed layer reducing agent. For example, the seed layer reducing agent can be a seed layer solvent. In some embodiments, the seed layer reducing agent and the seed layer solvent can comprise polyethylene glycol.

[0097] In some embodiments, the seed layer solution may comprise a first silver contributing component, a seed layer reducing agent, and a seed layer solvent.

[0098] Forming the silver seed layer may comprise mixing the diatom frustule portions with a seed layer solution. In some embodiments, mixing may comprise sonication.

[0099] In some embodiments, the seed layer reducing agent may comprise N,N-dimethylformamide, the first silver contributing component may comprise silver nitrate, and the seed layer solvent may comprise at least one of water and polyvinylpyrrolidone.

[0100] Forming the nanostructures can comprise combining the diatom frustule portions with a nanostructure-forming reducing agent. In some embodiments, forming the nanostructures can include heating the diatom frustule portions after combining the diatom frustule portions with the nanostructure-forming reducing agent. For example, heating can comprise heating to a temperature of from about 120°C to about 160°C.

[0101] In some embodiments, forming the nanostructures can include titrating the diatom frustule portions with a titration solution comprising a nanostructure-forming solvent and a second silver-contributing component, hi some embodiments, forming the nanostructures can include mixing after titrating the diatom frustule portions with the titration solution.

[0102] In some embodiments, at least one of the seed layer reducing agent and the nanostructure-forming reducing agent may comprise at least one of hydrazine, formaldehyde, glucose, sodium tartrate, oxalic acid, formic acid, ascorbic acid, and ethylene glycol.

[0103] In some embodiments, at least one of the first silver contributing component and the second silver contributing component may comprise at least one of a silver salt and a silver oxide. For example, the silver salt may include at least one of silver nitrate, ammoniacal silver nitrate, silver chloride (AgCl), silver cyanide (AgCN), silver tetrafluoroborate, silver hexafluorophosphate, and silver ethyl sulfate.

[0104] Forming the nanostructures can be in an atmosphere that reduces oxide formation. For example, the atmosphere can comprise an argon atmosphere.

[0105] In some embodiments, at least one of the seed layer solvent and the nanostructure formation solvent is selected from the group consisting of propylene glycol, water, methanol, ethanol, 1-propanol, 2-propanol, 1-methoxy-2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-hexanol, 2-hexanol, 3-hexanol, octanol, 1-octanol, 2-octanol, 3-octanol, tetrahydrofurfuryl alcohol (THFA), cyclohexanol, cyclopentanol, terpineol, butyl lactone, methyl ethyl ether, diethyl ether, ethyl propyl ether, polyether, diketone, cyclohexanone, cyclopentanone, cycloheptanone, cyclooctanone, acetone, benzophenone, acetylacetone, acetophenone, cyclopropanone, isophorone, methyl ethyl ketone, ethyl acetone, dimethyl adipate, propylene glycol monomethyl ether acetate, glutaraldehyde, methyl ethyl ketone, methyl methyl ether acetate ...ethyl ketone, methyl methyl ether acetate, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl ethyl ketone, methyl Dimethyl succinate, dimethyl succinate, glycerin acetate, carboxylate, propylene carbonate, glycerin, diol, triol, tetraol, pentanol, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, glycol ether, glycol ether acetate, 1,4-butanediol, 1,2-butanediol, 2,3-butanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, The solvent may comprise at least one of 1,8-octanediol, 1,2-propanediol, 1,3-butanediol, 1,2-pentanediol, ethohexadiol, p-menthane-3,8-diol, 2-methyl-2,4-pentanediol, tetramethylurea, n-methylpyrrolidone, acetonitrile, tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide (NMF), dimethyl sulfoxide (DMSO), thionyl chloride, and sulfuryl chloride.

[0106] The diatom frustule portions may comprise broken diatom frustule portions. The diatom frustule portions may comprise unbroken diatom frustule portions. In some embodiments, the diatom frustule portions may be obtained via a diatom frustule portion separation process. For example, the process may comprise at least one of using a surfactant to reduce clumping of the plurality of diatom frustule portions and using a disc stack centrifuge.

[0107] A method for forming zinc oxide nanostructures on a diatom frustule portion can include forming a zinc oxide seed layer on a surface of the diatom frustule portion. The method can include forming the nanostructures on the zinc oxide seed layer.

[0108] In some embodiments, the nanostructures may comprise at least one of nanowires, nanoplates, dense nanoparticle arrays, nanobelts, and nanodisks. In some embodiments, the nanostructures may comprise zinc oxide.

[0109] Forming the zinc oxide seed layer can comprise heating the first zinc-contributing component and the diatom frustule portion, hi some embodiments, heating the first zinc-contributing component and the diatom frustule portion can comprise heating to a temperature in a range from about 175°C to about 225°C.

[0110] In some embodiments, forming nanostructures can comprise applying a heating regime to the diatom frustule portion having the zinc oxide seed layer in the presence of a nanostructure-forming solution comprising a second zinc-contributing component. The heating regime can comprise heating to a nanostructure-forming temperature. For example, the nanostructure-forming temperature can be from about 80°C to about 100°C. In some embodiments, the heating can be for a duration of from about one hour to about three hours. In some embodiments, the heating regime can comprise applying a cyclic heating procedure. For example, the cyclic heating procedure can include applying microwave heating to the diatom frustule portion having the zinc oxide seed layer for the entire cyclic heating duration, and then turning off microwave heating for a cooling duration. In some embodiments, the heating duration can be from about one minute to about five minutes. In some embodiments, the cooling duration can be from about 30 seconds to about five minutes. Applying microwave heating can include applying microwave power of from about 480 watts to about 520 watts (e.g., microwave power of from about 80 watts to about 120 watts).

[0111] In some embodiments, at least one of the first zinc contributing component and the second zinc contributing component may comprise at least one of zinc acetate, zinc acetate hydrate, zinc nitrate, zinc nitrate hexahydrate, zinc chloride, zinc sulfide, and sodium zincate.

[0112] In some embodiments, the nanostructure-forming solution can include a base, for example, the base can comprise at least one of sodium hydroxide, ammonium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, lithium hydroxide, hexamethylenetetramine, ammonia solution, sodium carbonate, and ethylenediamine.

[0113] In some embodiments, forming the nanostructures can comprise adding an additional component, which can comprise at least one of tributylamine, triethylamine, triethanolamine, diisopropylamine, ammonium phosphate, 1,6-hexadianol, triethyldiethynol, isopropylamine, cyclohexylamine, n-butylamine, ammonium chloride, hexamethylenetetramine, ethylene glycol, ethanolamine, polyvinyl alcohol, polyethylene glycol, sodium dodecyl sulfate, cetyltrimethylammonium bromide, and carbamide.

[0114] In some embodiments, at least one of the nanostructure-forming solution and the zinc oxide seed layer-forming solution may comprise a solvent, and the solvent may be propylene glycol, water, methanol, ethanol, 1-propanol, 2-propanol, 1-methoxy-2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-hexanol, 2-hexanol, 3-hexanol, octanol, 1-octanol, 2-octanol, 3-octanol, tetrahydrofuran, Furfuryl alcohol (THFA), cyclohexanol, cyclopentanol, terpineol, butyl lactone, methyl ethyl ether, diethyl ether, ethyl propyl ether, polyether, diketone, cyclohexanone, cyclopentanone, cycloheptanone, cyclooctanone, acetone, benzophenone, acetylacetone, acetophenone, cyclopropanone, isophorone, methyl ethyl ketone, ethyl acetone, dimethyl adipate, propylene glycol monomethyl ether acetate, dimethyl glutarate, dimethyl succinate, glycerin acetate, carboxylates, propylene carbonate, glycerin, diols, triols, tetraols, pentanols, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, glycol ethers, glycol ether acetate, 1,4-butanediol, 1,2-butanediol, 2,3-butanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentane The solvent may include at least one of diol, 1,8-octanediol, 1,2-propanediol, 1,3-butanediol, 1,2-pentanediol, ethohexadiol, p-menthane-3,8-diol, 2-methyl-2,4-pentanediol, tetramethylurea, n-methylpyrrolidone, acetonitrile, tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide (NMF), dimethyl sulfoxide (DMSO), thionyl chloride, and sulfuryl chloride.

[0115] The diatom frustule portions may comprise broken diatom frustule portions. The diatom frustule portions may comprise unbroken diatom frustule portions. In some embodiments, the diatom frustule portions may be obtained via a diatom frustule portion separation process. For example, the process may comprise at least one of using a surfactant to reduce clumping of the plurality of diatom frustule portions and using a disc stack centrifuge.

[0116] A method for forming carbon nanostructures on a diatom frustule portion can include forming a metal seed layer on a surface of the diatom frustule portion. The method can include forming carbon nanostructures on the seed layer.

[0117] In some embodiments, the carbon nanostructures may comprise carbon nanotubes, which may comprise at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0118] In some embodiments, forming the metal seed layer can comprise spray coating the surface of the diatom frustule portion. In some embodiments, forming the metal seed layer can comprise exposing the surface of the diatom frustule portion to at least one of a liquid comprising the metal, a gas comprising the metal, and a solid comprising the metal.

[0119] In some embodiments, forming the carbon nanostructures may comprise using chemical vapor deposition (CVD). Forming the carbon nanostructures may comprise exposing the diatom frustule portions to a nanostructure-forming reducing gas after exposing the diatom frustule portions to a nanostructure-forming carbon gas. Forming the carbon nanostructures may comprise exposing the diatom frustule portions to a nanostructure-forming reducing gas before exposing the diatom frustule portions to the nanostructure-forming carbon gas. In some embodiments, forming the carbon nanostructures may comprise exposing the diatom frustule portions to a nanostructure-forming gas mixture comprising a nanostructure-forming reducing gas and a nanostructure-forming carbon gas. The nanostructure-forming gas mixture may include a neutral gas. For example, the neutral gas may be argon.

[0120] In some embodiments, the metal is nickel, iron, cobalt, cobalt molybdenum bimetallic, copper, gold, silver, platinum, palladium, manganese, aluminum, magnesium, chromium, antimony, aluminum iron molybdenum (Al / Fe / Mo), iron pentacarbonyl (Fe(CO)), iron(III) nitrate hexahydrate (Fe(NO)·6H0), cobalt(II) chloride hexahydrate (CoCl·6H0), ammonium molybdate tetrahydrate ((NH)MoO 24 4H2O), molybdenum (VI) dichloride dioxide (MoO2Cl2), and alumina nanopowder.

[0121] In some embodiments, the nanostructure-forming reducing gas may comprise at least one of ammonia, nitrogen, and hydrogen, and the nanostructure-forming carbon gas may comprise at least one of acetylene, ethylene, ethanol, methane, carbon oxides, and benzene.

[0122] In some embodiments, forming a metal seed layer may comprise forming a silver seed layer. Forming a silver seed layer may comprise forming silver nanostructures on the surface of the diatom frustule portion.

[0123] The diatom frustule portions may comprise broken diatom frustule portions. The diatom frustule portions may comprise unbroken diatom frustule portions. In some embodiments, the diatom frustule portions may be obtained via a diatom frustule portion separation process. For example, the process may comprise at least one of using a surfactant to reduce clumping of the plurality of diatom frustule portions and using a disc stack centrifuge.

[0124] A method for making a silver ink can include mixing an ultraviolet-sensitive component with a plurality of diatom frustule portions having silver nanostructures on a surface of the plurality of diatom frustule portions, the surface comprising a plurality of perforations.

[0125] In some embodiments, a method of making a silver ink can comprise forming a silver seed layer on a surface of a plurality of diatom frustule portions. In some embodiments, the method can include forming silver nanostructures on the seed layer.

[0126] The plurality of diatom frustule portions may comprise a plurality of broken diatom frustule portions. The plurality of diatom frustule portions may comprise a plurality of diatom frustule flakes.

[0127] In some embodiments, the silver ink can be deposited as a layer having a thickness of about 5 micrometers to about 15 micrometers after curing. In some embodiments, at least one of the plurality of perforations has a diameter of about 250 nanometers to about 350 nanometers. In some embodiments, the silver nanostructures can have a thickness of about 10 nanometers to about 500 nanometers. The silver ink can comprise diatom frustules in an amount of about 50 weight percent to about 80 weight percent.

[0128] Forming the silver seed layer can include forming a silver seed layer on surfaces within the plurality of perforations to form a plurality of silver seed-plated perforations. Forming the silver seed layer can include forming a silver seed layer on substantially all surfaces of the plurality of diatom frustule portions.

[0129] In some embodiments, forming the silver nanostructures may comprise forming silver nanostructures on surfaces within the plurality of perforations to form a plurality of silver nanostructure-plated perforations. Forming the silver nanostructures may comprise forming silver nanostructures on substantially all surfaces of the plurality of diatom frustule portions.

[0130] In some embodiments, the ultraviolet light sensitive component may be sensitive to actinic radiation having a wavelength shorter than a dimension of the plurality of pores. The ultraviolet light sensitive component may be sensitive to actinic radiation having a wavelength shorter than a dimension of at least one of the plurality of silver seed plated pores and the plurality of silver nanostructure plated pores.

[0131] In some embodiments, combining the plurality of diatom frustule portions with the UV-sensitive component can include combining the plurality of diatom frustule portions with a photoinitiator synergist. For example, the photoinitiator synergist can comprise at least one of ethoxylated hexanediol acrylate, propoxylated hexanediol acrylate, ethoxylated trimethylpropane triacrylate, triallyl cyanurate, and amine acrylate.

[0132] In some embodiments, combining the plurality of diatom frustule portions with the ultraviolet light-sensitive component can include combining the plurality of diatom frustule portions with a photoinitiator. The photoinitiator can include at least one of 2-methyl-1-(4-methylthio)phenyl-2-morpholinyl-1-propanone and isopropylthioxanthone.

[0133] In some embodiments, combining the plurality of diatom frustule portions with the UV-sensitive component can include combining the plurality of diatom frustule portions with a polar vinyl monomer, for example, the polar vinyl monomer can include at least one of n-vinyl-pyrrolidone and n-vinylcaprolactam.

[0134] A method of making a silver ink may comprise combining a plurality of diatom frustule portions with a rheology modifier. In some embodiments, a method of making a silver ink may comprise combining a plurality of diatom frustule portions with a crosslinking agent. In some embodiments, the method may include combining a plurality of diatom frustule portions with a flow and level agent. In some embodiments, the method may include combining a plurality of diatom frustule portions with at least one of an adhesion promoter, a wetting agent, and a viscosity reducer.

[0135] The silver nanostructures can include at least one of a coating, a nanowire, a nanoplate, a dense nanoparticle array, a nanobelt, and a nanodisk.

[0136] In some embodiments, forming the silver seed layer may comprise applying a cyclic heating regime to the first silver contributing element and the plurality of diatom frustule portions.

[0137] Forming the silver seed layer can comprise combining the diatom frustule portions with a seed layer solution. For example, the seed layer solution can comprise a first silver-contributing component and a seed layer reducing agent.

[0138] Forming the silver nanostructures may comprise combining the diatom frustule portions with a nanostructure-forming reducing agent. In some embodiments, forming the silver nanostructures may comprise heating the diatom frustule portions after combining the diatom frustule portions with the nanostructure-forming reducing agent. In some embodiments, forming the nanostructures may comprise titrating the diatom frustule portions with a titration solution comprising a nanostructure-forming solvent and a second silver-contributing component.

[0139] In some embodiments, the plurality of diatom frustule portions can be obtained via a diatom frustule portion separation process, for example, the process can include at least one of using a surfactant to reduce clumping of the plurality of diatom frustule portions and using a disc stack centrifuge.

[0140] The conductive silver ink can include an ultraviolet light-sensitive component. The conductive ink can include a plurality of diatom frustule portions having silver nanostructures on a surface of the plurality of diatom frustule portions, the surface comprising a plurality of perforations.

[0141] The plurality of diatom frustule portions may comprise a plurality of broken diatom frustule portions. The plurality of diatom frustule portions may comprise a plurality of diatom frustule flakes.

[0142] In some embodiments, the silver ink can be deposited as a layer having a thickness (e.g., after curing) of about 5 micrometers to about 15 micrometers. In some embodiments, at least one of the plurality of perforations has a diameter of about 250 nanometers to about 350 nanometers. In some embodiments, the silver nanostructures can have a thickness of about 10 nanometers to about 500 nanometers. The silver ink can comprise an amount of diatom frustules in a range of about 50 weight percent to about 80 weight percent.

[0143] In some embodiments, at least one of the plurality of perforations may comprise a surface having silver nanostructures.

[0144] In some embodiments, at least one of the plurality of perforations comprises a surface having a silver seed layer, hi some embodiments, substantially the entire surface of the plurality of diatom frustule portions may comprise silver nanostructures.

[0145] In some embodiments, the UV-sensitive component may be sensitive to actinic radiation having a wavelength shorter than a dimension of the plurality of perforations.

[0146] In some embodiments, the conductive silver ink can be curable by ultraviolet light. In some embodiments, the plurality of perforations can have a size sufficient to allow ultraviolet light to pass through. The conductive silver ink can be depositable as a layer having a thickness (e.g., after curing) of from about 5 micrometers to about 15 micrometers.

[0147] In some embodiments, the conductive silver ink may be heat curable.

[0148] In some embodiments, the UV-sensitive component can include a photoinitiator synergist. For example, the photoinitiator synergist can comprise at least one of ethoxylated hexanediol acrylate, propoxylated hexanediol acrylate, ethoxylated trimethylpropane triacrylate, triallyl cyanurate, and amine acrylate.

[0149] The UV-sensitive component may include a photoinitiator. The photoinitiator may include at least one of 2-methyl-1-(4-methylthio)phenyl-2-morpholinyl-1-propanone and isopropylthioxanthone.

[0150] In some embodiments, the UV-sensitive component can include a polar vinyl monomer. For example, the polar vinyl monomer can include at least one of n-vinyl-pyrrolidone and n-vinylcaprolactam.

[0151] The conductive silver ink may include at least one of a rheology modifier, a crosslinker, a flow and leveling agent, an adhesion promoter, a wetting agent, a viscosity reducing agent, etc. In some embodiments, the silver nanostructures may comprise at least one of a coating, a nanowire, a nanoplate, a dense nanoparticle array, a nanobelt, and a nanodisk.

[0152] A method of producing a silver film can include curing a mixture comprising an ultraviolet-sensitive component and a plurality of diatom frustule portions having silver nanostructures on a surface of the plurality of diatom frustule portions, the surface comprising a plurality of perforations.

[0153] In some embodiments, a method for producing a silver film can comprise forming a silver seed layer on a surface of a plurality of diatom frustule portions. In some embodiments, the method can comprise forming silver nanostructures on the seed layer. In some embodiments, the method can include mixing a plurality of diatom frustule portions with an ultraviolet light-sensitive component to form a silver ink.

[0154] The plurality of diatom frustule portions may comprise a plurality of broken diatom frustule portions. The plurality of diatom frustule portions may comprise a plurality of diatom frustule flakes.

[0155] In some embodiments, the silver ink can be deposited as a layer having a thickness (e.g., after curing) of about 5 micrometers to about 15 micrometers. In some embodiments, at least one of the plurality of perforations has a diameter of about 250 nanometers to about 350 nanometers. In some embodiments, the silver nanostructures can have a thickness of about 10 nanometers to about 500 nanometers. The silver ink can comprise an amount of diatom frustules in a range of about 50 weight percent to about 80 weight percent.

[0156] Forming the silver seed layer may comprise forming a silver seed layer on surfaces within the plurality of perforations to form a plurality of silver seed-plated perforations. Forming the silver seed layer may comprise forming a silver seed layer on substantially all surfaces of the plurality of diatom frustule portions.

[0157] Forming the silver nanostructures may comprise forming silver nanostructures on surfaces within the plurality of perforations to form a plurality of silver nanostructure-plated perforations. Forming the silver nanostructures may comprise forming silver nanostructures on substantially all surfaces of the plurality of diatom frustule portions.

[0158] In some embodiments, curing the mixture may comprise exposing the mixture to ultraviolet light having a wavelength shorter than a dimension of the plurality of perforations, hi some embodiments, curing the mixture may comprise exposing the mixture to ultraviolet light having a wavelength shorter than a dimension of at least one of the plurality of silver seed plated perforations and the plurality of silver nanostructure plated perforations.

[0159] In some embodiments, curing the mixture may comprise heat curing the mixture.

[0160] The ultraviolet light sensitive component may be sensitive to actinic radiation having a wavelength shorter than a dimension of the plurality of pores, hi some embodiments, the ultraviolet light sensitive component may be sensitive to actinic radiation having a wavelength shorter than a dimension of at least one of the plurality of silver seed plated pores and the plurality of silver nanostructure plated pores.

[0161] Combining the plurality of diatom frustule portions with the UV-sensitive component can comprise combining the plurality of diatom frustule portions with a photoinitiator synergist. For example, the photoinitiator synergist can include at least one of ethoxylated hexanediol acrylate, propoxylated hexanediol acrylate, ethoxylated trimethylpropane triacrylate, triallyl cyanurate, and amine acrylate.

[0162] In some embodiments, combining the plurality of diatom frustule portions with the ultraviolet light-sensitive component can comprise combining the plurality of diatom frustule portions with a photoinitiator. The photoinitiator can include at least one of 2-methyl-1-(4-methylthio)phenyl-2-morpholinyl-1-propanone and isopropylthioxanthone.

[0163] In some embodiments, combining the plurality of diatom frustule portions with the UV-sensitive component can comprise combining the plurality of diatom frustule portions with a polar vinyl monomer, which can include at least one of n-vinyl-pyrrolidone and n-vinylcaprolactam.

[0164] A method for making a conductive silver ink can include combining a plurality of diatom frustule portions with a rheology modifier. In some embodiments, a method for making a conductive silver ink can include combining a plurality of diatom frustule portions with a crosslinker. In some embodiments, the method comprises combining a plurality of diatom frustule portions with a flow and level agent. The method can include combining a plurality of diatom frustule portions with at least one of an adhesion promoter, a wetting agent, and a viscosity reducer.

[0165] In some embodiments, the silver nanostructures may comprise at least one of a coating, a nanowire, a nanoplate, a dense nanoparticle array, a nanobelt, and a nanodisk.

[0166] In some embodiments, forming the silver seed layer may comprise applying a cyclic heating regime to the first silver contributing element and the plurality of diatom frustule portions.

[0167] Forming the silver seed layer can comprise combining the diatom frustule portions with a seed layer solution. For example, the seed layer solution can comprise a first silver-contributing component and a seed layer reducing agent.

[0168] Forming the silver nanostructures may comprise combining the diatom frustule portions with a nanostructure-forming reducing agent. In some embodiments, forming the silver nanostructures may comprise heating the diatom frustule portions after combining the diatom frustule portions with the nanostructure-forming reducing agent. In some embodiments, forming the silver nanostructures may comprise titrating the diatom frustule portions with a titration solution comprising a nanostructure-forming solvent and a second silver-contributing component.

[0169] In some embodiments, the plurality of diatom frustule portions can be obtained via a diatom frustule portion separation process, for example, the process can include at least one of using a surfactant to reduce clumping of the plurality of diatom frustule portions and using a disc stack centrifuge.

[0170] The conductive silver film can include a plurality of diatom frustule portions having silver nanostructures on a surface of each of the plurality of diatom frustule portions, the surface comprising a plurality of perforations.

[0171] In some embodiments, the plurality of diatom frustule portions may comprise a plurality of broken diatom frustule portions. The plurality of diatom frustule portions may comprise a plurality of diatom frustule flakes.

[0172] In some embodiments, at least one of the plurality of perforations has a diameter of from about 250 nanometers to about 350 nanometers, hi some embodiments, the silver nanostructure may have a thickness of from about 10 nanometers to about 500 nanometers.

[0173] In some embodiments, at least one of the plurality of perforations may comprise a surface having silver nanostructures. In some embodiments, at least one of the plurality of perforations may comprise a surface having a silver seed layer. Substantially the entire surface of the plurality of diatom frustule portions may comprise silver nanostructures.

[0174] In some embodiments, the silver nanostructures may comprise at least one of a coating, a nanowire, a nanoplate, a dense nanoparticle array, a nanobelt, and a nanodisk.

[0175] In some embodiments, the conductive silver ink may comprise a binder resin.

[0176] The printed energy storage device can include a first electrode, a second electrode, and a separator between the first electrode and the second electrode, and at least one of the first electrode and the second electrode can include a plurality of frustules having manganese-containing nanostructures.

[0177] In some embodiments, the frustules have substantially uniform properties, the substantially uniform properties including at least one of frustule shape, frustule size, frustule porosity, frustule mechanical strength, frustule material, and frustule breakage.

[0178] In some embodiments, the manganese-containing nanostructures can include oxides of manganese. The oxides of manganese can include manganese (II, III) oxides. The oxides of manganese can include manganese oxyhydroxide.

[0179] In some embodiments, at least one of the first electrode and the second electrode can include a frustule having zinc oxide nanostructures, which can include at least one of nanowires and nanoplates.

[0180] In some embodiments, the manganese-containing nanostructures cover substantially the entire surface of the frustule, hi some embodiments, the manganese-containing nanostructures cover some surfaces of the frustule and the carbon-containing nanostructures cover other surfaces of the frustule, and the manganese-containing nanostructures are interspersed with the carbon-containing nanostructures.

[0181] The membrane of the energy storage device can include a frustule having manganese-containing nanostructures.

[0182] In some embodiments, the manganese-containing nanostructures can comprise oxides of manganese. The oxides of manganese can include manganese(II,III) oxides. The oxides of manganese can include manganese oxyhydroxide. In some embodiments, the manganese-containing nanostructures cover some surfaces of the frustule, the carbon-containing nanostructures cover other surfaces of the frustule, and the manganese-containing nanostructures are interspersed with the carbon-containing nanostructures.

[0183] In some embodiments, at least some of the manganese-containing nanostructures can be nanofibers, hi some embodiments, at least some of the manganese-containing nanostructures have a tetrahedral shape.

[0184] In some embodiments, the energy storage device comprises a zinc-manganese battery.

[0185] The ink for the printed film can include a solution and a frustule having manganese-containing nanostructures dispersed in the solution.

[0186] In some embodiments, the manganese-containing nanostructures can include oxides of manganese, hi some embodiments, the manganese-containing nanostructures can include at least one of MnO2, MnO, Mn2O3, MnOOH, and Mn3O4.

[0187] In some embodiments, at least some of the manganese-containing nanostructures may comprise nanofibers, hi some embodiments, at least some of the manganese-containing nanostructures have a tetrahedral shape.

[0188] In some embodiments, manganese-containing nanostructures cover some surfaces of the frustule, carbon-containing nanostructures cover other surfaces of the frustule, and the manganese-containing nanostructures are interspersed with the carbon-containing nanostructures.

[0189] In some embodiments, the energy storage device may include a cathode having a plurality of first frustules having nanostructures comprising an oxide of manganese, and an anode having a plurality of second frustules having nanostructures comprising zinc oxide, hi some embodiments, the device may be a rechargeable battery.

[0190] In some embodiments, the oxides of manganese include MnO. In some embodiments, the oxides of manganese include at least one of Mn3O4, Mn2O3, and MnOOH.

[0191] In some embodiments, at least one frustule of the plurality of first frustules comprises a ratio of a mass of oxide of manganese to a mass of the at least one frustule of from about 1:20 to about 20:1, and in some embodiments, at least one frustule of the plurality of second frustules comprises a ratio of a mass of zinc oxide to a mass of the at least one frustule of from about 1:20 to about 20:1.

[0192] In some embodiments, the anode can include an electrolyte salt. The electrolyte salt can include a zinc salt.

[0193] In some embodiments, at least one of the cathode and the anode may include carbon nanotubes. In some embodiments, at least one of the cathode and the anode may include a conductive filler. The conductive filler may include graphite.

[0194] In some embodiments, the energy storage device can have a separator between the cathode and the anode, the separator including a plurality of third futsae. The plurality of third futsae can be substantially free of a surface modification.

[0195] In some embodiments, at least one of the cathode, anode, and separator may include an ionic liquid.

[0196] In some embodiments, the first plurality of futshells have a plurality of first pores that are substantially unobstructed by nanostructures comprising an oxide of manganese, and the second plurality of futshells have a plurality of second pores that are substantially unobstructed by nanostructures comprising zinc oxide.

[0197] In some embodiments, the frustule may comprise a plurality of nanostructures on at least one surface, the plurality of nanostructures comprising zinc oxide, wherein the ratio of the mass of the plurality of nanostructures to the mass of the frustule is from about 1:1 to about 20:1. In some embodiments, the plurality of nanostructures comprises at least one of nanowires, nanoplates, dense nanoparticles, nanobelts, and nanodisks. In some embodiments, the frustule comprises a plurality of pores that are substantially unoccupied by the plurality of nanostructures.

[0198] In some embodiments, the frustule may comprise a plurality of nanostructures on at least one surface, the plurality of nanostructures comprising an oxide of manganese, wherein the plurality of nanostructures comprises an oxide of manganese, and wherein a ratio of the mass of the plurality of nanostructures to the mass of the frustule is from about 1:1 to about 20:1. In some embodiments, the oxide of manganese comprises MnO. In some embodiments, the oxide of manganese comprises Mn3O4. In some embodiments, the oxide of manganese comprises at least one of Mn2O3 and MnOOH. In some embodiments, the plurality of nanostructures comprises at least one of nanowires, nanoplates, dense nanoparticles, nanobelts, and nanodisks. In some embodiments, the frustule comprises a plurality of pores that are substantially unoccupied by the plurality of nanostructures.

[0199] In some embodiments, an electrode of an energy storage device can include a plurality of frustules, each of the plurality of frustules including a plurality of nanostructures formed on at least one surface, and at least one of the plurality of frustules having a ratio of the mass of the plurality of nanostructures to the mass of the at least one frustule of from about 1:20 to about 20:1.

[0200] In some embodiments, the electrodes may comprise carbon nanotubes. In some embodiments, the electrodes may comprise a conductive filler. The conductive filler may comprise graphite. In some embodiments, the electrodes may comprise an ionic liquid.

[0201] In some embodiments, each of the plurality of frustules comprises a plurality of pores that are substantially unoccupied by the plurality of nanostructures.

[0202] The electrode can be an anode of an energy storage device. In some embodiments, the anode can include an electrolyte salt. In some embodiments, the electrolyte salt can include a zinc salt. In some embodiments, the plurality of nanostructures can include zinc oxide. In some embodiments, the plurality of nanostructures can include at least one of nanowires, nanoplates, dense nanoparticles, nanobelts, and nanodisks.

[0203] The electrode can be a cathode of an energy storage device. In some embodiments, the plurality of nanostructures can include an oxide of manganese. In some embodiments, the oxide of manganese can include MnO. In some embodiments, the oxide of manganese can include at least one of Mn3O4, Mn2O3, and MnOOH.

[0204] In some embodiments, an energy storage device can include a cathode having a plurality of first frustules having nanostructures comprising an oxide of manganese and an anode having a plurality of second frustules having nanostructures comprising zinc oxide. In some embodiments, the device can be a rechargeable battery. In some embodiments, at least one frustule of the plurality of first frustules comprises a ratio of the mass of the oxide of manganese to the mass of the at least one frustule of from about 1:20 to about 100:1. In some embodiments, at least one frustule of the plurality of second frustules comprises a ratio of the mass of the zinc oxide to the mass of the at least one frustule of from about 1:20 to about 100:1.

[0205] In some embodiments, the frustule can include a plurality of nanostructures on at least one surface, the plurality of nanostructures comprising zinc oxide, and a ratio of the mass of the plurality of nanostructures to the mass of the frustule is from about 1:1 to about 100:1.

[0206] In some embodiments, the frustule can include a plurality of nanostructures on at least one surface, the plurality of nanostructures comprising an oxide of manganese, and a ratio of the mass of the plurality of nanostructures to the mass of the frustule is from about 1:1 to about 100:1.

[0207] In some embodiments, an electrode of an energy storage device can include a plurality of frustules, each of the plurality of frustules including a plurality of nanostructures formed on at least one surface, and at least one frustule of the plurality of frustules having a ratio of the mass of the plurality of nanostructures to the mass of the at least one frustule of from about 1:20 to about 100:1.

[0208] In some embodiments, a supercapacitor comprises a pair of electrodes and an electrolyte comprising an ionic liquid, at least one of the electrodes comprising a plurality of frustules having a surface active material formed thereon.

[0209] In some embodiments, the supercapacitor comprises a pair of electrodes in contact with an electrolyte, at least one of the electrodes comprising a plurality of frustules and zinc oxide.

[0210] In some embodiments, the supercapacitor comprises a pair of electrodes in contact with a non-aqueous electrolyte, at least one of the electrodes comprising a plurality of frustules and a manganese oxide.

[0211] In some embodiments, a method of making a supercapacitor comprises forming a separator between a pair of electrodes, the separator comprising a frustule, an electrolyte, and a thermally conductive additive, the thermally conductive additive configured to substantially absorb near infrared (NIR) radiation upon application to the separator, thereby heating the separator to accelerate drying.

[0212] Certain objects and advantages have been described herein to summarize the invention and its advantages over the prior art. Of course, it should be understood that not all of these objects and advantages need be achieved in accordance with any particular embodiment. For example, one skilled in the art will recognize that the invention can be practiced to achieve or optimize one advantage or set of advantages without necessarily achieving other objects or advantages.

[0213] All of these embodiments are intended to be within the scope of the present invention. These and other embodiments will become readily apparent to those skilled in the art from the following detailed description, which refers to the accompanying drawings, and the invention is not limited to the specific embodiments disclosed.

[0214] These and other features, aspects, and advantages of the present disclosure will now be described with reference to the drawings of specific embodiments that are illustrative of, but not limiting of, particular embodiments. [Brief explanation of the drawings]

[0215] [Figure 1] This is a scanning electron microscope (SEM) image of diatomaceous earth with frustules. [Figure 2] 1 is an SEM image of an exemplary frustule comprising a porous surface. [Figure 3] 1 is an SEM image of exemplary frustules, each having a substantially cylindrical shape. [Figure 4A] 1 is a flow diagram of exemplary steps in a putamen isolation process. [Figure 4B] 1 is a flow diagram of exemplary steps in a putamen isolation process. [Figure 5A] 1 illustrates an exemplary embodiment of a frustule with structures on both the exterior and interior surfaces. [Figure 5B] An SEM image at 50k magnification of an example of a silver-seeded frustule surface is shown. [Figure 5C] An SEM image of the silver-seeded frustule surface at 250k magnification is shown. [Figure 5D] 2 shows an SEM image at 20k magnification of the frustule surface on which silver nanostructures are formed. [Figure 5E] 1 shows an SEM image at 150k magnification of the frustule surface on which silver nanostructures are formed. [Figure 5F] 1 shows an SEM image at 25k magnification of a diatom frustule flake with a surface coated with silver nanostructures. [Figure 5G] An SEM image of the zinc oxide seeded frustule surface at 100k magnification is shown. [Figure 5H] An SEM image of the zinc oxide seeded frustule surface at 100k magnification is shown. [Figure 5I] 1 shows an SEM image at 50k magnification of the frustule surface on which zinc oxide nanowires are formed. [Figure 5J] 1 shows an SEM image at 25k magnification of the frustule surface on which zinc oxide nanowires are formed. [Figure 5K]1 shows an SEM image at 10k magnification of the frustule surface on which zinc oxide nanoplates have been formed. [Figure 5L] 1 shows an SEM image at 50k magnification of the frustule surface on which silver nanostructures are formed. [Figure 5M] 1 shows an SEM image at 10k magnification of the frustule surface on which zinc oxide nanowires are formed. [Figure 5N] 1 shows an SEM image at 100k magnification of the frustule surface on which zinc oxide nanowires are formed. [Figure 5O] 1 shows an SEM image at 500k magnification of a multiple frustule surface on which zinc oxide nanowires have been formed. [Figure 5P] 1 shows an SEM image at 5k magnification of the frustule surface on which zinc oxide nanowires are formed. [Figure 5Q] 2 shows an SEM image at 20k magnification of the surface of a frustule on which manganese oxide nanostructures are formed. [Figure 5R] 1 shows an SEM image at 50k magnification of the surface of a frustule on which manganese oxide nanostructures are formed. [Figure 5S] TEM image of manganese oxide nanocrystals formed on the surface of the frustule. [Figure 5T] 1 shows an electron diffraction pattern of manganese oxide particles. [Figure 5U] 1 shows an SEM image at 10k magnification of the frustule surface on which manganese-containing nanofibers are formed. [Figure 5V] This shows an SEM image at 20k magnification of the manganese oxide nanostructures on which the shells are formed. [Figure 5W] 1 shows an SEM image at 50k magnification of a cross section of an example of a frustule on which manganese oxide nanostructures are formed. [Figure 5X] This shows a 100kx magnification SEM image of the frustule formed on the manganese oxide nanostructure. [Figure 6] 1 illustrates a schematic diagram of an exemplary embodiment of an energy storage device. [Figure 7]7A to 7E show schematic diagrams of an example energy storage device during various steps of different manufacturing processes. [Figure 8] 1 illustrates an exemplary embodiment of a separator for an energy storage device incorporating a frustule in the separator layer. [Figure 9] 1 illustrates an exemplary embodiment of an electrode for an energy storage device incorporating frustules in the electrode layer. [Figure 10] 1 shows a graph of a discharge curve of an exemplary energy storage device. [Figure 11] 11 shows a graph of the cycling performance of the energy storage device of FIG. 10. [Figure 12] 1 shows a graph of an example of the charge and discharge performance of an energy storage device. [Figure 13] 13 shows another graph of the charge and discharge performance of the energy storage device of FIG. 12. [Figure 14A] FIG. 1 shows a cross-sectional view of a supercapacitor with both electrodes configured as a double layer capacitor. [Figure 14B] 14B shows a cross-sectional view of the supercapacitor of FIG. 14A in operation when a voltage is applied between the electrodes. [Figure 15] FIG. 1 shows a cross-sectional view of a supercapacitor with electrodes configured as a pseudocapacitor. [Figure 16A] Experimental charge-discharge measurements were performed on a supercapacitor with symmetric printed electrodes, each with opposite polarity and a frustule of zinc oxide (ZnxOy) nanostructures formed thereon. [Figure 16B] Experimental charge-discharge measurements are shown for a supercapacitor with symmetric printed electrodes, each with opposite polarity and a frustule of zinc oxide (ZnxOy) nanostructures formed thereon. [Figure 17A] Experimental charge-discharge measurements are shown for a supercapacitor with symmetric printed electrodes, each with opposite polarity and a manganese oxide (MnxOy) nanostructure frustule formed thereon. [Figure 17B]Experimental charge-discharge measurements are shown for a supercapacitor with symmetric printed electrodes, each with opposite polarity and a manganese oxide (MnxOy) nanostructure frustule formed thereon. [Figure 17C] Experimental charge-discharge measurements are shown for a supercapacitor with symmetric printed electrodes, each with opposite polarity and a manganese oxide (MnxOy) nanostructure frustule formed thereon. [Figure 17D] Experimental charge-discharge measurements are shown for a supercapacitor with symmetric printed electrodes, each with opposite polarity and a manganese oxide (MnxOy) nanostructure frustule formed thereon. [Figure 18A] Experimental charge-discharge measurements are shown for a supercapacitor with asymmetric printed electrodes, one of which has a manganese oxide (MnxOy) nanostructure frustule formed thereon and the other electrode has a CNT frustule formed thereon, with opposite polarity. [Figure 18B] Experimental charge-discharge measurements are shown for a supercapacitor with asymmetric printed electrodes, one of which has a manganese oxide (MnxOy) nanostructure frustule formed thereon and the other electrode has a CNT frustule formed thereon, with opposite polarity. [Figure 18C] Experimental charge-discharge measurements are shown for a supercapacitor with asymmetric printed electrodes, one of which has a manganese oxide (MnxOy) nanostructure frustule formed thereon and the other electrode has a CNT frustule formed thereon, with opposite polarity. [Figure 18D] Experimental charge-discharge measurements are shown for a supercapacitor with asymmetric printed electrodes, one of which has a manganese oxide (MnxOy) nanostructure frustule formed thereon and the other electrode has a CNT frustule formed thereon, with opposite polarity. [Figure 18E]Experimental charge-discharge measurements are shown for a supercapacitor with asymmetric printed electrodes, one of which has a manganese oxide (MnxOy) nanostructure frustule formed thereon and the other electrode has a CNT frustule formed thereon, with opposite polarity. [Figure 19A] 1 shows experimental charge-discharge measurements performed on a supercapacitor with symmetric printed electrodes, each with opposite polarity and a frustule of CNT formed thereon. [Figure 19B] 1 shows experimental charge-discharge measurements performed on a supercapacitor with symmetric printed electrodes, each with opposite polarity and a frustule of CNT formed thereon. DETAILED DESCRIPTION OF THE INVENTION

[0216] Although specific embodiments and examples are described below, those skilled in the art will recognize that the invention extends beyond the specifically disclosed embodiments and / or employs obvious modifications and equivalents thereof, and therefore, the scope of the invention is not limited to the specific embodiments described below.

[0217] Energy storage devices that power electronic devices typically include batteries (e.g., rechargeable batteries), capacitors, and supercapacitors (e.g., EDLCs, pseudocapacitors, and hybrid supercapacitors). Energy storage devices can include asymmetric energy storage devices, such as battery-capacitor hybrids. Energy storage devices can be manufactured using printing techniques, such as screen printing, roll-to-roll printing, and inkjet printing. Printed energy storage devices can facilitate a reduction in the thickness of the energy storage device, enabling compact energy storage. Increased energy storage density can facilitate the use of printed energy storage devices in applications requiring high power, such as solar energy storage. Unlike energy storage devices with rigid outer cases, printed energy storage devices can be implemented on flexible substrates, enabling flexible energy storage devices. Flexible energy storage devices can facilitate the fabrication of flexible electronic devices, such as flexible electronic display media. Due to their thin thickness and / or flexible structure, printed energy storage devices can power cosmetic patches, medical diagnostic products, remote sensor arrays, smart cards, smart packaging, smart clothing, greeting cards, and the like.

[0218] The reliability and durability of printed energy storage devices can be a barrier to increased adoption of printed batteries. Because printed energy storage devices typically lack a rigid outer case, such devices cannot withstand compressive pressures or deformation operations during use or manufacturing. Variations in the layer thickness of an energy storage device in response to compressive stresses or deformation operations can adversely affect device reliability. For example, some printed energy storage devices include electrodes spaced apart by a separator. Deviations in separator thickness can cause short circuits between electrodes; for example, a short circuit can occur if the separator is compressible and cannot maintain the spacing between the electrodes under compressive pressure or deformation operations.

[0219] The costs associated with manufacturing printed energy storage devices can also be a barrier to using printed energy storage devices to power a wide range of applications. Reliable manufacturing of energy storage devices using printing techniques can facilitate cost-effective energy storage device manufacturing. Printing energy storage devices can enable the device printing process to be integrated into the manufacturing of electronic devices, e.g., printed electronic devices can be powered by printed energy storage devices, further reducing costs. However, insufficient device structure robustness can hinder device integrity throughout the manufacturing process, reducing the feasibility of some printing techniques and hindering the cost-effective manufacturing of printed energy storage devices. The thickness of printed energy storage device layers can also hinder the use of certain printing techniques in the manufacturing process, for example, when the device layer thickness becomes greater than the film thickness that can be efficiently printed with the printing technique.

[0220] As described herein, a frustule may have significant mechanical strength and shear stress resistance due to, for example, its size, shape, porosity, and / or material. According to some embodiments described herein, an energy storage device includes one or more components, such as one or more layers or films of a printed energy storage device, that comprise a frustule. An energy storage device that comprises a frustule may have the mechanical strength and / or structural integrity to withstand compressive pressures and / or deformation operations that may occur during manufacturing and use, thereby preventing failure and increasing device reliability. An energy storage device that comprises a frustule may be able to withstand variations in layer thickness and maintain a uniform or substantially uniform device layer thickness. For example, a separator that comprises a frustule may facilitate improved energy storage device reliability by withstanding compressive pressures and deformation operations and maintaining a uniform or substantially uniform spacing between electrodes to reduce or prevent device shorting.

[0221] Increasing the mechanical strength of an energy storage device with a frustrating shell facilitates reliable manufacturing of energy storage devices using a variety of printing techniques, thereby increasing the yield and / or integrity of the manufacturing process, along with the manufacturing process of the application powered by the device, and enabling cost-effective device manufacturing.

[0222] Energy storage devices can be printed using inks that include a furring husk. For example, one or more layers of a printed energy storage device can include a furring husk. One or more layers of a printed energy storage device with a furring husk can be reliably printed onto a variety of substrates, including, but not limited to, flexible and non-flexible substrates, textiles, devices, plastics, various films such as metal and semiconductor films, various papers, and / or combinations thereof. For example, suitable substrates can include graphite paper, graphene paper, polyester film (e.g., Mylar®), polycarbonate film, aluminum foil, copper foil, stainless steel foil, and / or carbon foam, etc. Fabrication of printed energy storage devices on flexible substrates enables the use of flexible printed energy storage devices in a variety of devices and implementations due to the increased reliability of such particular printed energy storage devices, e.g., increased durability as a result of one or more layers including a furring husk.

[0223] The increased mechanical strength of printed energy storage devices with a frustule may also allow for a reduction in the thickness of the printed device layers. For example, the frustule may provide structural support for the energy storage device layers, allowing for thin layers with sufficient structural stability to withstand compressive pressures and deformation operations, thereby reducing the overall device thickness. Reducing the thickness of printed energy storage devices may further improve the energy storage density of the printed device and / or enable more widespread use of the printed device.

[0224] Printed energy storage devices comprising a frustule may have improved device performance, e.g., improved device efficiency. Reducing the thickness of the energy storage device layer may enable improved device performance. The performance of the energy storage device may depend at least in part on the internal resistance of the energy storage device. For example, the performance of the energy storage device may depend at least in part on the spacing distance between the first electrode and the second electrode. Reducing the separator film thickness, as a predetermined measure of reliability, may reduce the distance between the first electrode and the second electrode, reduce the internal resistance, and improve the efficiency of the energy storage device. The internal resistance of the energy storage device may depend at least in part on the mobility of ionic species between the first electrode and the second electrode. The porosity of the frustule surface may provide mobility for ionic species. For example, a separator comprising a frustule may facilitate the mobility of ionic species between the electrodes while enabling more structurally stable separation between the electrodes of the energy storage device. The porosity of the frustule surface may facilitate a direct path for mobile ionic species between the first electrode and the second electrode, reducing resistance and / or increasing efficiency. Reducing the thickness of the electrode layer comprising the frustule and the porosity of the electrode frustule can also improve storage device performance. Reducing the electrode thickness can increase access for ionic species to the active material in the electrode. The porosity and / or conductivity of the frustule in the electrode can facilitate the mobility of ionic species within the electrode. The frustule in the electrode can also improve device performance, for example, by acting as a substrate onto which the active material and / or structures comprising the active material are applied or formed, thereby facilitating access for ionic species to the active material by increasing the surface area for the active material.

[0225] FIG. 1 is an SEM image of diatomaceous earth having frustules 10. The frustules 10 generally have a cylindrical shape, although some frustules are broken or have different shapes. In some embodiments, the cylindrical frustules 10 have a diameter between about 3 μm and about 5 μm. In some embodiments, the cylindrical frustules 10 have a length between about 10 μm and about 20 μm. Other diameters and / or lengths are possible. The frustules 10 may have significant mechanical strength and shear stress resistance due to, for example, their structure (e.g., diameter, shape), material, and / or a combination thereof. For example, the mechanical strength of the frustules 10 may be inversely proportional to the size of the frustules 10. In some embodiments, frustules 10 having a major axis within a range between about 30 μm and about 130 μm can withstand a compressive force of about 90 μN to about 730 μN.

[0226] FIG. 2 is an SEM image of an example frustule 10 including a porous surface 12. The porous surface 12 includes circular or substantially circular openings 14. Other shapes of the openings 14 are possible (e.g., curved, polygonal, elongated, etc.). In some embodiments, the porous surface 12 of the frustule 10 has uniform or substantially uniform porosity, e.g., includes openings 14 having uniform or substantially uniform shapes, sizes, and / or spacing (see, e.g., FIG. 2). In some embodiments, the porous surface 12 of the frustule 10 has variable porosity, e.g., includes openings 14 of different shapes, sizes, and / or spacing. The porous surfaces 12 of multiple frustules 10 can have uniform or substantially uniform porosity, or the porosity of the porous surfaces 12 of different frustules 10 can vary. The porous surface 12 can have nanoporosity, microporosity, mesoporosity, and / or macroporosity.

[0227] FIG. 3 is an SEM image of example frustules 10, each having a cylindrical or substantially cylindrical shape. Frustule characteristics can vary among different species of diatoms, with each diatom species having a different shape, size, porosity, material, and / or other frustule characteristics. Commercially available diatomaceous earth (e.g., from Mount Sylvia Diatomite Pty Ltd., Canberra, Australia; Continental Chemical USA, Inc., Fort Lauderdale, Florida; and Lintech International, Inc., Macon, Georgia) can be a source of frustules. In some embodiments, diatomaceous earth is sorted according to predetermined frustule characteristics. For example, sorting can result in frustules each having predetermined characteristics, such as shape, size, material, porosity, and / or combinations thereof. Sorting of frustules may include one or more separation processes, such as, for example, filtering, screening (e.g., using a vibrating sieve to separate frustules according to shape or size), separation processes involving voraxial or centrifugation techniques (e.g., separation according to frustule density), other suitable solid-solid separation processes, and / or combinations thereof. Frustules may also be available (e.g., commercially available) already sorted according to frustule characteristics, such that the frustules already have a uniform or substantially uniform shape, size, material, porosity, other predetermined frustule traits, and / or combinations thereof. For example, frustules available from a certain region (e.g., a region of a country such as the United States, Peru, Australia, a region on the globe, etc.) and / or a certain natural environment (e.g., a freshwater environment, a saltwater environment, etc.) may comprise frustules of species typically found in that region and / or environment, providing frustules having a uniform or substantially uniform shape, size, material, porosity, other predetermined frustule traits, and / or combinations thereof.

[0228] In some embodiments, a separation process can be used to sort the frustules to retain only unbroken frustules, or to retain substantially only unbroken frustules. In some embodiments, a separation process can be used to remove broken or small frustules to obtain only cylindrical frustules having a particular length and / or diameter, or to obtain substantially only cylindrical frustules (e.g., as shown in FIG. 3). A separation process to remove broken frustules can include screening, e.g., using a sieve with a mesh size selected to retain only frustules having a predetermined dimension, or to retain substantially only frustules having a predetermined dimension. For example, the sieve mesh size can be selected to remove frustules having a dimension (e.g., length or diameter) of about 40 μm or less, about 30 μm or less, about 20 μm or less, or about 10 μm or less (including the boundaries and ranges between the above values). Other sieve mesh sizes may also be suitable.

[0229] In some embodiments, the separation process to remove broken frustules includes applying ultrasound to the frustules in the dispersion, e.g., sonication, which involves exposing frustules dispersed in a water bath to ultrasound. Sonication parameters, such as power, frequency, and / or duration, can be adjusted based at least in part on one or more characteristics of the frustules. In some embodiments, sonication involves the use of sound waves having a frequency between about 20 kilohertz (kHz) and about 100 kHz, between about 30 kHz and about 80 kHz, or between about 40 kHz and about 60 kHz. In some embodiments, sonication may use sound waves having a frequency of about 20 kHz, about 25 kHz, about 30 kHz, about 35 kHz, about 40 kHz, or about 45 kHz, including boundaries and ranges between the above values. The sonication step may have a duration between about 2 minutes and about 20 minutes, between about 2 minutes and about 15 minutes, or between about 5 minutes and about 10 minutes. In some embodiments, the sonication step may have a duration of about 2 minutes, about 5 minutes, about 10 minutes, or a range inclusive of the above values. For example, a putamen fluid sample may be subjected to ultrasound at a frequency of about 35 kHz for a duration of about 5 minutes.

[0230] In some embodiments, the separation process includes sedimentation. For example, the separation process includes both sonication and sedimentation, where during sonication, heavier particles from the frustule fluid sample are caused to settle out of the suspended phase of the frustule fluid sample. In some embodiments, the sedimentation process of the heavier particles from the frustule fluid sample has a duration of between about 15 seconds and about 120 seconds, between about 20 seconds and about 80 seconds, or between about 30 seconds and about 60 seconds. In some embodiments, the sedimentation has a duration of about 120 seconds or less, about 60 seconds or less, about 45 seconds or less, or about 30 seconds or less.

[0231] The separation process to remove broken frustules may involve the use of high-speed centrifugation techniques for density-based physical separation, e.g., an ultracentrifugation process. For example, the separation process may involve ultracentrifugation of the suspended phase of a frustule fluid sample. Ultracentrifugation parameters, such as angular velocity and / or duration, may depend at least in part on the composition of the suspended phase (e.g., frustule density) and / or the characteristics of the apparatus used. For example, the suspended phase may be ultracentrifuged at angular velocities of between about 10,000 RPM (revolutions per minute) and about 40,000 RPM, between about 10,000 RPM and about 30,000 RPM, between about 10,000 RPM and about 20,000 RPM, or between about 10,000 RPM and about 15,000 RPM. The suspended phase may be ultracentrifuged for a duration of between about 1 minute and about 5 minutes, between about 1 minute and about 3 minutes, or between about 1 minute and about 2 minutes. For example, the suspended phase of a frustule fluid sample can be ultracentrifuged for approximately 1 minute at an angular velocity of approximately 13,000 RPM.

[0232] 4A and 4B are flow diagrams of exemplary steps of frustule separation process 20. Process 20 can separate broken and / or unbroken diatom frustules from a solid mixture having, for example, broken and unbroken diatom frustules. In some embodiments, separation process 20 enables large-scale frustule classification.

[0233] As described herein, there are two possible sources of diatom frustules for nanostructured materials and / or nanodevices: living diatoms and diatomaceous earth. Diatoms can be harvested directly from nature or cultivated. Artificially, large numbers of identical silica frustules can be cultivated within a few days. To use natural diatoms for nanostructured materials and / or nanodevices, a separation process can be performed to separate the diatoms from other organic materials and / or substances. Another method is the use of diatomaceous earth, which is abundant in deposits and has low material costs.

[0234] Diatomaceous earth can have frustules ranging from a mixture of different diatom species to a single diatom species (e.g., containing several freshwater sediments). Diatomaceous earth can contain contaminants of different origins in addition to broken and / or intact diatom frustules. Depending on the application, only intact diatom frustules, only broken frustules, or a mixture of both can be used. For example, if intact frustules are isolated, diatomaceous earth with one type of frustule can be used.

[0235] In some embodiments, the separation method comprises separating intact diatom frustules from broken pieces of diatom frustules. In some embodiments, the separation process comprises sorting diatom frustules according to common frustule characteristics (e.g., size, including length and diameter, shape, and / or material) and / or sorting portions of diatom frustules based on common frustule characteristics (e.g., size, including length and diameter, shape, degree of breakage, and / or material). For example, the separation process may extract multiple diatom frustules or diatom frustule portions that share at least one common characteristic. In some embodiments, the separation process comprises removing contaminants of different chemical origin from the diatom frustules and / or diatom frustule portions.

[0236] Diatoms and diatom frustules, which remain intact over time, can be used in biological, ecological, and related geoscience studies. Numerous methods have been developed to extract small samples of frustules from water and sediments. Sediments (diatomaceous earth) contain diatom frustules (broken and unbroken) as well as carbonates, mica, clay, organic matter, and other sedimentary particles. Isolation of intact frustules can involve three main steps: removal of organic residues, removal of particles of different chemical origin, and removal of broken fragments. Removal of organic matter can be achieved by heating the sample in bleach (e.g., hydrogen peroxide and / or nitric acid) and / or annealing at higher temperatures. Carbonates, clays, and other soluble non-silica materials can be removed with hydrochloric and / or sulfuric acid. Several methods are applicable to the separation of broken and intact frustules: sieving, sedimentation, centrifugation, heavy-medium centrifugation, split-flow lateral-transport thin separation cells, and combinations of these. All these methods often suffer from the problem of clumping of broken and unbroken frustules, which can degrade the quality of the separation and / or make the separation process suitable only for laboratory-scale samples.

[0237] Scaling up of the isolation procedure could make diatom frustules usable as industrial nanomaterials.

[0238] In some embodiments, separation procedures applicable to industrial-scale diatom separation include separating diatom frustule portions that share at least one common characteristic. For example, the common characteristic can be unbroken diatom frustules or broken diatom frustules. Separation process 20, as shown in Figures 4A and 4B, is an example of a separation procedure that allows for industrial-scale separation of diatoms. In some embodiments, separation procedures that allow for large-scale separation of diatoms can reduce frustule clumping by using surfactants and / or disk stack centrifugation, etc. In some embodiments, the use of surfactants enables large-scale separation. In some embodiments, disk stack centrifugation (e.g., a milk-separation type centrifugation process) enables large-scale classification. For example, using surfactants to disperse diatom frustules and classifying them based on frustule characteristics in a disk stack centrifuge can facilitate large-scale classification of diatoms by reducing diatom frustule clumping. Conventional non-disk stack centrifugation processes cause frustules to settle. The supernatant is discarded, and the settled frustules are redispersed in a solvent, followed by centrifugation to again settle the frustules. This process is repeated until the desired separation is achieved. The disc stack centrifugation process can continuously redisperse and separate the settled frustules. For example, a phase rich in intact frustules is continuously circulated through the disc stack centrifuge to become more enriched. In some embodiments, disc stack centrifugation can separate broken diatom frustules from unbroken diatom frustules. In some embodiments, disc stack centrifugation can separate diatom frustules according to diatom frustule characteristics. For example, disc stack centrifugation allows for the extraction of frustules that share at least one common characteristic (e.g., size, shape, degree of breakage, and / or material).

[0239] A separation procedure that allows for the separation of frustules on an industrial scale, such as the separation process 20 shown in Figures 4A and 4B, may include the following steps:

[0240] 1. Particles of the solid mixture (e.g., diatomaceous earth) comprising diatom frustules and / or diatom frustule portions can be rock-like and breakable into smaller particles. For example, the particle size of the solid mixture can be reduced to facilitate the separation process 20. In some embodiments, the diatomaceous earth can be gently crushed or ground using, for example, a mortar and pestle, a jar mill, a rock crusher, and / or combinations thereof to obtain a powder.

[0241] 2. In some embodiments, components of the diatomaceous earth larger than the diatom frustules and diatom frustule portions may be removed via a sieving step. In some embodiments, the sieving step is performed after the diatomaceous earth is crushed. For example, the diatomaceous earth powder may be sieved to remove powder particles larger than the frustules. Sieving may be facilitated by dispersing the solid mixture (e.g., crushed diatomaceous earth) in a liquid solvent. The solvent may be water and / or other suitable liquid solvent. Dispersion of the solid mixture in the solvent may be facilitated by sonicating the mixture comprising the solid mixture and the solvent. Other methods of facilitating dispersion may also be suitable. In some embodiments, the dispersion comprises a weight percent of diatoms in the range of about 1 weight percent to about 5 weight percent, about 1 weight percent to about 10 weight percent, about 1 weight percent to about 15 weight percent, or about 1 weight percent to about 20 weight percent. The concentration of the solid mixture in the dispersion may be reduced to facilitate the sieving step, which removes particles of the dispersion larger than the frustules. The openings in the sieve depend on the size of the diatoms in the sample. For example, a suitable sieve may have a mesh size of about 20 micrometers or other suitable mesh size that allows for the removal of dispersed particles of the solid mixture larger than the frustules (e.g., the sieve may have a mesh size of about 15 micrometers to about 25 micrometers, or about 10 micrometers to about 25 micrometers). Vibrating sieves may be used to effectively increase the flow through the sieve.

[0242] 3. In some embodiments, the separation process includes a purification step to remove organic contaminants from the frustules (e.g., diatom frustules or diatom frustule portions). Suitable processes for removing organic contaminants may include soaking and / or heating the diatoms in bleach (e.g., nitric acid and / or hydrogen peroxide) and / or annealing the frustules at higher temperatures. For example, a sample of frustules may be heated in a volume of solution comprising about 10 volume percent to about 50 volume percent (e.g., 30 volume percent) hydrogen peroxide for about 1 minute to about 15 minutes (e.g., 10 minutes). Other compositions, concentrations, and / or durations may also be suitable. For example, the composition of the solution used, the concentration of the solution used, and / or the duration of heating may depend on the composition of the sample being purified (e.g., the organic contaminants and / or the type of diatom). In some embodiments, the diatoms may be heated in the solution until no more or substantially no more bubbles emerge from the solution (e.g., indicating complete or substantially complete removal of the organic contaminants) to facilitate sufficient removal of the organic contaminants. Immersion in the solution and / or heating may be repeated until the organic contaminants are removed or substantially removed.

[0243] Purification of the frustules from organic contaminants may be followed by washing with water. In some embodiments, the diatoms may be washed with a liquid solvent (e.g., water). The diatoms may be separated from the solvent, for example, via a sedimentation process including a centrifugation step. Suitable centrifugation techniques include, for example, a disc stack centrifuge, a decanter centrifuge, a tubular bowl centrifuge, and / or combinations thereof.

[0244] 4. In some embodiments, the separation process includes a purification process that removes inorganic contaminants. Inorganic contaminants may be removed by mixing the diatoms with hydrochloric acid and / or sulfuric acid. Inorganic contaminants may include carbonates, clays, and other soluble non-silica materials. For example, a sample of diatoms may be mixed with a volume of a solution comprising about 15 volume percent to about 25 volume percent hydrochloric acid (e.g., about 20 volume percent hydrochloric acid) for a duration of about 20 minutes to about 40 minutes (e.g., 30 minutes). Other compositions, concentrations, and / or durations may also be suitable. For example, the composition of the solution used, the concentration of the solution used, and / or the duration of mixing may depend on the composition of the sample being purified (e.g., the type of inorganic contaminant and / or diatom). In some embodiments, the diatoms may be mixed in solution until the solution stops or substantially stops foaming (e.g., indicating complete or substantially complete removal of the inorganic contaminants) to facilitate sufficient removal of the inorganic contaminants. Mixing the diatoms with the solution can be repeated until the inorganic contaminants are removed or substantially removed.

[0245] Purification of the diatoms from soluble inorganic contaminants may be followed by washing with water. In some embodiments, the diatoms may be washed with a liquid solvent (e.g., water). The frustules may be separated from the solvent, for example, via a sedimentation process including a centrifugation step. Suitable centrifugation techniques include, for example, a disc stack centrifuge, a decanter centrifuge, a tubular bowl centrifuge, and / or combinations thereof.

[0246] 5. In some embodiments, the separation process comprises dispersing the frustules in a surfactant. The surfactant may facilitate separation of the frustules and / or frustule portions from one another and reduce clumping of the frustules and / or frustule portions. In some embodiments, an additive is used to reduce clumping of the diatoms. For example, the diatoms may be dispersed in the surfactant and additive. In some embodiments, dispersion of the frustules in the surfactant and / or additive may be facilitated by sonicating a mixture comprising the diatoms, surfactant and / or additive.

[0247] 6. In some embodiments, the broken frustule pieces may be extracted by a wet sieving process. For example, a filtration process may be used. In some embodiments, the filtration process comprises using a sieve to remove smaller pieces of broken frustules. The sieve may have a mesh size suitable for removing smaller pieces of broken frustules (e.g., a 7 micrometer sieve). The wet sieving process inhibits or prevents small sediments from clumping in the sieve pores, for example, by preventing agglomeration of the sediment, and / or allowing small particles to pass through the sieve pores. Preventing agglomeration may include, for example, stirring, bubbling, shaking, or combinations thereof, of the sediment material on the sieve mesh. In some embodiments, the filtration process may be sequential (e.g., multiple sieves in a machine with a single input and output) through a set of sieves (e.g., those with progressively smaller pore or mesh sizes).

[0248] 7. In some embodiments, continuous centrifugation of the frustules in liquid (a milk separator-type machine) can be used. For example, a disc stack centrifugation can be used. This process can be used to separate diatoms according to common characteristics, for example, to further separate broken frustule pieces from unbroken frustules. In some embodiments, the disc stack centrifugation step can be repeated to achieve a desired separation (e.g., a desired level of separation of broken frustules from unbroken frustules).

[0249] 8. As described herein, the frustules may be washed in a solvent followed by a sedimentation process (e.g., centrifugation) to extract the frustules from the solvent. For example, centrifugation can be used to sediment the frustules or frustule portions after each washing step and / or before final use. Suitable centrifugation techniques for sedimenting the frustules after a washing step include continuous centrifugation, including, but not limited to, disc stack centrifugation, decanter centrifugation, and / or tubular bowl centrifugation.

[0250] An exemplary isolation procedure was tested using freshwater diatoms from Mount Silvia Pty Ltd (a diatomite mining company) in Queensland, Australia. The majority of diatoms in the sample contained a single species, Aulacoseira sp. The frustules were cylindrical in shape, approximately 5 micrometers in diameter and 10 to 20 micrometers in length.

[0251] The flowchart of the separation process 20 shown in Figures 4A and 4B is merely an example. The parameter amounts in the flowchart are given as example amounts (e.g., appropriate for selected samples only). For example, the amounts may vary for different types of diatoms.

[0252] The surface of diatoms may contain amorphous silica and may also contain negatively charged silanol groups. The isoelectric point found from zeta potential measurements is often around pH 2 for diatoms (e.g., similar to amorphous silica).

[0253] In some embodiments, the surfactant may comprise a cationic surfactant. Suitable cationic surfactants include benzalkonium chloride, cetrimonium bromide, laurylmethyl gluceth-10 hydroxypropyldimonium chloride, benzethonium chloride, bronidox, dimethyldioctadecylammonium chloride, tetramethylammonium hydroxide, and / or mixtures thereof. The surfactant may also be a nonionic surfactant. Suitable nonionic surfactants include cetyl alcohol, stearyl alcohol, cetostearyl alcohol, oleyl alcohol, polyoxyethylene glycol alkyl ethers, octaethylene glycol monododecyl ether, glucoside alkyl ethers, decyl glucoside, polyoxyethylene glycol octylphenol ether, Triton X-100, nonoxynol-9, glyceryl laurate, polysorbates, poloxymers, and / or combinations thereof.

[0254] In some embodiments, one or more additives may be added to reduce clumping. Suitable additives include potassium chloride, ammonium chloride, ammonium hydroxide, sodium hydroxide, and / or combinations thereof.

[0255] The frustule may have one or more modifications applied to its surface. In some embodiments, the frustule may be used as a substrate for forming one or more structures on one or more surfaces of the frustule. FIG. 5A shows an example of a frustule 50 comprising structures 52. For example, the frustule 50 may have a hollow cylindrical or substantially cylindrical shape and may comprise structures 52 on both the outer and inner surfaces of the cylinder. The structures 52 may modify or affect a property or characteristic of the frustule 50 (e.g., the conductivity of the frustule 50). For example, an electrically insulating frustule 50 may be made conductive by forming conductive structures 52 on one or more surfaces of the frustule 50. The frustule 50 may comprise structures 52 comprising silver, aluminum, tantalum, brass, copper, lithium, magnesium, and / or combinations thereof. In some embodiments, the frustule 50 comprises structures 52 comprising ZnO. In some embodiments, the frustule 50 includes a structure 52 comprising an oxide of manganese, such as manganese dioxide (MnO), manganese (II, III) oxide (MnO), manganese (II) oxide (MnO), manganese (III) oxide (MnO), and / or manganese oxyhydroxide (MnOOH). In some embodiments, the frustule 50 includes a structure 52 comprising other metal-containing compounds or oxides. In some embodiments, the frustule 50 includes a structure 52 comprising a semiconductor, such as silicon, germanium, silicon germanium, gallium arsenide, and / or combinations thereof. In some embodiments, the frustule 50 includes a modified structure 52 over the entire or substantially the entire surface of the frustule 50.

[0256] The structures 52 applied or formed on the surface of the frustule 50 can have a variety of shapes, sizes, and / or other characteristics. The frustule 50 can have structures 52 with uniform or substantially uniform shapes, sizes, and / or other characteristics of the structures 52. In some embodiments, the frustule 50 can have structures 52 comprising nanowires, nanotubes, nanosheets, nanoflakes, nanospheres, nanoparticles, rosette-shaped structures, and / or combinations thereof. In some embodiments, the nanostructures can have dimensions ranging from about 0.1 nanometers (nm) to about 1000 nm in length. In some embodiments, the dimensions are the diameter of the nanostructure. In some embodiments, the dimensions are the longest dimension of the nanostructure. In some embodiments, the dimensions are the length and / or width of the nanostructure. The nanostructures on the surface of the frustule promote a large surface area for the material, providing the material with increased surface area on which electrochemical reactions can occur. In some embodiments, diatom frustules may reduce, prevent, or substantially prevent agglomeration of nanostructures during the manufacturing process and / or in products produced by the manufacturing process (e.g., electrodes manufactured using diatom frustules, devices including such electrodes). Reducing nanostructure agglomeration may facilitate increasing the active surface area for electrolyte access (e.g., increased active surface area of ​​an electrode, better electrical performance of a device including such an electrode). In some embodiments, the porosity of the surface of the diatom frustules may facilitate electrolyte access to the active surface area, such as facilitating the diffusion of electrolyte ions to the active surface of an electrode (e.g., diatom frustules may have pore sizes from about 1 nanometer (nm) to about 500 nm).

[0257] In some embodiments, the frustules 50 may be thickly coated with nanostructures 52. In some embodiments, the ratio of the mass of the nanostructures 52 to the mass of the frustules 50 is between about 1:1 and about 20:1, between about 5:1 and about 20:1, or between about 1:1 and about 10:1. The nanostructures 52 preferably have a mass greater than the mass of the frustules 50 before coating. The mass of the nanostructures 52 may be determined by weighing the frustules 50 before and after coating and taking the difference as the mass of the nanostructures 52.

[0258] The structures 52 can be formed or deposited on the surface of the frustule 50, at least in part by combining the frustule 50 with a formulation comprising the desired substance to allow coating or seeding of the structures 52 on the surface of the frustule 50.

[0259] As described herein, the structures 52 on the surface of the frustule 50 may comprise zinc oxide, e.g., zinc oxide nanowires. In some embodiments, zinc oxide nanowires may be formed by combining the frustule 50 with a solution having zinc acetate dihydrate (Zn(CHCO)2·2H0) and ethanol. For example, a solution having zinc acetate dihydrate at a concentration of 0.005 mol / L (M) in ethanol may be combined with the frustule 50 to coat the surface of the frustule 50. The coated frustule 50 may then be air-dried and rinsed with ethanol. In some embodiments, the dried frustule 50 may then be annealed (e.g., at a temperature of approximately 350°C). Zinc oxide nanowires may then be grown on the coated surface of the frustule 50. In some embodiments, the annealed frustule 50 may be maintained at a temperature above room temperature (e.g., near a temperature of approximately 95°C) to promote the formation of zinc oxide nanowires.

[0260] The frustule 50 may also include a material formed or deposited on the surface of the frustule 50 to modify the properties or characteristics of the frustule 50. For example, an electrically insulating frustule 50 may be made conductive by forming or applying a conductive material on one or more surfaces of the frustule. The frustule 50 may include silver, aluminum, tantalum, brass, copper, lithium, magnesium, and / or combinations thereof, etc. In some embodiments, the frustule 50 includes a material comprising ZnO. In some embodiments, the frustule 50 includes a material comprising an oxide of manganese. In some embodiments, the frustule 50 includes a material comprising a semiconductor, such as silicon, germanium, silicon germanium, gallium arsenide, and / or combinations thereof, etc. The surface modification material may be present on the outer surface and / or the inner surface of the frustule 50. In some embodiments, the frustule 50 includes a surface modification material over the entire surface or substantially the entire surface of the frustule 50.

[0261] The substance can be formed or deposited on the surface of the frustule 50, at least in part, by combining the frustule 50 with a formulation containing the desired substance to allow for coating or sheeting onto the surface of the frustule 50.

[0262] As described herein, a substance may be deposited on the surface of the frustule 50. In some embodiments, the substance comprises a conductive metal, such as silver, aluminum, tantalum, copper, lithium, magnesium, brass, or the like. In some embodiments, coating the surface of the frustule 50 with a silver-containing substance involves, at least in part, combining the frustule 50 with a solution having ammonia (NH3) and silver nitrate (AgNO3). In some embodiments, the solution may be prepared by a process similar to that often used to prepare Tollen's reagent. For example, preparing the solution may comprise adding ammonia to aqueous silver nitrate to form a precipitate, then adding more ammonia until the precipitate dissolves. The solution may then be combined with the frustule 50. As an example, 5 milliliters (mL) of ammonia may be added to 150 mL of aqueous silver nitrate with stirring to form a precipitate, then adding another 5 mL of ammonia until the precipitate dissolves. A mixture may then be formed by combining the solution with 0.5 grams (g) of frustules 50 and an aqueous glucose solution (e.g., 4 g of glucose dissolved in 10 mL of distilled water). The mixture may then be placed in a container immersed in a bath maintained at a temperature (e.g., a hot water bath maintained at a temperature of approximately 70° C.) to facilitate coating of the frustules 50.

[0263] [Growth of nanostructures on diatom frustules or diatom frustule segments] As described herein, diatomaceous earth is a naturally occurring deposit of fossilized microorganisms called diatoms. The fossilized microorganisms have highly structured, hard silica frustules, often ranging in size from approximately 1 micrometer to approximately 200 micrometers. Different species of diatoms have different three-dimensional shapes and characteristics, and vary from source to source.

[0264] Diatomaceous earth can comprise highly porous, abrasive, and / or heat-resistant materials. Due to these properties, diatomaceous earth has found a wide variety of applications, including filtration, liquid absorption, insulation, ceramic-like additives, mild abrasives, cleaning, food additives, cosmetics, etc.

[0265] Diatom frustules possess attractive features for nanoscience and nanotechnology, namely, naturally occurring nanostructures, nanopores, nanocavities, and nanobumps (e.g., as shown in Figures 1 to 3). The diversity of frustule shapes (over 105 species) depending on the diatom species is another attractive property. Diatom frustules are formed from silicon dioxide, which can be coated or replaced with useful materials while maintaining the diatom nanostructure. Diatom nanostructures can be useful nanomaterials in many processes and devices, including dye-sensitized solar cells, drug delivery systems, electroluminescent displays, anodes for Li-ion batteries, gas sensors, and biosensors. The formation of MgO, ZrO2, TiO2, BaTiO3, SiC, SiN, and Si can be achieved using high-temperature gas displacement of SiO2.

[0266] In some embodiments, diatom frustules can be coated with three-dimensional nanostructures. The diatom can be coated on its interior and / or exterior surfaces (such as inside the diatom's nanopores). The coating may not exactly preserve the diatom's structure. However, the coating itself may have nanopores and nanobumps. Such silica frustule / nanostructure composites use the frustules as a support. The nanostructured material may have small nanoparticles (nanowires, nanospheres, nanoplates, dense arrays of nanoparticles, nanodisks, and / or nanobelts) tightly bound together. Overall, the composite can have a very large surface area.

[0267] Nanostructures comprising a variety of materials may be formed on the surface of the frustule. In some embodiments, the nanostructures comprise a metallic material. For example, nanostructures formed on one or more surfaces of the frustule may comprise zinc (Zn), magnesium (Mg), aluminum (Al), mercury (Hg), cadmium (Cd), lithium (Li), sodium (Na), calcium (Ca), iron (Fe), lead (Pd), nickel (Ni), silver (Ag), and / or combinations thereof. In some embodiments, the nanostructures comprise a metal oxide. For example, nanostructures formed on the frustule surface may be zinc oxide (ZnO), manganese dioxide (MnO2), manganese(II,III) oxide (Mn3O4), manganese(II) oxide (MnO), manganese(III) oxide (Mn2O3), mercury oxide (HgO), cadmium oxide (CdO), silver(I,III) oxide (AgO), silver(I) oxide (Ag2O), nickel oxide (NiO), lead(II) oxide (PbO), lead(II,IV) oxide (Pb2O3), and lead(II) oxide (PbO). The oxide may comprise lead oxide (PbO2), vanadium (V) oxide (VO5), copper oxide (CuO), molybdenum trioxide (MoO3), iron (III) oxide (Fe2O3), iron (II) oxide (FeO), iron (II,III) oxide (Fe3O4), rubidium (IV) oxide (RuO2), titanium dioxide (TiO2), iridium (IV) oxide (IrO2), cobalt (II,III) oxide (Co3O4), tin dioxide (SnO2), and / or combinations thereof.In some embodiments, the nanostructures may be formed from other metal-containing compounds, such as manganese(III) oxyhydroxide (MnOOH), nickel oxyhydroxide (NiOOH), nickel silver oxide (AgNiO), lead(II) sulfide (PbS), silver lead oxide (AgPbO), bismuth(III) oxide (BiO), silver bismuth oxide (AgBiO), silver vanadium oxide (AgVO), copper(I) sulfide (CuS), iron disulfide (FeS), iron sulfide (FeS), lead(II) iodide (PbI), nickel sulfide (NiS), silver chloride (AgC), or other metal-containing compounds. l), silver chromium oxide or silver chromate (Ag2CrO4), copper(II) oxide phosphate (Cu4O(PO4)2), lithium cobalt oxide (LiCoO2), metal hydrides (e.g., LaCePrNdNiCoMnAl), lithium iron phosphate (LiFePO4, LEP), lithium permanganate (LiMn2O4), lithium manganese dioxide (LiMnO2), Li(NiMnCo)O2, Li(NiCoAl)O2, cobalt oxyhydroxide (CoOOH), titanium nitride (TiN), and / or combinations thereof.

[0268] In some embodiments, the nanostructures formed on the surface of the frustules may comprise non-metallic or organic materials. In some embodiments, the nanostructures may comprise carbon. For example, the nanostructures may comprise multi-walled and / or single-walled carbon nanotubes, graphene, graphite, carbon nano-onions, and / or combinations thereof. In some embodiments, the nanostructures may comprise fluorocarbons (e.g., CF x ), sulfur (S), conductive n / p-type doped polymers (e.g., conductive n / p-type doped polyfluorenes, polyphenylenes, polypyrenes, polyazulenes, polynaphthalenes, polypyrroles, polycarbazoles, polyindoles, polyazepines, polyanilines, polythiophenes, poly3,4-ethylenedioxythiophenes, and / or poly-p-phenylene sulfides), and / or combinations thereof.

[0269] Nanostructures formed on the surface of diatom frustules include 1) silver (Ag) nanostructures, 2) zinc oxide (ZnO) nanostructures, carbon nanotube "forests," and / or 4) manganese-containing nanostructures. As described herein, diatom frustules having nanostructures formed on one or more surfaces thereof can be used as energy storage devices, such as batteries, supercapacitors, solar cells, and / or gas sensors. Nanostructures can be formed on one or more surfaces of intact and / or broken frustules. In some embodiments, the frustules or frustule portions used in the nanostructure formation process can be extracted via a separation procedure (e.g., separation process 20 shown in Figures 4A and 4B) that includes a separation step described herein. In some embodiments, the frustules can be pretreated with one or more functionalizing chemicals (e.g., siloxanes, fluorosiloxanes, proteins, and / or surfactants) prior to growth of the nanostructured active material. In some embodiments, prior to growth of the nanostructured active material, the frustule can be pre-coated with a conductive material (e.g., metal and / or conductive carbon) and / or a semiconductor material, such as silver (Ag), gold (Au), copper (Cu), nickel (Ni), platinum (Pt), graphene, graphite, carbon nanotubes, silicon (Si), germanium (Ge), semiconductor-containing alloys (e.g., aluminum silicon (AlSi) alloys), and / or combinations thereof.

[0270] In some embodiments, nanostructures are grown using a two-step method. The first step generally involves the growth of seeds on the surface of diatom frustules. The seeds are nanostructures that are directly bonded (e.g., chemically bonded) to the surface of the diatom frustules and may have a particular grain size and / or uniformity. Energy may be applied to cause such bonding to occur. The seeding process may be performed under elevated temperatures and / or may involve other methods capable of generating heat or other forms of energy gain.

[0271] The second stage of nanostructure formation generally involves growing the final nanostructure from the seed. The seed-precoated frustule may be immersed in an environment of the initial material under specific conditions. The nanostructure may include one or more of nanowires, nanoplates, dense nanoparticles, nanobelts, nanodisks, and / or combinations thereof. The shape factor may depend on the growth conditions of the nanostructure (e.g., the morphology of the nanostructure may depend on one or more growth conditions during the formation of the nanostructure on the seed layer, such as growth temperature, heating pattern, inclusion of chemical additives during nanostructure growth, and / or combinations thereof).

[0272] [An exemplary process for forming Ag nanostructures on the surface of diatom frustules] The initial coating (or seeding) of silica with silver was performed using microwave, ultrasonic treatment, and surface modification. + This can be done by salt reduction and / or reduction of silver nitrate (AgNO3) with a reducing agent.

[0273] The seed growth step can include dissolving a silver salt and a reducing agent in a solvent (e.g., the reducing agent and solvent can be the same substance) and dispersing the purified frustules in the mixture. During and / or after dissolution, physical forces (such as mixing, stirring, heating, sonication, microwaves, and / or combinations thereof) can be applied. The seed layer growth process can be carried out for a variety of times.

[0274] [Example of growing Ag seeds on the surface of diatom frustules] Example 1 includes the following steps: 0.234 g of purified diatom, 0.1 g of AgNO3, and 50 mL of PEG600 (polyethylene glycol) melted at 60°C are mixed in a beaker. In some embodiments, a mixture comprising clean diatom, a silver-contributing component (e.g., silver nitrate), and a reducing agent can be heated in a cyclic heating mode. In some embodiments, the reducing agent and solvent can be the same substance. For example, the mixture can be heated for approximately 20 to approximately 40 minutes, varying the heat from approximately 100 watts to approximately 500 watts per minute. For example, a mixture comprising cleaned diatom, silver nitrate, and molten PEG was heated in a microwave for approximately 30 minutes. The microwave power was varied from 10 to 500 watts per minute to prevent overheating of the mixture. Some commercially available microwave heaters allow the user to determine the temperature of the contents after a specific period of time and / or to determine multiple temperatures after various periods of time (e.g., to establish a temperature gradient), and the microwave heater controls the power to achieve the results. For example, a microwave heater may determine that less power is required to heat 50 mL of water to 85°C in 2 minutes than to heat 50 mL of water to 85°C in 1 minute, and this adjustment may be made during the heating process, for example, based on a temperature sensor. In another example, a microwave heater may determine that less power is required to heat 50 mL of water to 85°C in 2 minutes than to heat 100 mL of water to 85°C in 2 minutes, and this adjustment may be made during the heating process, for example, based on a temperature sensor. The diatoms were centrifuged and washed with ethanol. The seeds are shown in Figures 5B and 5C.

[0275] Example 2 involves the following steps: 45 mL of N,N-dimethylformamide, 0.194 g of 6000 MW PVP (polyvinylpyrrolidone), 5 mL of 0.8 mM aqueous AgNO3, and 0.1 g of filtered and purified diatoms are mixed in a beaker. A sonicator tip (e.g., 13 mm diameter, 20 kHz, 500 watts) is placed in the mixture, and the beaker with the mixture is placed in an ice bath. The tip amplitude is set to 100%. Sonication is continued for 30 minutes. After this procedure, the diatoms are washed twice in ethanol using bath sonication and centrifugation at 3000 RPM for 5 minutes. This process is then repeated twice more until seeds are visible on the diatoms.

[0276] Figure 5B shows an SEM image at 50kx magnification of silver seeds 62 formed on the surface of diatom frustules 60. Figure 5C shows an SEM image at 250kx magnification of silver seeds 62 formed on the surface of diatom frustules 60.

[0277] [Example of forming silver nanostructures on the surface of silver-seeded diatom frustules] Further coating the sheeted frustules with silver can be performed under an argon (Ar) atmosphere to inhibit the formation of silver oxide. In some embodiments, the diatom frustule portions are calcined (e.g., heated to a temperature between about 400°C and about 500°C) to obtain silver from silver oxide that may form on one or more surfaces of the diatom frustule portions (including silver oxide formed during the process of further coating the seeded diatom frustule portions with silver). For example, calcination of diatom frustule portions can be performed on diatom frustule portions used in producing conductive silver inks (e.g., ultraviolet-curable conductive silver inks as described herein). In some embodiments, calcination can be under an atmosphere (e.g., hydrogen gas) that promotes the reduction of silver oxide to silver. Firing the diatom frustules of the conductive silver ink to obtain silver from silver oxide may improve the conductivity of the conductive silver ink because silver is more conductive than silver oxide and / or may increase silver-to-silver contact points (e.g., silver-to-silver oxide and / or silver oxide-to-silver oxide). Other methods of obtaining silver from silver oxide (e.g., processes involving chemical reactions) may also be suitable instead of or in addition to firing.

[0278] The formation of nanostructures on the seed layer can include a silver salt, a reducing agent, and a solvent, and mixing, heating, and / or titration steps (e.g., to promote interaction of the components of the nanostructure growth process) can be applied to form the nanostructures on the seed layer.

[0279] An example process for forming nanostructures on a seed layer includes the following process.

[0280] Five mL of a 0.0375 M PVP (6000 MW) aqueous solution is placed in one syringe, and 5 mL of a 0.094 M AgNO3 aqueous solution is placed in the other. 0.02 g of seeded, washed, and dried diatoms are mixed with 5 mL of ethylene glycol and heated to approximately 140°C. Using a syringe pump, the diatoms are titrated with a silver salt (e.g., AgNO3) and PVP solution at a rate of approximately 0.1 milliliters per minute (mL / min). After the titration is complete, the mixture is stirred for 30 minutes. The diatoms are then washed (e.g., washed twice) using ethanol, bath sonication, and centrifugation.

[0281] Figures 5D and 5E show SEM images of an example in which silver nanostructures 54 have been formed on the surface of a diatom frustule 60. Figures 5D and 5E show a frustule 60 with a thick, nanostructured coating over a high surface area. Figure 5D is an SEM image of the frustule surface at 20kx magnification, and Figure 5E is an SEM image of the frustule surface at 150kx magnification. Figure 5L is another SEM image at 50kx magnification of a diatom frustule 60 with silver nanostructures on its surface. In Figure 5L, the thick, nanostructured coating of the diatom frustule 60 can be seen.

[0282] Examples of suitable reducing agents for Ag growth include common reducing agents used in electroless silver deposition, such as hydrazine, formaldehyde, glucose, sodium tartrate, oxalic acid, formic acid, ascorbic acid, ethylene glycol, and / or combinations thereof.

[0283] Suitable Ag + Examples of salts and oxides include silver salts. The most commonly used silver salts are water-soluble (e.g., AgNO). Suitable silver salts include ammonium solutions of AgNO (e.g., Ag(NH)NO). In some embodiments, silver(I) salts or oxides may be used (e.g., water-soluble and / or water-insoluble). For example, silver oxide (AgO), silver chloride (AgCl), silver cyanide (AgCN), silver tetrafluoroborate, silver hexafluorophosphate, silver ethyl sulfate, and / or combinations thereof may also be suitable.

[0284] Suitable solvents include water, alcohols such as methanol, ethanol, N-propanol (e.g., 1-propanol, 2-propanol (isopropanol, IPA), 1-methoxy-2-propanol, etc.), butanol (e.g., 1-butanol, 2-butanol (isobutanol)), pentanol (e.g., 1-pentanol, 2-pentanol, 3-pentanol, etc.), hexanol (e.g., 1-hexanol, 2-hexanol, 3-hexanol), octanol, N-octanol (e.g., 1-octanol, 2-octanol, 3-octanol, etc.), tetrahydrofurfuryl alcohol (THFA), cyclohexanol, cyclopentanol, terpineol, etc.; lactones such as butyl lactone, etc.; ethers such as methyl ethyl ether, diethyl ether, ethyl propyl ether, polyethers, etc.; Ketones (including diketones and cycloketones), for example, cyclohexanone, cyclopentanone, cycloheptanone, cyclooctanone, acetone, benzophenone, acetylacetone, acetophenone, cyclopropanone, isophorone, and methyl ethyl ketone; esters, for example, ethyl acetone, dimethyl adipate, propylene glycol monomethyl ether acetate, dimethyl glutarate, dimethyl succinate, glycerin acetate, and carboxylates; carbonates, for example, propylene carbonate, and the like; Polyols (or liquid polyols), glycerol, other polymeric polyols and glycols, such as glycerin, diols, triols, tetraols, pentanols, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, glycol ethers, glycol ether acetates, 1,4-butanediol, 1,2-butanediol, 2,3-butanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,8-octanediol, 1,2-propanediol, 1,3-butanediol, 1,2-pentanediol, ethoxyhexadiol, p-menthane-3,8-diol, 2-methyl-2,4-pentanediol;Tetramethylurea, n-methylpyrrolidone, acetonitrile, tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide (NMF), dimethyl sulfoxide (DMSO); thionyl chloride, sulfuryl chloride, and / or combinations thereof, etc.;

[0285] In some embodiments, the solvent may also function as a reducing agent.

[0286] Exemplary Method for Producing Low-Cost UV-Curable Silver Diatom Conductive Ink Thermosetting silver flake and silver nanoparticle conductive inks are available from numerous manufacturers, including Henkel, Spraylat, Conductive Compounds, DuPont, and Creative Materials. A less common product is ultraviolet (UV) curable silver conductive ink. Only a few companies (e.g., Henkel) offer such inks. UV-curable silver conductive inks are often very expensive due to their high silver loading and high cost per square meter relative to conductivity. Their conductivity can be five to ten times lower than that of thermosetting silver conductive inks applied at the same wet film thickness.

[0287] Clearly, there is a need for low-cost UV-curable silver that has at least the same or better conductivity than currently available UV-curable inks. Because some UV-curable silvers may not fully utilize the large amount of silver present in the ink, there is a need to develop silver inks that use much less silver but have similar or better conductivity and / or curability than current UV-curable silver inks.

[0288] The difficulty in developing UV-curable silver can be attributed to the UV-absorbing properties of silver. In thermally curable silver inks, the highest conductivity can be achieved by using silver flakes with a high aspect ratio to maximize the intra-flake contact area. When these types of silver flakes are mixed with a UV-curable resin system suitable for conductive inks, applied to a surface using a printing or other coating process, and exposed to UV light, much of the UV light can be absorbed by the silver before it can scatter through the wet layer of silver ink. UV absorption by the silver flakes can inhibit or prevent UV-initiated polymerization in the wet ink film (e.g., inhibit or prevent UV-initiated polymerization of the wet ink beyond a certain depth). Reduced polymerization of the ink film can result in an incompletely cured layer of silver ink that does not adhere to the substrate, for example, because most of the bottom of the silver ink layer remains uncured and wet. Using low-aspect-ratio silver particles in UV-curable silver inks can increase the number of possible light scattering paths through the applied layer of silver ink, thereby achieving proper curing throughout the applied layer of silver ink. Low aspect ratio particles have a small surface area and can reduce the inter-flake contact area, which in turn can reduce the conductivity of the cured film relative to what is possible with high aspect ratio flakes. If this curing problem could be solved, larger aspect, high conductivity silver flakes could be used in the silver ink, improving the conductivity of the resulting silver film and / or reducing the amount of silver used to achieve high conductivity.

[0289] In some embodiments, a non-conductive substrate (e.g., a diatom frustule portion, such as a diatom frustule flake) can be plated with silver. Ultraviolet light can pass through perforations on one or more surfaces of the body of the diatom frustule flake. Using silver-plated diatom flakes in a silver ink can accelerate the curing of the silver ink and allow for the use of high aspect ratio flakes in the silver ink. In some embodiments, a silver ink comprising silver-plated diatom frustules can increase the conductivity of the cured silver ink and allow for reduced ink costs.

[0290] In some embodiments, portions of diatom frustules (e.g., broken diatom frustules) used in silver inks can be purified and separated from intact diatom particles, and one or more surfaces of the portions of diatom frustules can be electrolessly coated with silver, for example, according to the methods described herein.

[0291] The diatom surface, even when coated with silver, can be perforated with regular patterns of holes or openings (e.g., containing holes approximately 300 nm in diameter). The openings can be large enough to allow UV wavelengths to scatter through the silver-coated diatom particle. Broken silver-coated diatoms can comprise perforated flake-like fragments with high aspect ratios. Figure 5F shows an SEM image of a broken fragment of a diatom frustule (e.g., diatom frustule flake 60A) coated with Ag nanostructures (e.g., silver nanostructures 64).

[0292] In some embodiments, silver-coated, perforated diatom flakes can be used to make UV-curable silver inks for use in medium thickness inks (e.g., silver inks having thicknesses of about 5 μm to about 15 μm), even when the conductive particles have a high aspect ratio and therefore a large surface area. The large surface area of ​​the frustrating flakes creates excellent intra-flake conductivity by increasing the number of intra-flake electrical contacts, resulting in highly conductive inks that use substantially only as much silver as necessary to achieve the desired sheet conductivity, with the remaining volume being accounted for by inexpensive diatom filler and UV binder resin.

[0293] The silver nanostructures can cover substantially the entire surface of the frustule (including the inner surfaces of the frustule perforations), but do not block the perforations (e.g., one or more surfaces of the perforations and the frustule surface can be plated with silver nanostructures and / or a silver seed layer). The perforations in the Ag-coated diatom flakes can allow ultraviolet light to pass through the diatom flakes, promoting deep curing of the applied silver ink film, while allowing electrical current to travel directly from one side of the flake to the other through the perforations. Reducing the length of the conductive path through the flake can lower the overall resistance of the cured silver ink film.

[0294] An exemplary UV-induced polymerizable ink formulation includes the ingredients listed below: In some embodiments, a silver ink having diatom frustule flakes can be produced by combining the ingredients listed below, for example, combining a plurality of frustule portions (e.g., frustule flakes) having silver nanostructures formed on one or more surfaces thereof with one or more other silver ink ingredients listed below: A silver film can be produced by curing the silver ink with a UV light source.

[0295] 1) Frustules, any of a variety of types, plated with an Ag coating (e.g., with nanostructures formed thereon) between about 10 nm and about 500 nm thick. The thickness of the Ag coating can depend on the pore size of the diatom fenestration. The proportion in the composition can be between about 50% and about 80% by weight. An example of a diatom species from which fragments can be used is Aulacoseira sp. 1.

[0296] 2) Polar vinyl monomers with good affinity for silver, such as n-vinyl-pyrrolidone and n-vinylcaprolactam.

[0297] 3) Acrylate oligomers that act as rheology modifiers, offering excellent elongation properties and improving the flexibility of cured films.

[0298] 4) One or more di- or trifunctional acrylate monomers or oligomers as crosslinkers to increase crosslinking and thereby produce tough, solvent-resistant cured films. Such materials can be selected to function as photoinitiator synergists, which can improve surface cure. Examples include ethoxylated or propoxylated hexanediol, e.g., Sartomer CD560®, ethoxylated trimethylpropane triacrylate (e.g., available from Sartomer under the designation SR454®), and triallyl cyanurate (e.g., available from Sartomer under the designation SR507A®). Acrylate amine synergists are also an option, e.g., Sartomer CN371® and Sartomer CN373®.

[0299] 5) Acrylate-based flow and level agents to reduce bubbling and improve wet ink quality (e.g., suitable flow and level agents include Modaflow 2100®, Modaflow 9200®). Improving wet ink quality can improve the quality of the cured silver ink film.

[0300] 6) One or more photoinitiators suitable for dye-bearing ink systems. In some embodiments, at least one photoinitiator is sensitive to wavelengths near or below the average pore size of the silver-plated diatom flakes, allowing ultraviolet photons to pass through the pores and initiate polymerization below the flakes, and / or to scatter through perforations in other silver-plated diatom flakes and penetrate deeper into the uncured film, where they initiate polymerization. Examples of photoinitiators include Ciba Irgacure 907®, isopropyl thioxothanone (ITX, available from Lambson, UK, under the trade name Speedcure ITX®).

[0301] 7) An optional adhesion-promoting acrylate (e.g., 2-carboxyethyl acrylate).

[0302] 8) An optional wetting agent to reduce surface tension and improve flake wetting (e.g., DuPont Capstone FS-30®, DuPont Capstone FS-31®).

[0303] 9) An optional ultraviolet stabilizer (e.g., hydroquinone, methyl ethyl hydroquinone (MEHQ)) to inhibit premature polymerization caused by the presence of silver metal.

[0304] 10) Any low boiling point solvent that reduces viscosity to facilitate use of the silver ink composition in high speed coating processes (processes such as flexographic printing, gravure printing, and / or combinations thereof).

[0305] In some embodiments, the silver ink comprising diatom frustule portions is heat-curable. In some embodiments, the silver ink can be exposed to a heat source. For example, the silver ink can be heated to promote a polymerization reaction between polymer components of the silver ink. In some embodiments, heat-curing the silver ink can promote removal of the solvent component. For example, the silver ink can be exposed to a heat source to raise the temperature of the silver ink above the boiling point of the silver ink solvent component, promoting removal of the solvent component.

[0306] [An exemplary process for forming zinc oxide (ZnO) nanostructures on the surface of diatom frustules] Typically, ZnO seeds can be deposited on a substrate using spray or spin coating of colloidal ZnO or by thermal decomposition of zinc salt solutions. For example, thermal decomposition of a zinc acetate precursor can yield well-aligned vertical ZnO nanowires.

[0307] Growth of ZnO nanostructures from seeds can be achieved by hydrolysis of Zn salts in a basic solution. This process can be carried out at room temperature or at higher temperatures. Microwave heating can significantly accelerate the growth of nanostructures. Depending on the growth parameters, a variety of nanostructures have been observed (e.g., nanostructure morphology may depend on one or more growth conditions during the formation of nanostructures on the seed layer, such as growth temperature, heating pattern, inclusion of chemical additives during nanostructure growth, and / or a combination thereof). For example, chemical additives can be used to obtain nanostructures with desired morphologies. ZnO nanostructures can also be doped to control their semiconducting properties.

[0308] [An exemplary process for growing ZnO seeds on the surface of diatom frustules] 1. ZnO seed construction can be achieved by heating a mixture of 0.1 g of purified diatoms in ethanol and 10 mL of 0.005 M zinc acetate (Zn(CHCOO)) (e.g., zinc-contributing component) to about 200°C (e.g., from about 175°C to about 225°C) until dry. SEM images of ZnO-seeded frustule surfaces at 100kx magnification are shown in Figures 5G and 5H. Figures 5G and 5H show SEM images of ZnO-containing seeds 72 formed on the surface of frustules 70. Figure 5G shows an SEM image of a frustule surface with zinc oxide-containing seeds 72 at 100kx magnification. Figure 5H shows an SEM image of a frustule surface with zinc oxide-containing seeds 72 at 100kx magnification.

[0309] In some embodiments, the process of seeding the frustule surface with ZnO comprises forming a mixture having the following composition: 2 wt. % to approximately 5 wt. % frustules, approximately 0.1 wt. % to approximately 0.5 wt. % zinc salt (e.g., Zn(CHCOO)), and approximately 94.5 wt. % to approximately 97.9 wt. % alcohol (e.g., ethanol). In some embodiments, forming the ZnO seeds on the frustule surface comprises heating the mixture. The mixture may be heated to a desired temperature for a predetermined period of time to facilitate the formation of the ZnO seeds on the frustule surface and the removal of liquid from the mixture. Heating may be performed using any number of heating devices (such as a hot plate) capable of heating the mixture to a desired temperature for a desired period of time. In some embodiments, the mixture may be heated to a temperature greater than approximately 80° C. to facilitate the formation of ZnO seeds on the frustule surface and to dry the ZnO-sheeted frustules. In some embodiments, the heated mixture may be further heated in a vacuum oven to facilitate further removal of liquid. For example, the mixture may be heated in a vacuum oven at a pressure of about 1 mbar and at a temperature of about 50°C to about 100°C.

[0310] In some embodiments, the dried frustules may be subjected to an annealing process. In some embodiments, the annealing process may be configured to promote the desired formation of ZnO, for example, to promote the decomposition of zinc salts to form ZnO. In some embodiments, the conditions of the annealing process may be configured to achieve further drying of the frustules, for example, to evaporate any remaining liquid from the frustules. In some embodiments, the annealing process may comprise heating the dried frustules in an inert atmosphere at a temperature from about 200° C. to about 500° C. In some embodiments, the annealing process may include heating in an atmosphere including argon gas (Ar) and / or nitrogen gas (N).

[0311] [Exemplary process for growing ZnO nanostructures on the ZnO-sheeted surface of diatom frustules] 2. ZnO nanostructures can be grown on the ZnO seeds formed on the frustule surface as described herein. In some embodiments, growth of ZnO nanostructures can be carried out in a mixture of 0.1 g of sheeted frustules and 10 mL of 0.025 M ZnNO (e.g., zinc-donating component) and 0.025 M hexamethylenetetramine solution (e.g., basic solution) in water. The mixture can be heated on a stir plate to about 90°C (e.g., from about 80°C to about 100°C) for about two hours (e.g., from about one hour to about three hours), or a cyclic heating routine (e.g., microwave heating) for a duration of about 10 minutes (e.g., from about 5 minutes to about 30 minutes) can be used, where the sample is heated at a power of about 500 watts (e.g., from about 480 watts to about 520 watts) for about two minutes (e.g., from about 30 seconds to about 5 minutes, from about 1 minute to about 5 minutes, from about 5 minutes to about 20 minutes), then the heating is turned off for about one minute (e.g., from about 30 seconds to about 5 minutes), followed by a cycle of heating at 500 watts. Nanowires 74 on the inner and outer surfaces of frustule 70 resulting from the above process are shown in Figures 5I and 5J. 5I shows an SEM image at 50k magnification of ZnO nanowires 74 formed on both the interior and exterior surfaces of diatom frustules 70. In some embodiments, ZnO nanowires 74 may be formed on a portion of the interior surface of diatom frustules 70. For example, ZnO nanowires 74 may be formed on all or substantially all of the interior surface of diatom frustules 70. ZnO nanowires 74 may be formed on all or substantially all of the interior and exterior surfaces of diatom frustules 70. The figures herein demonstrate that it is possible to grow nanostructures (e.g., ZnO nanowires) on diatom frustules, including growing nanostructures (e.g., ZnO nanowires) within diatom frustules.Coating all or substantially all surfaces of a diatom frustule with ZnO nanowires can increase the electrical conductivity of a material (e.g., an ink or a layer printed thereon) comprising diatom frustules coated with ZnO nanostructures, compared to a material (e.g., an ink or a layer printed thereon) comprising ZnO nanostructures formed only on the outer surface of a substrate. Figure 5J shows an SEM image at 25kX magnification of ZnO nanowires 74 formed on the surface of a diatom frustule 70. Figures 5M and 5N are additional SEM images of a diatom frustule 70 having ZnO nanowires 74 on one or more surfaces. Figure 5M is an SEM image of a diatom frustule 70 at 10kX magnification. Figure 5N is an SEM image of a diatom frustule 70 at 100kX magnification. The polyhedral, polygonal cross-section, rod-like structure of ZnO nanowires 74 attached to the surface of the frustule 70 is clearly visible in Figure 5N. Microwave heating at 100 watts (e.g., from about 80 watts to about 120 watts, on for about 2 minutes, then off for about 1 minute, repeated for a total duration of about 10 minutes) can form nanoplates 76 on the surface of the frustule 70 (e.g., as shown in FIG. 5K).

[0312] In some embodiments, a process for forming ZnO nanostructures on one or more surfaces of ZnO-seeded frustules comprises forming a mixture having the following composition: about 1% to about 5% by weight of the sheeted frustules, about 6% to about 10% by weight of a zinc salt (e.g., Zn(NO3)2), about 1% to about 2% by weight of a base (e.g., ammonium hydroxide (NH4OH)), about 1% to about 5% by weight of an additive (e.g., hexamethylenetetramine (HMTA)), and about 79% to about 91% by weight of purified water. In some embodiments, forming the ZnO nanostructures comprises heating the mixture. The mixture can be heated using microwaves. For example, the mixture may be heated to a temperature of about 100°C to about 250°C for about 30 minutes (min) to about 60 minutes in a microwave device (e.g., in a Monowave 300 for small-scale synthesis of mixtures, such as about 10 mL to about 30 mL, or in a Masterwave BTR for large-scale synthesis, such as about 1 liter (L) of mixture, both of which are commercially available from Anton Paar®). In some embodiments, the mixture may be stirred while being heated in a microwave. For example, the mixture may be stirred at about 200 RPM (revolutions per minute) to about 1000 RPM using a magnetic stirrer while being heated. The use of microwave heating may advantageously facilitate a reduced heating period, providing a more efficient manufacturing process.

[0313] In some embodiments, the frustule having the ZnO nanostructures formed thereon comprises from about 5% to about 95% by weight (including from about 10% to about 95% by weight, from about 20% to about 95% by weight, from about 30% to about 95% by weight, from about 40% to about 95% by weight, from about 50% to about 95% by weight) ZnO, with the remainder being the frustule. In some embodiments, the frustule having the ZnO nanostructures formed thereon comprises from about 5% to about 95% by weight of the frustule, with the remainder being ZnO. In some embodiments, the frustule having the ZnO nanostructures formed thereon comprises from about 40% to about 50% by weight of the frustule, with the remainder being ZnO. In some embodiments, the frustule having the ZnO nanostructures formed thereon comprises from about 50% to about 60% by weight of the frustule, with the remainder being ZnO. The mass ratio of ZnO to frustule can be from about 1:20 to about 20:1 (including from about 1:15 to about 20:1, from about 1:10 to about 20:1, from about 1:1 to about 20:1, from about 2:1 to about 10:1, and from about 2:1 to about 9:1). Preferably, the ZnO nanostructures have a mass greater than the mass of the frustules prior to coating. In some embodiments, the mass ratio of ZnO nanostructures to frustules can be greater than about 1:1, about 10:1, or about 20:1. In certain such embodiments, the upper limit can be based, for example, on the openness of the pores of the frustules (e.g., the ZnO nanostructures not completely blocking the pores).

[0314] In some embodiments, the mass ratio of ZnO to the mass of the frustule can be from about 1:20 to about 100:1 (including from about 1:1 to about 100:1, from about 10:1 to about 100:1, from about 20:1 to about 100:1, from about 40:1 to about 100:1, from about 60:1 to about 100:1, and from about 80:1 to about 100:1). In some embodiments, the mass ratio of the ZnO nanostructure to the mass of the frustule can be greater than about 30:1, about 40:1, about 50:1, about 60:1, about 70:1, about 80:1, or about 90:1. In some embodiments, the mass ratio of the ZnO to the mass of the frustule can be selected to provide desired device performance.

[0315] In some embodiments, the pores of the frustule may be filled with nanostructures, for example, ZnO nanostructures may be formed on the surface of the frustule, including on surfaces within the pores of the frustule, such that the ZnO nanostructures may fill or substantially fill some or all of the pores of the frustule.

[0316] The mass of the ZnO nanostructures can be determined by weighing the frustules before and after coating and determining the difference as the mass of the ZnO nanostructures. In some embodiments, the composition of the mixture for forming the ZnO nanostructures can be determined so that the ZnO-coated frustules have a desired weight percent of ZnO. In some embodiments, the weight percent of ZnO on the frustule surface can be selected based on the desired mass of the surface active material on the counter energy storage device electrode. For example, the composition of the mixture for forming the ZnO nanostructures can be selected based on the mass of the manganese oxides (e.g., the mass of one or more of MnO, Mn2O3, Mn3O4, and MnOOH) in the counter energy storage electrode. For example, based on stoichiometric calculations, the mass of Mn2O3 in the energy storage device electrode can be at least 2.5 times the mass of ZnO in the counter electrode.

[0317] 5O, a 500x magnification SEM image of a plurality of frustules 70 having ZnO nanostructures formed thereon is shown. The ZnO nanostructure-covered frustules 70 were first seeded with ZnO using a mixture consisting essentially of about 2% to about 5% frustules by weight, about 0.1% to about 0.5% Zn(CHCOO)2 by weight, and about 94.5% to about 97.9% ethanol by weight. The mixture for forming the ZnO-seeded frustules was heated to a temperature greater than about 80°C for a duration sufficient to form the ZnO-seeded frustules and achieve the desired drying of the ZnO-seeded frustules. ZnO nanostructures were then formed on the ZnO-seeded frustules using a mixture consisting essentially of about 1 wt% to about 5 wt% ZnO-seeded frustules, about 6 wt% to about 10 wt% Zn(NO3)2, about 1 wt% to about 2 wt% ammonium hydroxide (NH4OH), about 1 wt% to about 5 wt% hexamethylenetetramine (HMTA), and about 78 wt% to about 91 wt% purified water. The mixture was heated to a temperature of about 100°C for about 30 to about 60 minutes using a microwave to promote the formation of ZnO nanostructures and drying of the frustules. As shown in FIG. 5O, the multiple frustules 70 on which the ZnO nanostructures were formed unexpectedly showed no or substantially no agglomeration. Each frustule was individually covered or substantially covered with ZnO nanostructures. Each of the frustules 70 having ZnO nanostructures formed thereon, shown in FIG. 5O, contained approximately 50% to approximately 60% ZnO by weight. FIG. 5P shows an SEM image at 5kX magnification of the frustules 70 having ZnO nanostructures formed thereon. The ZnO nanostructures on the frustules 70 in FIG. 5P were formed using the process described with reference to FIG. 5O. As shown in FIG. 5P, the frustules 70 are covered by ZnO nanoflakes 78. As shown in FIG. 5P, the frustules 70 having ZnO nanoflakes 78 formed thereon are porous. For example, the ZnO nanoflakes 78 do not block the pores of the frustules 70, advantageously facilitating electrolyte transport through an electrode comprising the frustules 70 having ZnO nanoflakes 78 formed thereon.

[0318] Examples of suitable Zn salts that can be used for ZnO seeding and nanostructure growth include zinc acetate hydrate, zinc nitrate hexahydrate, zinc chloride, zinc sulfide, sodium zincate, and / or combinations thereof.

[0319] Examples of suitable bases for growing ZnO nanostructures include sodium hydroxide, ammonium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, lithium hydroxide, hexamethylenetetramine, ammonia solution, sodium carbonate, ethylenediamine, and / or combinations thereof.

[0320] Examples of solvents suitable for the formation of ZnO nanostructures include one or more alcohols. Solvents described herein as suitable for Ag nanostructure growth may also be suitable for the formation of ZnO nanostructures.

[0321] Examples of additives that can be used to control the morphology of nanostructures include tributylamine, triethylamine, triethanolamine, diisopropylamine, ammonium phosphate, 1,6-hexadianol, triethyldiethynol, isopropylamine, cyclohexylamine, n-butylamine, ammonium chloride, hexamethylenetetramine, ethylene glycol, ethanolamine, polyvinyl alcohol, polyethylene glycol, sodium dodecyl sulfate, cetyltrimethylammonium bromide, carbamide, and / or combinations thereof.

[0322] [An exemplary process for forming carbon nanotubes on the surface of diatom frustules] Carbon nanotubes (e.g., multi-walled and / or single-walled) can be grown on diatom surfaces (e.g., inside and / or outside) by chemical vapor deposition (CVD) and its variations. In this method, the frustules are first coated with catalytic seeds, and then a gas mixture is introduced. One of the gases can be a reducing gas, and the other gas can be a carbon source. In some embodiments, a mixture of gases can be used. In some embodiments, a neutral gas can be included for concentration control (e.g., argon). Argon can also be used to carry liquid carbonaceous materials (e.g., ethanol). Seeds for carbon nanotube formation can be deposited as metals by methods such as spray coating and / or introduced from liquid, gas, and / or solid forms and subsequently reduced by pyrolysis at high temperatures. Reduction of the carbonaceous gas can occur at high temperatures, for example, in the range of about 600°C to about 1100°C.

[0323] Both seed coating processes and gas reactions can be achieved on the frustule surface due to its nanoporosity. Methods have been developed to grow carbon nanotube "forests" on a variety of substrates (silicon, alumina, magnesium oxide, quartz, graphite, silicon carbide, zeolites, metals, silica, etc.).

[0324] Examples of metal compounds suitable for catalyst seed growth include nickel, iron, cobalt, cobalt-molybdenum bimetallic particles, copper (Cu), gold (Au), Ag, platinum (Pt), palladium (Pd), manganese (Mn), aluminum (Al), magnesium (Mg), chromium (Cr), antimony (Sb), aluminum-iron-molybdenum (Al / Fe / Mo), iron pentacarbonyl (Fe(CO)5), iron(III) nitrate hexahydrate (Fe(NO3)3·6H2O), CoCl2·6H2O, and ammonium molybdate tetrahydrate ((NH4)6Mo7O). 24 ·4H2O), MoO2Cl2, alumina nanopowder, and / or combinations thereof.

[0325] Examples of suitable reducing gases include ammonia, nitrogen, hydrogen, and / or combinations thereof.

[0326] Examples of suitable gases (eg, carbonaceous gases) that can serve as a carbon source include acetylene, ethylene, ethanol, methane, carbon oxides, benzene, and / or combinations thereof.

[0327] [Exemplary Process for Forming Manganese-Containing Nanostructures on the Surface of Diatom Frustules] In some embodiments, manganese-containing nanostructures can be formed on one or more surfaces of the frustule. In some embodiments, oxides of manganese can be formed on one or more surfaces of the frustule. In some embodiments, oxides of manganese can be formed on one or more surfaces of the frustule. x O y Nanostructures comprising an oxide of manganese, such as manganese dioxide (MnO), manganese(II,III) oxide (MnO), manganese(II) oxide (MnO), and / or manganese(III) oxide (MnO), can be formed on one or more surfaces of the frustules. In some embodiments, nanostructures comprising manganese oxyhydroxide (MnOOH) can be formed on one or more surfaces of the frustules. In some embodiments, a membrane of an energy storage device can include a frustule having manganese-containing nanostructures. In some embodiments, a printed energy storage device (e.g., a battery, capacitor, supercapacitor, and / or fuel cell) can include one or more electrodes having a plurality of frustules comprising manganese-containing nanostructures. In some embodiments, an ink for printing a film can include a solution in which frustules comprising manganese-containing nanostructures are dispersed.

[0328] In some embodiments, one or more electrodes of the battery can include a shell comprising manganese-containing nanostructures on one or more surfaces (e.g., an electrode in a zinc-manganese battery). A charged battery can include a first electrode including a shell comprising nanostructures comprising manganese dioxide (MnO) and a second electrode comprising zinc (e.g., a shell comprising a zinc coating). In some embodiments, the second electrode can comprise other materials. A discharged battery can include a first electrode including a shell comprising nanostructures comprising manganese(II,III) oxide (MnO), manganese(II) oxide (MnO), manganese(III) oxide (MnO), and / or manganese oxyhydroxide (MnOOH), and a second electrode comprising zinc oxide (ZnO) (e.g., a shell comprising nanostructures comprising zinc oxide). In some embodiments, the second electrode of a discharged battery can comprise other materials. In some embodiments, the charged battery can include a first electrode having a frustule of manganese(II,III) oxide (MnO), manganese(II) oxide (MnO), manganese(III) oxide (MnO), and / or manganese oxyhydroxide (MnOOH) formed thereon, and a second counter electrode having a ZnO structure formed thereon. In some embodiments, the battery can be a rechargeable battery.

[0329] A method for forming manganese-containing nanostructures on diatom frustule portions can include adding the frustules to an oxidized manganese acetate solution and heating the frustules and the oxidized manganese acetate solution. An example of a process for forming MnO on one or more surfaces of the frustules is provided. For example, pure water (e.g., commercially available from EMD Millipore, Inc., Billerica, Massachusetts) can be bubbled with oxygen gas (O) for a duration of approximately 10 minutes (min) to approximately 60 minutes (e.g., O purging) to form oxygenated water. Manganese(II) acetate (Mn(CHCOO)) can then be dissolved in the oxygenated water at a concentration of approximately 0.05 moles per liter (M) to approximately 1.2 M to form an oxidized manganese acetate solution.

[0330] The frustules can be added to the oxidized manganese acetate solution. The frustules added to the oxidized manganese acetate solution may not have nanostructures and / or coatings pre-formed on the frustule surface. In some embodiments, the frustules added to the oxidized manganese acetate solution may have one or more nanostructures and / or coatings on the frustule surface. In some embodiments, the frustules added to the oxidized manganese acetate solution may have one or more nanostructures and / or coatings on at least a portion of the frustule surface. For example, the frustules may have carbon-containing nanostructures on a portion of the frustule surface, such that manganese-containing nanostructures formed according to one or more processes described herein are dispersed among the carbon-containing nanostructures. In some embodiments, the carbon-containing nanostructures may include reduced graphene oxide, carbon nanotubes (e.g., single-walled and / or multi-walled), and / or carbon nano-onions. Carbon-containing nanostructures may be formed on the frustule surface according to one or more processes described herein or other processes.

[0331] In some embodiments, frustules may be added to the oxidized manganese acetate solution so that the solution comprises about 0.01% to about 1% frustules by weight. 2+ Salts may be suitable. In some embodiments, other oxidizing agents (e.g., peroxides) may be suitable.

[0332] In some embodiments, growth of manganese-containing nanostructures can be performed using thermal and / or microwave techniques. In some embodiments, the desired growth of nanostructures can involve longer durations when using thermal methods. For example, thermal methods can include thermal heating during the nanostructure growth process. An example of a thermal method for growing nanostructures involves mixing (e.g., stirring using any number of suitable techniques) frustules in an oxidized manganese acetate solution for a duration of about 15 to about 40 hours (e.g., 24 hours) while maintaining the mixture at a temperature of about 50 degrees Celsius (°C) to about 90°C (e.g., about 60°C). In some embodiments, the temperature of the mixture can be maintained by thermally heating the mixture.

[0333] In some embodiments, microwave methods of growing nanostructures may facilitate shorter nanostructure growth processes and / or facilitate scalable nanostructure growth processes. For example, microwave methods of nanostructure growth may include using microwave heating in the nanostructure growth process. One example of a nanostructure growth process using microwave techniques may include adding frustules to an oxidized manganese acetate solution and maintaining the mixture at a temperature of about 50° C. to about 150° C. for about 10 minutes to about 120 minutes. The mixture may be stirred while maintained at the temperature.

[0334] In some embodiments, manganese-containing structures having a reddish-brown color (e.g., after washing and drying) can be formed on one or more surfaces of the frustules using one or more processes described herein. In some embodiments, the manganese oxide structures can have a tetrahedral shape. The reddish-brown color can be indicative of the presence of manganese(II,III) oxide (Mn3O4). In some embodiments, the formation of tetrahedral nanocrystals can be indicative of the presence of manganese(II,III) oxide (Mn3O4).

[0335] FIG. 5Q is a scanning electron microscope (SEM) image at 20kx magnification of an example of a frustule 80 having a nanostructure 82 comprising manganese(II,III) oxide (Mn3O4) on its surface, the nanostructure 82 being formed using a microwave method of nanostructure growth. FIG. 5R is an SEM image at 50kx magnification of the frustule 80 shown in FIG. 5Q. The nanostructure 82 comprising manganese(II,III) oxide (Mn3O4) shown in FIGS. 5Q and 5R can be formed using an oxidizing solution having a manganese acetate concentration of approximately 0.15 M prepared by bubbling oxygen gas (O2) through purified water for a duration of approximately 30 minutes. For example, commercially available oxygen gas (e.g., greater than 95% purity, e.g., greater than approximately 97% purity, greater than approximately 99% purity, etc.) can be used. For example, oxygen gas having a purity of 97% or greater can be bubbled through a glass frit into a vial (e.g., a vial with a volume of approximately 20 milliliters (mL)) containing approximately 15 mL of purified water at room temperature (e.g., approximately 25°C) for a duration of approximately 30 minutes. A weight of 0.55 grams (g) of manganese acetate tetrahydrate (e.g., commercially available from Sigma-Aldrich) can be dissolved in peroxide-containing purified water. A weight of 0.005 grams (g) of frustules can be added to the manganese oxide-containing solution. The solution containing the mixture with added frustules can then be placed in a microwave heater (e.g., a Monowave 300 microwave heater manufactured by Anton Paar) and synthesis can be carried out at a desired temperature for a desired period of time. The mixture comprising the solution and frustules can be maintained at a temperature of approximately 60°C for approximately 30 minutes and, for example, continuously stirred (e.g., with a magnetic stir bar, at a rotation speed of, for example, approximately 600 rpm). In some embodiments, the mixture may then be diluted with water and centrifuged (e.g., at about 5000 rpm for about 5 minutes), and the supernatant may be discarded. In some embodiments, the precipitate may be diluted again with water, then dispersed (shaken and / or vortexed), and centrifuged again, and the supernatant may be discarded. The sediment may then be dried in a vacuum oven at about 70°C to about 80°C.

[0336] 5R, the nanostructures 82 can have a tetrahedral shape. Surprisingly, manganese(II,III) oxide (MnO) was observed to grow on the surface of the frustules rather than growing in solution away from the frustules.

[0337] Figure 5S is a transmission electron microscope (TEM) image of nanostructures 82 formed on the surface of the frustules shown in Figures 5Q and 5R. One or more individual atoms of the nanostructures 82 are visible, and a scale is provided for size comparison. Figure 5T shows an electron diffraction pattern of manganese(II,III) oxide (Mn3O4) particles.

[0338] In some embodiments, the shape and / or dimensions of the nanostructures formed on the frustule surface may depend on the parameters of the nanostructure formation process. For example, the morphology of the nanostructures may depend on the solution concentration and / or oxidation level of the solution. Figure 5U is an SEM image at 10kx magnification of a frustule 90 having manganese-containing nanostructures 92 formed on its surface, which were formed using a solution with a higher oxygen concentration (e.g., oxygen purging of water for a duration of approximately 40 minutes) and a higher manganese concentration (e.g., a manganese acetate concentration of approximately 1 M) compared to the process used to form the nanostructures 82 shown in Figures 5Q and 5R. For example, nanostructures 92 may be formed on frustule 90 according to a process similar to that described for forming nanostructures 82, with the following differences: oxygen gas may be bubbled through purified water for a duration of approximately 40 minutes, approximately 0.9 grams (g) of manganese acetate may be added to the oxygenated purified water, approximately 0.01 grams (g) of diatoms may be added to the manganese-containing solution, and the mixture comprising the diatoms and manganese-containing solution may be microwaved at a temperature of approximately 150°C.

[0339] As shown in Figure 5U, nanostructures 92 may have an elongated fibrous shape. In some embodiments, nanostructures 92 may have a thin, elongated shape (thin whisker-like structures). In some embodiments, the formation of fibrous structures may indicate the presence of manganese oxyhydroxide (MnOOH).

[0340] In some embodiments, one or more surfaces of the frustule may have a chemical formula Mn x O y Forming nanostructures comprising one or more oxides of manganese having a manganese content of about 1 to about 3, where x is from about 1 to about 3, and y is from about 1 to about 4, can include combining the frustules with a manganese source (such as a manganese salt, e.g., manganese acetate (Mn(CH3COO)2)) and a base (e.g., ammonium hydroxide (NH4OH)) in oxygenated water. In some embodiments, forming nanostructures comprising one or more oxides of manganese having a manganese content of about 1 to about 3, where x is from about 1 to about 3, and y is from about 1 to about 4 can include combining the frustules with a manganese source (such as a manganese salt, e.g., manganese acetate (Mn(CH3COO)2)) and a base (e.g., ammonium hydroxide (NH4OH)) in oxygenated water. In some embodiments, forming a nanostructure comprising one or more oxides of manganese having a manganese content of about 1 to about 4, where x is from about 1 to about 3, and y is from about 1 to about 4, can include combining the frustules with a manganese source (such as a manganese salt, e.g., manganese acetate (Mn(CH3COO)2)) and a base (e.g., ammonium hydroxide (NH4OH)) in oxygenated water. x O y Forming the nanostructures can include forming a mixture having the following composition: about 0.5% to about 2% frustules by weight, about 7% to about 10% Mn(CH3COO)2 by weight, about 5% to about 10% NH4OH by weight, and about 78% to about 87.5% pure oxygenated water by weight. In some embodiments, the pure oxygenated water for the mixture can be prepared by bubbling oxygen through pure water for about 10 to about 30 minutes. Heating the mixture using a microwave to form the Mn x O y The formation of nanostructures can be facilitated (e.g., in a Monowave 300 for small-scale synthesis of mixtures, such as about 10 mL to about 30 mL, or in a Masterwave BTR for large-scale synthesis, such as about 1 liter (L) of mixture, both of which are commercially available from Anton Paar®). For example, the mixture can be heated to a temperature of about 100° C. to about 250° C. for about 30 to about 60 minutes using a microwave. In some embodiments, the mixture can be stirred while being heated, for example, by a magnetic stirrer at about 200 RPM (revolutions per minute) to about 1000 RPM.

[0341] In some embodiments, oxides of manganese (e.g., having the chemical formula Mn x O yThe frustule on which the nanostructures (e.g., oxide of manganese, where x is from about 1 to about 3 and y is from about 1 to about 4) are formed comprises from about 5% to about 95% by weight (including from about 30% to about 95% by weight, from about 40% to about 95% by weight, from about 30% to about 85% by weight, from about 50% to about 85% by weight, from about 55% to about 95% by weight, and from about 75% to about 95% by weight) of an oxide of manganese, with the remainder being the frustule. In some embodiments, an oxide of manganese (e.g., having the chemical formula Mn x O y The frustules on which the nanostructures of an oxide of manganese (where x is from about 1 to about 3 and y is from about 1 to about 4) are formed comprise from about 5% to about 50% by weight of the frustule, with the remainder being the oxide of manganese nanostructures. In some embodiments, the ratio of the mass of the manganese oxide nanostructures to the mass of the frustules can be from about 1:20 to about 20:1 (including from about 1:15 to about 20:1, from about 1:10 to about 20:1, from about 1:1 to about 20:1, from about 5:1 to about 20:1, from about 1:1 to about 10:1, and from about 2:1 to about 9:1). The manganese oxide nanostructures preferably have a mass greater than the mass of the frustules prior to coating. In some embodiments, the ratio of the mass of the manganese oxide to the mass of the frustules can be greater than about 1:1, about 10:1, or about 20:1. In certain such embodiments, the upper limit may be based, for example, on the openness of the pores of the frustule (eg, the manganese oxide nanostructures not completely blocking the pores).

[0342] In some embodiments, the pores of the frustule may be filled by nanostructures, for example, manganese oxide nanostructures may be formed on the surface of the frustule, including the surface of the interior pores of the frustule, and the manganese oxide nanostructures may fill or substantially fill some or all of the pores of the frustule.

[0343] In some embodiments, the mass of the manganese oxide nanostructure to the mass of the frustule is from about 1:20 to about 100:1 (including from about 1:1 to about 100:1, from about 10:1 to about 100:1, from about 20:1 to about 100:1, from about 40:1 to about 100:1, from about 60:1 to about 100:1, and from about 80:1 to about 100:1). In some embodiments, the mass of the manganese nanostructure to the mass of the frustule can be greater than about 30:1, about 40:1, about 50:1, about 60:1, about 70:1, about 80:1, or about 90:1. In some embodiments, the mass of the manganese nanostructure to the mass of the frustule can be selected to provide desired device performance.

[0344] The mass of the manganese oxide nanostructures can be determined by weighing the frustules before and after coating and taking the difference as the mass of the manganese oxide nanostructures. In some embodiments, the composition of the mixture for forming the manganese oxide nanostructures can be selected to form a desired weight percent of manganese oxide. In some embodiments, the weight percent of manganese oxide on the frustule surface can be selected based on the desired mass of the surface active material on the counter energy storage device electrode. For example, the composition of the mixture for forming the manganese oxide nanostructures can be selected based on the mass of ZnO in the counter energy storage device electrode. In some embodiments, based on stoichiometric calculations, the mass of MnO in the energy storage device electrode can be at least 2.5 times the mass of ZnO in the counter electrode.

[0345] FIG. 5V is an SEM image at 20k magnification of the manganese oxide nanostructure frustule 94 on which the nanostructure 96 is formed. The nanostructure 96 contains a mixture of various manganese oxides, which have the formula Mn x O y where x is from about 1 to about 3 and y is from about 1 to about 4. As shown in FIG. 5V, the frustule 94 is thickly covered by a manganese oxide nanostructure 96. FIG. 5W shows the manganese oxide nanostructure 96 (e.g., having the chemical formula Mn x O y5A and 5B are SEM images at 50kx magnification of a cross-section of a frustule 94 having an oxide of manganese (e.g., an oxide of manganese having the formula Mn), where x is from about 1 to about 3 and y is from about 1 to about 4, formed thereon. The frustule 94 was cut using a focused ion beam (FIB), and a cross-section of the cut frustule 94 is shown in FIG. 5W. As shown in FIG. 5W, manganese oxide nanostructures 96 can be formed on the interior and exterior surfaces of the frustule 94, and the volume of the nanostructures 96 can be larger than the volume of the frustule 94. FIG. 5X shows a manganese oxide nanostructure 96 (e.g., an oxide of manganese having the formula Mn x O y 5X is an SEM image at 100k magnification of a sidewall of a frustule 94 having manganese oxide nanostructures 96 formed thereon, where x is from about 1 to about 3 and y is from about 1 to about 4. As shown in FIG. 5X, the sidewall of the frustule 94 can be covered with manganese oxide nanostructures 96 without blocking the pores on the sidewall. A frustule having manganese oxide nanostructures formed thereon without blocking or substantially blocking the pores of the frustule can advantageously facilitate electrolyte transport through an electrode comprising a frustule covered with manganese oxide nanostructures.

[0346] The frustule 94 having manganese oxide nanostructures 96 formed thereon, shown in Figures 5V-5X, was formed using a mixture consisting essentially of about 0.5 wt% to about 2 wt% frustule, about 7 wt% to about 10 wt% Mn(CH3COO)2, about 5 wt% to about 10 wt% NH4OH, and about 78 wt% to about 87.5 wt% pure water peroxide. The mixture was heated using a microwave to a temperature between about 100°C and about 250°C for about 30 to about 60 minutes. As shown in Figures 5V-5X, the frustule 94 was thickly covered with manganese oxide nanostructures 96. For example, a frustule covered with about 75 wt% to about 95 wt% manganese oxide nanostructures would be nanostructures, with the remainder being the mass of the frustule.

[0347] [Coating combination] In some embodiments, combinations of coatings are possible, for example, the surface of a frustule may include both a nickel coating and a carbon nanotube coating (e.g., such a frustule may be used in an energy storage device such as a supercapacitor).

[0348] FIG. 6 schematically illustrates an exemplary embodiment of an energy storage device 100. FIG. 6 may be a cross-sectional or elevational view of the energy storage device 100. The energy storage device 100 includes a first electrode 140 and a second electrode 150, which may be, for example, a cathode and an anode, respectively, or may not be so related. The first electrode 140 and the second electrode 150 are separated by a separator 130. The energy storage device 100 optionally includes one or more current collectors 110, 120, which are electrically connected to one or both of the electrodes 140, 150.

[0349] In some embodiments, the energy storage device 100 comprises a first electrode 140, a second electrode 150, and / or a separator, any of which may be a film or layer (including a deposited film or layer).

[0350] The current collectors 110, 120 may include any component that provides a path for electrons to external wiring. For example, the current collectors 110, 120 may be disposed adjacent to the surfaces of the first electrode 140 and the second electrode 150, respectively, to allow the flow of energy between the electrodes 140, 150 to conduct to an electrical device. In the embodiment shown in Figure 6, the first current collector layer 110 and the second current collector layer 120 are adjacent to the surfaces of the first electrode 140 and the second electrode 150, respectively. The current collectors 110, 120 are adjacent to the surfaces of the electrodes 140, 150 opposite the surfaces adjacent to the separator layer 130.

[0351] In some embodiments, the current collectors 110, 120 comprise a conductive foil (e.g., graphite (e.g., graphite paper), graphene (e.g., graphene paper), aluminum (Al), copper (Cu), stainless steel (SS), carbon foam). In some embodiments, the current collectors 110, 120 comprise a conductive material deposited on a substrate. For example, the current collectors 110, 120 may comprise a conductive material printed on a substrate. In some embodiments, suitable substrates include polyester, polyimide, polycarbonate, cellulose (e.g., cardboard, paper (e.g., coated paper, e.g., plastic-coated paper, and / or fiber paper)). In some embodiments, the conductive material may comprise silver (Ag), copper (Cu), carbon (C) (e.g., carbon nanotubes, graphene, and / or graphite), aluminum (Al), nickel (Ni), and / or combinations thereof. Examples of nickel-containing conductive materials suitable for current collectors are provided in International Application No. PCT / US2013 / 078059 (entitled "NICKEL INKS AND OXIDATION RESISTANT AND CONDUCTIVE COATINGS," filed December 27, 2013), the entire contents of which are incorporated herein by reference.

[0352] In some embodiments, the energy storage device 100 includes at least one layer or film comprising a frustule. For example, the energy storage device 100 can include a layer or film comprising a dispersion comprising a frustule. The layer or film comprising a frustule can include, for example, the first electrode 140, the second electrode 150, the separator 130, the first current collector layer 110, the second current collector layer 120, and / or combinations thereof. In some embodiments, the energy storage device 100 includes a frustule having a uniform or substantially uniform shape, dimension (e.g., diameter, length), material, porosity, surface modification material and / or structure, other suitable characteristics or properties, and / or combinations thereof. In embodiments in which multiple layers of the energy storage device 100 include a frustule, the frustules can be the same or substantially the same (e.g., have similar dimensions) or different (e.g., insulating for the separator 130 and conductive for the electrodes 140, 150).

[0353] The energy storage device 100 may include one or more layers or films comprising a frustule having a length in the range of about 0.5 μm to about 50 μm, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 1 μm to about 10 μm, about 5 μm to about 50 μm, about 5 μm to about 40 μm, about 5 μm to about 30 μm, about 5 μm to about 20 μm, or about 5 μm to about 10 μm. In some embodiments, the cylindrical frustule has a length of about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, about 15 μm or less, about 10 μm or less, or about 5 μm or less. Other frustule lengths are possible.

[0354] The energy storage device 100 may include one or more layers or films comprising a frustule having a diameter in the range of about 0.5 μm to about 50 μm, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 1 μm to about 10 μm, about 5 μm to about 50 μm, about 5 μm to about 40 μm, about 5 μm to about 30 μm, about 5 μm to about 20 μm, or about 5 μm to about 10 μm. In some embodiments, the cylindrical frustule has a diameter of about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, about 15 μm or less, about 10 μm or less, about 5 μm or less, about 2 μm or less, or about 1 μm or less. Other frustule diameters are possible.

[0355] The energy storage device 100 may include a frustule having uniform or substantially uniform intra- and / or inter-frustum porosity and / or a frustule having a porosity within a particular range. In some embodiments, the energy storage device 100 includes one or more layers or films including a frustule having a porosity within a range of about 10% to about 50%, about 15% to about 45%, or about 20% to about 40%. In some embodiments, the pores in the frustule surface may have a size (e.g., length, width, diameter, and / or longest dimension) of about 1 nanometer (nm) to about 500 nm. For example, the pores in the frustule surface may have a size that can facilitate desired energy storage device performance (e.g., diffusion of electrolyte ions in the energy storage device to facilitate desired electrical performance of the device). Other frustule porosities are possible.

[0356] As described herein, the energy storage device 100 may include one or more layers or films including a frustule 50 that is free or substantially free of surface-modifying materials and / or structures 52 applied or formed on the surface of the frustule, and / or a frustule that has materials and / or structures 52 applied or formed on the surface of the frustule to modify a property or characteristic of the frustule 50. For example, the separator 130 may include a frustule 50 that is free or substantially free of surface-modifying materials and / or structures 52 applied or formed on the surface of the frustule 50, and one or more electrodes 140, 150 may include a frustule 50 that has materials and / or structures 52 applied or formed on the surface of the frustule to modify a property or characteristic of the frustule. As another example, the separator 130 may include some frustrums 50 that are free or substantially free of surface-modifying substances and / or surface-modifying structures 52 applied or formed on the surface of the frustrums 50, and some frustrums 50 that include substances and / or structures 52 applied or formed on the surface of the frustrums 50 to modify the properties or characteristics of the frustrums 50.

[0357] In some embodiments, the energy storage device 100 comprises a frustule having a non-uniform or substantially non-uniform shape, size, porosity, surface modification material and / or structure, other suitable characteristics, and / or combinations thereof.

[0358] In some embodiments, one or more layers or films of the energy storage device 100 may be printed. In some embodiments, one or more layers or films of the energy storage device 100 may be printed from an ink. In some embodiments, the ink may be printed using a variety of methods described herein, such as stencil printing, screen printing, rotary printing, die coating, rotogravure printing, flexographic and pad printing, and / or combinations thereof. In some embodiments, the viscosity of the ink may be adjusted based on the printing method being applied (e.g., the desired viscosity may be achieved by adjusting the quality of the solvent used in the ink).

[0359] In some embodiments, the current collector may be printed using a conductive ink. For example, the current collector may comprise a conductive material printed on a substrate. In some embodiments, suitable substrates include polyester, polyimide, polycarbonate, cellulose (e.g., cardboard, paper (coated paper, e.g., plastic-coated paper, and / or fiber paper)). In some embodiments, the conductive ink may comprise aluminum, silver, copper, nickel, bismuth, conductive carbon, carbon nanotubes, graphene, graphite, and / or combinations thereof, etc. The conductive material may comprise silver (Ag), copper (Cu), carbon (C) (e.g., carbon nanotubes, graphene, and / or graphite), aluminum (Al), nickel (Ni), and / or combinations thereof, etc. Examples of nickel-containing conductive materials suitable for current collectors are provided in International Application No. PCT / US2013 / 078059 (entitled "NICKEL INKS AND OXIDATION RESISTANT AND CONDUCTIVE COATINGS," filed December 27, 2013), the entire contents of which are incorporated herein by reference.

[0360] In some embodiments, an ink may be prepared with multiple frustules. An ink with frustules may be printed to form components of an energy storage device, such as an electrode or separator of an energy storage device. In some embodiments, an ink may have frustules with nanostructures formed thereon (including one or more nanostructures described herein). For example, an ink with frustules covered with nanostructures may be printed to form an electrode of an energy storage device 100. In some embodiments, an ink may have frustules that are free or substantially free of nanostructures formed thereon. For example, an ink with frustules that are free or substantially free of surface modifications may be printed to print a separator 130 of an energy storage device 100.

[0361] 7A-7E are schematic diagrams illustrating cross-sectional views of example energy storage devices. In some embodiments, the energy storage devices of FIGS. 7A-7E are printed energy storage devices. For example, the energy storage devices of FIGS. 7A-7E may include a first current collector 110, a second current collector 120, a first electrode 140, a second electrode 150, and a separator 130, all of which are printed. For example, one or more layers of the printed energy storage devices of FIGS. 7A-7C may be printed on separate substrates, and the separate substrates may then be assembled together to form the energy storage device, while the layers of the energy storage devices of FIGS. 7D and 7E may be printed on a single substrate.

[0362] In some embodiments, Figures 7A-7C are schematic diagrams showing cross-sections of example partial printed energy storage devices, while Figures 7D and 7E are schematic diagrams showing cross-sections of complete printed energy storage devices at various stages of the manufacturing process. The energy storage devices shown in Figures 7A-7C can include current collectors 110, 120, which can be printed (e.g., printed on a separate substrate) and / or non-printed (e.g., serving as a substrate on which other layers are printed). Figures 7D and 7E show cross-sectional views of energy storage devices including current collectors 110, 120, which can be printed (e.g., each printed on a single substrate) or non-printed (e.g., the first current collector 110 of Figure 7D serves as a substrate on which other layers are printed, and the first current collector 110 and second current collector 120 of Figure 7E together serve as substrates on which other layers are printed).

[0363] In some embodiments, the first current collector 110, the second current collector 120, the first electrode 140, the second electrode 150, and / or the separator 130 of FIGS. 7A-7E can have one or more properties as described herein and / or can be manufactured as described herein. For example, the first current collector 110, the second current collector 120, the first electrode 140, the second electrode 150, and / or the separator 130 can be printed using one or more methods and / or ink compositions as described herein. For example, one of the electrodes 140, 150 can be printed using an oxide of manganese (e.g., with the chemical formula Mn x O y where x is from about 1 to about 3 and y is from about 1 to about 4), and the other of electrodes 140, 150 may have a shell including nanostructures comprising zinc (e.g., ZnO), one or both of which may be printed from ink. As another example, separator 130 may have a shell with no or substantially no surface modification, and the shell may be printed from ink. As described herein, non-printed current collectors may comprise conductive foils, such as aluminum, copper, nickel, stainless steel, graphite (e.g., graphite paper), graphene (e.g., graphene paper), carbon nanotubes, carbon foam, and / or combinations thereof. In some embodiments, the conductive foil may be laminated and may have a polymer layer on one of its two sides.

[0364] 7A , energy storage device 200 includes a first structure 202 and a second structure 204. First structure 202 includes a first electrode 140 on a first current collector 110 and a separator 130 on the first electrode 140. Second structure 204 includes a second electrode 150 on a second current collector 120. In some embodiments, first electrode 140 may be printed on first current collector 110. For example, separator 130 may be printed on and in direct contact with first electrode 140. In some embodiments, separator 130 may be printed on first electrode 140 such that separator 130 and first current collector 110 encapsulate or substantially encapsulate first electrode 140. In some embodiments, second electrode 150 may be printed on second electrode 120, for example, in direct contact with second electrode 120. In some embodiments, a process for manufacturing energy storage device 200 may include assembling first structure 202 and second structure 204 together. For example, fabrication of the energy storage device 200 shown in FIG. 7A may include contacting the second electrode 205 of the second structure 204 with the separator 130 of the first structure 202 such that the separator 130 is between the first electrode 140 and the second electrode 150.

[0365] 7B shows an energy storage device 210 comprising a first structure 212 comprising a first electrode 140 on a first current collector 110 and a first portion of a separator on the first electrode 140. The energy storage device 210 may comprise a second structure 214 comprising a second electrode 150 on a second current collector 120 and a second portion of a separator 130 on the second electrode 150. In some embodiments, the second electrode may be printed on the second current collector 120. For example, the second electrode 150 may be printed on and in direct contact with the second current collector 120. In some embodiments, the second portion of the separator 130 may be printed on the second electrode 150. For example, the second portion of the separator 130 may be printed on and in direct contact with the second electrode 150. In some embodiments, the first electrode 140 may be printed on the first current collector 140. For example, the first electrode 140 may be printed on and in direct contact with the first current collector 110. In some embodiments, the first portion of the separator 130 may be printed on the first electrode 140. For example, the first portion of the separator 130 may be printed on and in direct contact with the first electrode 140. In some embodiments, the first and second portions of the separator 130 may be printed such that the first portion of the separator 130 and the first current collector 110 encapsulate or substantially encapsulate the first electrode 140, and / or the second portion of the separator 130 and the second current collector 120 encapsulate or substantially encapsulate the second electrode 150. In some embodiments, a process for manufacturing the energy storage device 210 may include assembling the first structure 212 and the second structure 214 together to form the energy storage device 210. Assembling the first structure 212 and the second structure 214 may comprise providing the first and second portions of the separator 130 between the first electrode 140 and the second electrode 150. For example, fabrication of the energy storage device 210 shown in FIG. 7B may include contacting a second portion of the separator 130 of the second structure 214 with a first portion of the separator 130 of the first structure 212 such that the two portions of the separator 130 are between the first electrode 140 and the second electrode 150.

[0366] As shown in FIG. 7C , in some embodiments, an energy storage device 220 may include a first structure 222 including a first electrode 140 on a first current collector 110, a separator 130 on the first electrode 140, and a second electrode on the separator 130. The energy storage device 220 may include a second structure 224 including a second current collector 120. In some embodiments, the first electrode 140 may be printed on the first current collector 110. For example, the first electrode 140 may be printed on and in direct contact with the first current collector 110. In some embodiments, the separator 130 may be printed on and in direct contact with the first electrode 140. In some embodiments, the separator 130 may be printed on and in direct contact with the first electrode 140 such that the separator 130 and the first current collector 110 encapsulate or substantially encapsulate the first electrode. In some embodiments, the second electrode 150 may be printed on and in contact with the separator 140. For example, the second electrode 150 may be printed directly on and in contact with the separator 130. In some embodiments, assembling the energy storage device 220 includes bonding the first structure 222 and the second structure 224 to form the energy storage device 220. In some embodiments, bonding the first structure 222 and the second structure 224 may include contacting the second current collector 120 to the second electrode 150 such that the second electrode 150 is between the second current collector 140 and the separator 130.

[0367] As described herein, Figures 7D and 7E are schematic diagrams of a complete printed energy storage device. Figure 7D shows an example of a vertically stacked energy storage device 230 comprising printed current collectors 110, 120, electrodes 140, 150, and a separator 130. Referring to Figure 7D, in some embodiments, the first current collector 110 of the energy storage device 230 may be printed on a substrate. In some embodiments, the first electrode 140 may be printed on top of the first current collector 110. For example, the first electrode 140 may be printed on top of and in direct contact with the first current collector 110. In some embodiments, the separator 130 may be printed on top of the first electrode 140. For example, the separator 130 may be printed on top of and in direct contact with the first electrode 140. In some embodiments, the second electrode 150 may be printed on top of the separator 130. For example, the second electrode 150 may be printed on top of and in direct contact with the separator 130. In some embodiments, the second current collector 120 may then be printed on top of the second electrode 150. For example, the second current collector 120 may be printed on top of and in direct contact with the second electrode 150. In some embodiments, the second current collector 120 may be printed on top of the second electrode 150 such that the second current collector 120 and separator 130 encapsulate or substantially encapsulate the second electrode 150. In some embodiments, the separator 130 may be printed on the first electrode 140 such that the separator 130 and first current collector 110 encapsulate or substantially encapsulate the first electrode 140.

[0368] Referring to FIG. 7E, an energy storage device 240 having laterally spaced electrodes 140, 150 is shown. The energy storage device 240 may include a first current collector 110 laterally spaced from a second current collector 120, a first electrode 140 on the first current collector 110, and a second electrode 150 on the second current collector 120. A separator 130 may be present on the first electrode 140 and the second electrode 150. For example, the separator 130 may be formed between the first electrode 140 and the second electrode 150 such that the electrodes 140, 150 are electrically isolated from each other. In some embodiments, the separator 130 promotes electrical isolation between the first current collector 110 and the second current collector 120. In some embodiments, each of the first current collector 110, the second current collector 120, the first electrode 140, the second electrode 150, and the separator 130 may be printed. For example, the first current collector 110 and the second current collector 120 may be printed on the substrate. In some embodiments, the first electrode 140 may be printed on the first current collector 110. For example, the first electrode 140 may be printed on top of and in direct contact with the first current collector 110. In some embodiments, the second electrode 150 may be printed on top of the second current collector 120. For example, the second electrode 150 may be printed on top of and in direct contact with the second current collector 120. In some embodiments, the separator 130 may be printed on top of the first electrode 140 and the second electrode 150, for example, in direct contact with both the first electrode 140 and the second electrode 150. In some embodiments, the separator 130 is printed on top of the first electrode 140 and the second electrode 150 such that the separator 130, the first current collector 110, and the second current collector 120 may encapsulate or substantially encapsulate the first electrode 140 and the second electrode 150. In some embodiments, first and second structures similar to first and second structures 202 and 204 of FIG. 7A (e.g., comprising current collectors, electrodes, and optionally separators) can be formed with different electrode active materials (e.g., one or more oxides of manganese, ZnO) and then laterally bonded together.

[0369] FIG. 8 illustrates an exemplary embodiment of a separator layer or film 300 that may form part of an energy storage device (e.g., the separator 130 of any of the energy storage devices described with respect to FIGS. 6 and 7A-7E). The separator 300 includes a frustule 320. In some embodiments, the energy storage device includes the separator layer or film 300 including the frustule 320. For example, the energy storage device may include the separator 300 including a dispersion including the frustule 320. As described herein, the frustule 320 may be classified according to shape, size, material, porosity, and / or combinations thereof, and the separator 300 may include a frustule 320 having a uniform or substantially uniform shape, size (e.g., length, diameter), porosity, material, and / or combinations thereof. For example, the separator 300 may include a frustule 320 having a cylindrical or substantially cylindrical shape (e.g., as shown in FIG. 8), a spherical or substantially spherical shape, other shapes, and / or combinations thereof. In some embodiments, separator 300 includes a frustule 320 having a substance and / or structure applied or formed on the surface of the frustule 320. Separator 300 may include a frustule 320 that is free or substantially free of a surface-modifying substance and / or structure applied or formed on the surface of the frustule 320 (e.g., as shown in FIG. 8). Separator 300 may include a frustule 320 that is free or substantially free of a surface-modifying substance and / or structure applied or formed on the surface of the frustule 320 to modify the properties or characteristics of the frustule 320. Separator 300 may include some frustules 320 that are free or substantially free of a surface-modifying substance and / or structure applied or formed on the surface of the frustule, and ... 320 to modify the properties or characteristics of the frustule 320.

[0370] The separator 300 may comprise a frustule 320 having sufficient mechanical strength to enable stable or substantially stable separation between the first electrode 140 and the second electrode 150 of an energy storage device (e.g., the first electrode 140 and the second electrode 150 of any of FIGS. 6 and 7A-7E). In some embodiments, the separator 300 comprises a frustule 320 configured to increase the efficiency of the energy storage device, for example, by reducing the spacing between the first electrode 140 and the second electrode 150 and / or by facilitating the flow of ionic species between the first electrode 140 and the second electrode 150. For example, the frustule 320 may have a uniform or substantially uniform shape, size, porosity, surface modification material and / or structure, and / or combinations thereof, etc., to improve the efficiency and / or strength of the energy storage device. The separator 300 for an energy storage device may comprise a cylindrical or substantially cylindrical frustule including a wall having a desired porosity, size, and / or surface modification material and / or structure.

[0371] Separator 300 may include one or more layers of furring shell 320. Separator 300 with furring shell 320 may have a uniform or substantially uniform thickness. In some embodiments, separator 300 with furring shell 320 has as thin a thickness as possible. In some embodiments, the thickness of the separator 300 including the substrate 320 is from about 1 μm to about 100 μm, e.g., from about 1 μm to about 80 μm, from about 1 μm to about 60 μm, from about 1 μm to about 40 μm, from about 1 μm to about 20 μm, from about 1 μm to about 10 μm, from about 5 μm to about 60 μm, from about 5 μm to about 40 μm, from about 5 μm to about 20 μm, from about 5 μm to about 15 μm, from about 5 μm to about 10 μm, from about 10 μm to about 60 μm, from about 10 μm to about 40 μm, from about 10 μm to about 20 μm, from about 10 μm to about 15 μm, from about 15 μm to about 30 μm, etc. In some embodiments, the separator has a thickness of less than about 100 μm, less than about 90 μm, less than about 80 μm, less than about 70 μm, less than about 60 μm, less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 20 μm, less than about 15 μm, less than about 10 μm, less than about 5 μm, less than about 2 μm, or less than about 1 μm (including the boundaries and ranges therebetween of the above values). Other thicknesses of the separator 300 are also possible. For example, the separator 300 may comprise a single layer of frustule 320, such that the thickness of the separator 300 may depend at least in part on the dimensions (e.g., longest axis, length, diameter) of the frustule 320.

[0372] Separator 300 may include a frustule 320 having a non-uniform or substantially non-uniform shape, size, porosity, surface modification material and / or structure, and / or combinations thereof.

[0373] In some embodiments, the frustule may include hollow and / or solid microspheres made of a non-conductive material. For example, separator 300 may include hollow and / or solid microspheres made of glass, alumina, silica, polystyrene, melamine, and / or combinations thereof. In some embodiments, the microspheres may have a size that facilitates printing of separator 300. For example, separator 300 may include microspheres having diameters from approximately 0.1 micrometers (μm) to approximately 50 μm. Examples of separators comprising hollow and / or solid microspheres are provided in U.S. Patent Application No. 13 / 223,279, entitled "PRINTABLE IONIC GEL SEPARATION LAYER FOR ENERGY STORAGE DEVICES," filed August 9, 2012, which is incorporated herein by reference in its entirety.

[0374] In some embodiments, separator 300 comprises a material configured to reduce electrical resistance between first electrode 140 and second electrode 150 of the energy storage device. For example, referring to FIG. 8 , in some embodiments, separator 300 comprises electrolyte 340. Electrolyte 340 can include any material that promotes the conductivity of ionic species, such as a material that provides mobile ionic species that can travel between first electrode 140 and second electrode 150 of the energy storage device. Electrolyte 340 can comprise any compound capable of forming ionic species, including, but not limited to, sodium sulfate (NaSO), lithium chloride (LiCl), and / or potassium sulfate (KSO). In some embodiments, electrolyte 340 comprises an acid, a base, or a salt. In some embodiments, the electrolyte 340 is a strong acid (e.g., including but not limited to, sulfuric acid (HSO) and / or phosphoric acid (HPO)) or a strong base (e.g., including but not limited to, sodium hydroxide (NaOH) and / or potassium hydroxide (KOH)). In some embodiments, the electrolyte 340 comprises a solvent having one or more dissolved ionic species. For example, the electrolyte 340 may comprise an organic solvent. In some embodiments, the electrolyte 340 comprises an ionic liquid or an organic liquid salt. The electrolyte 340 may comprise an aqueous solution with an ionic liquid. The electrolyte 340 may comprise a salt solution with an ionic liquid. In some embodiments, the electrolyte 340 comprises an ionic liquid including propylene glycol and / or acetonitrile. In some embodiments, the electrolyte 340 comprising an ionic liquid includes an acid or a base. For example, the electrolyte 340 may comprise an ionic liquid mixed with potassium hydroxide (e.g., adding a 0.1 M solution of KOH).

[0375] In some embodiments, the electrolyte may include one or more ionic liquids and / or one or more salts as described in U.S. Patent Application No. 14 / 249,316, entitled "PRINTED ENERGY STORAGE DEVICE," filed April 9, 2014, which is incorporated herein by reference in its entirety.

[0376] In some embodiments, separator 300 comprises polymer 360, e.g., a polymer gel. Polymer 360 can be mixed with electrolyte 340. A suitable polymer 360 can exhibit electrical and electrochemical stability during electrochemical reactions and / or application of an electrical potential (e.g., an electrical potential between electrodes 140 and 150 of an energy storage device), e.g., maintaining integrity and / or functionality when mixed with electrolyte 350. In some embodiments, polymer 360 can be an inorganic polymer. In some embodiments, polymer 360 can be a synthetic polymer. Separator 300 may include a polymer 360 including, for example, cellulose (e.g., cellophane), polyamide (e.g., nylon), polypropylene, polyolefin, polyethylene (e.g., radiation-grafted polyethylene), polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polyvinyl alcohol, polymethyl methacrylate, polyvinyl chloride, poly(bis(methoxyethoxyethoxy)phosphazene), polyvinyl sulfonate, polyvinyl pyrrolidone, polypropylene oxide, copolymers thereof, and / or combinations thereof. In some embodiments, polymer 360 comprises polytetrafluoroethylene (PTFE), such as an aqueous solution comprising an aqueous dispersion of PTFE (e.g., Teflon® aqueous suspension). In some embodiments, separator 300 may include asbestos, potassium titanate fiber, fibrous sausage casing, borosilicate glass, zirconium oxide, and / or combinations thereof. In some embodiments, the electrolyte 340 is immobilized in or on the polymer 360 to form a solid or semi-solid material. In some embodiments, the electrolyte 340 is immobilized on or on the polymer 360 to form, for example, an electrolyte gel.

[0377] In some embodiments, separator 300 optionally comprises an adhesive material to improve adhesion of frustule 320 within separator 300 and / or between separator 300 and first electrode 140 and / or second electrode 150 of the energy storage device. In some embodiments, adhesive material comprises polymer 360. For example, the adhesive material provides sufficient adhesion within separator 300 and / or between separator 300 and first electrode 140 and / or second electrode 150 of the energy storage device.

[0378] In some embodiments, the ink for printing the separator of the energy storage device comprises a plurality of frustules, a polymer, an ionic liquid, an electrolyte salt, and / or a solvent, with or without or substantially without surface modification. Examples of suitable solvents are provided in U.S. Patent Application No. 14 / 249,316, entitled "PRINTED ENERGY STORAGE DEVICE," filed April 9, 2014, which is incorporated herein by reference in its entirety. In some embodiments, the solvent for the ink used to print the separator may comprise dimethyl formamide (DMF), dimethyl acetamide (DMAC), tetramethyl urea, dimethyl sulfoxide (DMSO), triethyl phosphate, n-methyl-2-pyrrolidone (NMP), and / or combinations thereof. In some embodiments, the ink for printing the separator has the following composition: about 5% to about 20% by weight of a frustule without surface modification (e.g., purified frustule), about 3% to about 10% by weight of a polymer component (e.g., polyvinylidene fluoride, e.g., Kynar® ADX, available from Arkema, Inc., King of Prussia, Pennsylvania), about 15% to about 40% by weight of an ionic liquid (e.g., 1-ethyl-3-ethylimidazolium tetrafluoroborate), about 1% to about 5% by weight of a salt (e.g., zinc tetrafluoroborate), and about 25% to about 76% by weight of a solvent (e.g., N-methyl-2-pyrrolidone). In some embodiments, other polymers, ionic liquids, salts (e.g., other zinc salts), and / or solvents may also be suitable.

[0379] In some embodiments, a process for preparing a separator ink can include dissolving a binder in a solvent. For example, dissolving the binder in a solvent can include heating a mixture comprising the binder and solvent at a temperature of from about 80° C. to about 180° C. for about 5 minutes to about 30 minutes. In some embodiments, heating can be performed using a hot plate. In some embodiments, the ionic liquid and electrolyte salt can be added to the mixture, for example, after heating while the mixture is warm. The binder, solvent, ionic liquid, and electrolyte salt can be stirred, for example, for about 5 minutes to about 10 minutes, to promote the desired mixing. In some embodiments, the frustules can then be added. The addition of the frustules can be promoted by mixing, for example, by using a planetary stirrer. Mixing can be performed using a planetary stirrer for about 1 minute to about 15 minutes.

[0380] FIG. 9 illustrates an exemplary electrode layer or film 400 that may form part of an energy storage device (e.g., any of the energy storage devices described with reference to FIGS. 6 and 7A-7E). The electrode 400 includes a frustule 420. Some embodiments include one or more electrode layers or films 400 comprising a frustule 420 (e.g., the first electrode 140 and / or the second electrode 150 of any of the energy storage devices described with reference to FIGS. 6 and 7A-7E). For example, an energy storage device may include an electrode layer or film 400 comprising a dispersion including a frustule 420. As described herein, frustules 420 may be classified according to shape, size, material, porosity, and / or combinations thereof, and the electrode 400 may include a frustule 420 having a uniform or substantially uniform shape, size (e.g., length, diameter), porosity, material, and / or combinations thereof. For example, electrode 400 may include a frustule 420 having a cylindrical or substantially cylindrical shape (e.g., as shown in FIG. 9 ), a spherical or substantially spherical shape, other shapes, and / or combinations thereof. In some embodiments, electrode 400 includes a frustule 420 having a substance and / or structure applied or formed on the surface of frustule 420. Electrode 400 may include a frustule 420 that is free or substantially free of surface-modifying substances and / or structures applied or formed on the surface of frustule 420, may be insulating, and / or may include a frustule 420 that includes a substance and / or structure applied or formed on the surface of frustule 420 to modify a property or characteristic of frustule 420 (e.g., as shown schematically in FIG. 9 by chicken-foot-like features on the surface of frustule 420). The electrode 400 may include some frustules 420 that are free or substantially free of surface-modifying substances and / or surface-modifying structures applied or formed on the surface of the frustules 420, and some frustules 420 that include substances and / or structures applied or formed on the surface of the frustules 420 to modify the properties or characteristics of the frustules 420.

[0381] The electrode 400 may include a frustule 420 selected for mechanical strength that enables an energy storage device including the electrode 400 to withstand compressive forces and / or deformation. In some embodiments, the electrode 400 includes a frustule 420 configured to increase the efficiency of the energy storage device, for example, by promoting the flow of ionic species within the electrode 400 and / or between the electrode 400 and other portions of the energy storage device. For example, the frustule 420 may have a uniform or substantially uniform shape, size, porosity, surface modification material and / or structure, and / or combinations thereof, etc., to improve the efficiency and / or strength of the energy storage device. The electrode 400 of an energy storage device may include a cylindrical or substantially cylindrical frustule 420 including a wall with a desired porosity, size, and / or surface modification material and / or structure.

[0382] The electrode 400 may comprise one or more layers of frustule 420. The electrode 400 with frustule 420 may have a uniform or substantially uniform thickness. In some embodiments, the thickness of the electrode 400 with frustule 420 may depend at least in part on resistivity, amount of material available, desired energy device thickness, etc. In some embodiments, the thickness of the electrode 420 comprising the substrate 420 is from about 1 μm to about 100 μm, e.g., from about 1 μm to about 80 μm, from about 1 μm to about 60 μm, from about 1 μm to about 40 μm, from about 1 μm to about 20 μm, from about 1 μm to about 10 μm, from about 5 μm to about 60 μm, from about 5 μm to about 40 μm, from about 5 μm to about 20 μm, from about 5 μm to about 15 μm, from about 5 μm to about 10 μm, from about 10 μm to about 60 μm, from about 10 μm to about 40 μm, from about 10 μm to about 20 μm, from about 10 μm to about 15 μm, from about 15 μm to about 30 μm, etc. In some embodiments, the thickness of electrode 400 including frustule 420 is less than about 100 μm, less than about 90 μm, less than about 80 μm, less than about 70 μm, less than about 60 μm, less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 20 μm, less than about 15 μm, less than about 10 μm, less than about 5 μm, less than about 2 μm, or less than about 1 μm (including the boundaries and ranges therebetween). Other thicknesses of electrode 400 are possible.

[0383] The electrode 400 may comprise a frustule 420 having a non-uniform or substantially non-uniform shape, size, porosity, surface modification material and / or structure, and / or combinations thereof, and the like.

[0384] In some embodiments, electrode 400 optionally comprises a material that improves the conductivity of electrons within electrode 400. For example, referring again to FIG. 9 , in some embodiments, electrode 400 comprises a conductive filler 460 that improves the conductivity of electrode 400. Conductive filler 460 may comprise a conductive carbon material. For example, conductive filler 460 may comprise graphitic carbon, graphene, carbon nanotubes (e.g., single-walled and / or multi-walled), and / or combinations thereof, etc. In some embodiments, conductive filler 460 may include a metallic material (e.g., silver (Ag), gold (Au), copper (Cu), nickel (Ni), and / or platinum (Pt)). In some embodiments, conductive filler 460 may include a semiconductor material (e.g., silicon (Si), germanium (Ge), and / or a semiconductor-containing alloy (e.g., an aluminum silicon (AlSi) alloy)). In energy storage device 100 including multiple electrodes 400, electrodes 400 may include different frustules and / or different additives, e.g., different ionic and / or ion-generating species. In some embodiments, electrode 400 may include an electrolyte, e.g., electrolyte 340 described with respect to separator 300 in FIG. 8. In some embodiments, an electrode may include one or more active materials (e.g., free active material, e.g., active material separate from the nanostructured active material on one or more surfaces of diatom frustules).

[0385] In some embodiments, the electrode 400 can include a binder. The binder can comprise a polymer. Suitable polymers, polymer precursors, and / or polymerizable precursors for electrode binders include, for example, polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and the like. alcohol), polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, polytetrafluoroethylene, polydimethylsiloxane, polyethylene, polypropylene, polyethylene oxide, polypropylene oxide, polyethylene glycol hexafluoropropylene, polyethylene terephthalate polyacrylonitrile, polyvinyl butyral, polyvinyl caprolactam, polyvinyl chloride, polyimide polymers and copolymers (e.g., aliphatic, aromatic, and / or semi-aromatic polyimides), polyamide, polyacrylamide, acrylate and methacrylate polymers and copolymers, e.g., polymethyl methacrylate, polyacrylonitrile, acrylonitrile butadiene styrene, allyl methacrylate, polystyrene, polybutadiene, polybutylene terephthalate, polycarbonate , polychloroprene, polyethersulfone, nylon, styrene-acrylonitrile resin, polyethylene glycol, clays such as hectorite clay, garamite clay, organically modified clays, saccharides and polysaccharides such as guar gum, xanthan gum, starch, butyl rubber, agarose, pectin, cellulose and modified celluloses such as hydroxymethylcellulose, methylcellulose, ethylcellulose, propylmethylcellulose, methoxycellulose, methoxymethylcellulose, methoxypropylmethylcellulose, hydroxypropylmethylcellulose, carboxymethylcellulose, hydroxyethylcellulose, ethylhydroxyethylcellulose, cellulose ethers, cellulose ethyl ether, chitosan, copolymers thereof, and / or combinations thereof.

[0386] In some embodiments, electrode 400 may include a corrosion inhibitor and / or one or more other functional additives. In some embodiments, the corrosion inhibitor may include one or more surface-active organic compounds. In some embodiments, the corrosion inhibitor may comprise glycols, silicates, mercury (Hg), cadmium (Cd), lead (Pb), gallium (Ga), indium (In), antimony (Sb), bismuth (Bi), and / or combinations thereof, etc.

[0387] In some embodiments, electrode 400 optionally comprises an adhesive material that can improve adhesion of frustule 420 within electrode 400 and / or between electrode 400 and other components of the energy storage device (such as separator 130 and / or current collectors 110, 120). In some embodiments, the adhesive material of electrode 400 comprises a polymer, such as polymer 360 described herein.

[0388] In some embodiments, an ink for printing an electrode of an energy storage device may comprise a plurality of frustules having nanostructures formed on one or more surfaces, a conductive filler (e.g., carbon nanotubes, graphite), a binder component, an electrolyte (e.g., an ionic liquid, an electrolyte salt), and / or a solvent. For example, the electrolyte may comprise a composition described herein. In some embodiments, one or more solvents described for the separator ink may also be suitable as an ink for printing an electrode. In some embodiments, a solvent for the ink used to print the electrode may comprise dimethylformamide (DMF), dimethylacetamide (DMAC), tetramethylurea, dimethylsulfoxide (DMSO), triethyl phosphate, n-methyl-2-pyrrolidone (NMP), and / or combinations thereof. In some embodiments, an ink for printing an electrode may comprise a frustule having ZnO nanostructures formed on one or more surfaces. In some embodiments, an ink for printing an electrode may comprise a frustule having ZnO nanostructures formed on one or more surfaces.

[0389] In some embodiments, an ink for printing an energy storage electrode comprising an oxide of manganese can have the following composition: about 10% to about 20% by weight of a frustule having one or more surfaces covered by an oxide of manganese, about 0.2% to about 2% by weight of carbon nanotubes (e.g., multi-walled carbon nanotubes, such as those commercially available from Southwest Nanotechnologies of Norman, Oklahoma), up to 10% by weight of graphite (e.g., C65, commercially available from Timcal Graphite and Carbon of Switzerland), about 1% to about 5% by weight of a binder (e.g., polyvinylidene fluoride, such as HSV 900 Kynar®, commercially available from Arkema, Inc. of King of Prussia, Pennsylvania), about 2% to about 15% by weight of an ionic liquid (e.g., 1-ethyl-3-ethylimidazolium tetrafluoroborate), and about 48% to about 86.8% by weight of a solvent (e.g., N-methyl-2-pyrrolidone). In some embodiments, the oxide of manganese has the formula Mn x O y where x is from about 1 to about 3 and y is from about 1 to about 4. For example, the ink may be printed to form a cathode for a battery.

[0390] In some embodiments, an ink for printing an energy storage electrode comprising ZnO may have the following composition: about 10 wt % to about 20 wt % ZnO formed thereon, about 0.2 wt % to about 2 wt % carbon nanotubes (e.g., multi-walled carbon nanotubes, e.g., commercially available from Southwest Nanotechnologies, Norman, Oklahoma), up to 10 wt % graphite (e.g., C65, commercially available from Timcal Graphite and Carbon, Switzerland), about 1 wt % to about 5 wt % binder (e.g., polyvinylidene fluoride, e.g., HSV 900 Kynar®, commercially available from Arkema, Inc., King of Prussia, Pennsylvania), about 2 wt % to about 15 wt % ionic liquid (e.g., 1-ethyl-3-ethylimidazolium tetrafluoroborate), about 0.3 wt % to about 1 wt % electrolyte salt (e.g., zinc tetrafluoroborate), and about 48 wt % to about 86.8 wt % solvent (e.g., N-methyl-2-pyrrolidone). For example, the ink may be printed to print the anode of a battery.

[0391] In some embodiments, the carbon nanotubes may comprise multi-walled and / or single-walled carbon nanotubes. In some embodiments, other types of graphite, polymer binders, ionic liquids, and / or solvents may also be suitable.

[0392] In some embodiments, the process for preparing the ink for printing the electrodes can be configured to provide a desired dispersion of carbon nanotubes in the ink, saturate the frustules with the ionic liquid (e.g., provide the interior, inner surface, outer surface, and / or pores of the frustules with the ionic liquid), and / or thoroughly mix the components of the ink. In some embodiments, the process for preparing the ink comprises dispersing the carbon nanotubes in the ionic liquid. In some embodiments, the carbon nanotubes can be dispersed in the ionic liquid using an automated mortar and pestle. In some embodiments, the carbon nanotubes and the ionic liquid can then be dispersed in a solvent. An ultrasonic tip can be used to disperse the carbon nanotubes and the ionic liquid in the solvent. In some embodiments, the frustules having nanostructures formed thereon (e.g., manganese oxide or ZnO nanostructures) and graphite can be added to the carbon nanotubes, ionic liquid, and solvent and stirred using a centrifugal mixer. In some embodiments, the electrolyte salt along with the frustules and graphite can be added to the carbon nanotubes, ionic liquid, and solvent and stirred using a centrifugal mixer. For example, the frustules, graphite, carbon nanotubes, ionic liquid, solvent, and / or electrolyte salt may be mixed using a planetary mixer for about 1 minute to about 10 minutes. In some embodiments, a solution comprising a polymer binder in a solvent may be added to a mixture comprising the frustules, graphite, carbon nanotubes, ionic liquid, solvent, and / or electrolyte salt and heated. The solution comprising the polymer binder and solvent may have about 10% to about 20% polymer binder by weight. The mixture comprising the polymer binder, frustules, graphite, carbon nanotubes, ionic liquid, solvent, and / or electrolyte salt may be heated to a temperature of about 80° C. to about 180° C. In some embodiments, heating may be performed for about 10 minutes to about 30 minutes. In some embodiments, heating may be performed using a hot plate. In some embodiments, heating may be performed while stirring (e.g., using a mixing rod).

[0393] 10-13 show oxides of manganese (e.g., those having the chemical formula Mn) produced using the processes described herein. x O yFigure 10 shows the electrical performance of an example printed battery comprising a cathode of MnxOy (where x is from about 1 to about 3, and y is from about 1 to about 4) and a ZnO anode. Figure 10 is a discharge curve graph of a printed MnxOy and ZnO battery, where the cathode included multiple frustules of manganese oxide nanostructures formed thereon and the anode included multiple frustules of ZnO formed thereon. The battery potential in volts (V) is shown on the y-axis, and the discharge duration in hours (hr) is shown on the x-axis. The battery was screen-printed in a 1.27 centimeter (cm) x 1.27 cm square (i.e., a 0.5 inch (in) x 0.5 inch square). The battery included a printed current collector, anode, cathode, and separator. The anode and cathode each had an average thickness of approximately 40 micrometers (μm). The cathode had a total weight of approximately 0.023 grams (g), and the manganese oxide weight was approximately 0.01 g. The weight of the active material ZnO in the anode was in excess.

[0394] In Figure 10, the battery was discharged from a fully or substantially fully charged state to a cutoff voltage of approximately 0.8 V. The battery was discharged at approximately 0.01 amperes per gram (A / g). The battery exhibited a capacity of approximately 1.28 milliampere-hours (mAh) and a capacity of 128 milliampere-hours per gram (mAh / g) based on the weight of the cathode active material. Figure 11 shows the capacitance performance of the printed battery of Figure 10 after multiple charge-discharge cycles. The battery underwent 40 cycles, with the capacitance performance for each cycle shown on the axis as a percentage of the initial capacitance. As shown in Figure 11, the capacitance can be improved after multiple charge-discharge cycles.

[0395] Figure 12 shows charge-discharge curves for another example of a printed MnxOy and ZnO battery, showing the potential performance for each charge-discharge cycle as a function of time during three charge-discharge cycles. Potential is shown on the y-axis in volts (V), and time is shown on the x-axis in hours (hr). The printed batteries were screen-printed in squares approximately 1.27 centimeters (cm) × 1.27 cm (i.e., 0.5 inches (in) × 0.5 inches). The battery's cathode included multiple frustules with manganese oxide nanostructures formed thereon, and the anode included multiple frustules with ZnO nanostructures formed thereon. The battery included a printed current collector, anode, cathode, and separator. The anode and cathode each had an average thickness of approximately 40 micrometers (μm). The cathode had a total weight of approximately 0.021 grams (g), and the manganese oxide weight was approximately 0.01 g. The active material (e.g., ZnO) in the anode was in excess by weight. The printed cell of FIG. 12 was charged and discharged at approximately 0.01 amperes per gram (A / g) based on the weight of the active material in the cathode. x O y The charge / discharge curves of the printed Mn and ZnO batteries were obtained at approximately 0.04 A / g. The two sets of curves show excellent reproducibility for both charge and discharge. x O y This indicates that the ZnO / ZnO battery can be an efficient rechargeable battery.

[0396] [Supercapacitor with surface-modified diatoms] The foregoing describes energy storage devices that offer a variety of advantages due to diatom frustules. Below, we provide a detailed description of a particular type of energy storage device, referred to herein and in related industries as a supercapacitor. Supercapacitors, also known as ultracapacitors, electric double-layer capacitors (EDLCs), and electrochemical capacitors, are relatively new energy storage devices that share some advantageous characteristics with conventional electrostatic capacitors and other characteristics with conventional batteries, e.g., secondary batteries.

[0397] Similar to certain batteries, supercapacitors have a cathode or positive electrode and an anode or negative electrode separated by a porous separator and electrolyte. For example, the separator may comprise an ion-permeable dielectric material impregnated with the electrolyte. Ion transport, which occurs from one electrode to the other as part of the electrochemical reaction during charging and discharging of a battery, does not occur in supercapacitors.

[0398] Supercapacitors are similar in some aspects to conventional electrostatic capacitors, for example, they have a relatively fast charging capability while having a much higher capacitance compared to conventional electrostatic capacitors. Unlike conventional electrostatic capacitors, which store energy in electrodes separated by a dielectric, supercapacitors store energy at one or both of the interfaces between the cathode and electrolyte and the anode and electrolyte.

[0399] The capacitance value of a supercapacitor can be much higher than that of a conventional electrostatic capacitor. Some supercapacitors have a lower voltage limit compared to conventional electrostatic capacitors. For example, some supercapacitors are limited to operating at approximately 2.5-2.8 V. Some supercapacitors can operate at voltages above 2.8 V. Certain such supercapacitors may exhibit a shorter lifespan.

[0400] Supercapacitors can transport charge much faster than batteries, and therefore generally have a much higher power density than batteries. Supercapacitors generally have much lower internal resistance than batteries, and as a result, do not generate as much heat during rapid charging and discharging. Some supercapacitors can be charged and discharged millions of times, while many secondary batteries can have significantly shorter life cycles, typically 500 to 10,000 times. Some supercapacitors have significantly lower energy densities than batteries. Some commercially available supercapacitors are more expensive (higher cost per watt) than commercially available batteries.

[0401] These and other properties allow supercapacitors to be used in applications where rapid charge / discharge cycles may be required rather than long-term energy storage. For example, applications for large units of supercapacitors include automobiles, buses, trains, cranes, elevators, etc., where they are used for regenerative braking, short-term energy storage, and burst-mode power supply. Applications for small units of supercapacitors include memory backup for static random access memory (SRAM). Other current and future applications for supercapacitors include electrical appliances such as cell phones, laptops, electric vehicles, and a variety of other devices that use batteries. Supercapacitors can be charged much faster than batteries, making them particularly attractive for devices that can benefit from fast charging speeds, e.g., minutes instead of the hours that current electric vehicles and cell phones can take to charge.

[0402] In some devices, supercapacitors are used in conjunction with batteries to take advantage of the advantageous properties of both. In these applications, supercapacitors are used when fast charging is needed to meet short-term power needs, while batteries are used to provide long-term energy. Combining the two into a hybrid energy storage device can meet both needs while reducing stress on the battery, potentially enabling a longer battery and supercapacitor lifespan.

[0403] Because the capacitance of a supercapacitor is directly proportional to the effective surface area of ​​the electrode, it is desirable for the electrode of the supercapacitor to have a relatively large effective surface area. A relatively large effective surface area can be achieved by utilizing an electrode material with a high surface-to-volume ratio. As described above, the frustules, due to their nanoporous structure, can advantageously provide a very large effective surface area and serve as a substrate on which the surface active material of the supercapacitor is formed. As described herein with respect to supercapacitors, the surface active material refers to the portion of the electrode that forms an interface with the electrolyte and generates capacitance resulting from at least one supercapacitance mechanism, e.g., electric double layer capacitance and / or pseudocapacitance, as described in more detail below. Additionally or alternatively, nanostructures (e.g., nanoparticles and nanotubes) can provide a very large surface area for a given volume of surface active material, for example, compared to a thin film formed from the same material. As used herein with respect to supercapacitors, nanostructures refer to solids having at least one axial dimension that is submicron, e.g., less than about 1000 nm, 500 nm, 200 nm, 100 nm, or within a range defined by these values.

[0404] The nanostructures can have any of the shapes described above, including, for example, nanowires, nanosheets, nanotubes, nanoplates, nanoparticles, nanobelts, nanodisks, and rosette-shaped nanostructures. Additionally, the nanostructures can have any three-dimensional geometric shape, such as spheres, cylinders, cones, spheroids, ellipsoids, tetrahedrons, pyramidal shapes, prisms, cubes, rectangular prisms, plates, disks, rods, and the like. In some embodiments, the nanostructures can be selected to have a specific shape based on the crystalline structure of the nanostructures. As described above, the inventors have discovered the inventive method of modifying the surface of the frustules with various surface-active materials. The inventors have recognized that the synergistic effect of the extremely large effective surface area of ​​the frustules and the extremely high surface-to-volume ratio of the nanostructured surface-active materials can lead to supercapacitors with higher power and energy densities than existing supercapacitors. The present inventors have realized a supercapacitor that benefits from the synergistic effect of the frustule and the nanostructured surface active material, for example, by modifying the surface of the frustule with a nanostructured surface active material having a high surface-to-volume ratio.

[0405] According to various embodiments, a supercapacitor comprises a pair of electrodes in contact with an electrolyte. In some embodiments, the electrodes may be interposed between an electrolyte and may further comprise a separator (e.g., impregnated with the electrolyte). In various embodiments, one or both electrodes comprise a plurality of frustules and a surface active material. The surface active material contacts the electrolyte to provide one or more supercapacitance mechanisms described below. In some embodiments, each frustule has a surface active material formed thereon. The surface active material is nanostructured to take advantage of the large surface area of ​​the frustules and / or the high surface-to-volume ratio of the surface active material, thereby providing improved supercapacitance performance, including high power density and / or energy density. For example, the surface active material may be in the form of a plurality of nanostructures covering the surface of the frustules. The nanostructures may include one or more of zinc oxide nanostructures, manganese oxide nanostructures, and carbon nanostructures. The performance of the supercapacitors of the present disclosure benefits from the synergistic effect of the large surface area provided by the nanoporous nature of the diatom frustule structure and the high surface-to-volume ratio of the surface active material. Because the surface active material, e.g., nanostructures, are grown on the diatom frustules and are not aggregated, a relatively large portion of the surface area is accessible to the electrolyte. Because the diatom frustules are nanoporous, the electrolyte has direct access to the nanostructures and can easily migrate throughout the device. The supercapacitors of the present disclosure can be advantageously fabricated using scalable techniques, such as printing. The fabricated supercapacitors can be used as small devices, e.g., in printed electronics, and / or can be fabricated in large sizes and folded into shapes for powerful applications.

[0406] Without being bound by theory, supercapacitors can store energy through a variety of mechanisms, such as electric double-layer capacitance and / or pseudocapacitance. Double-layer capacitance has electrostatic properties, while pseudocapacitance has electrochemical properties. The various mechanisms are described in more detail below. Depending on whether the storage mechanism has double-layer capacitance and / or pseudocapacitance properties, and depending on whether the supercapacitor has two identical or symmetric electrodes or two different or asymmetric electrodes, a supercapacitor having multiple frustules, one or both of which are coated with a nanostructured surface active material, can be configured as one of three different groups of supercapacitors.

[0407] A first group of supercapacitors has both electrodes configured as pseudocapacitors, each electrode comprising a frustule and a transition metal oxide (e.g., manganese oxide or zinc oxide) to create pseudocapacitance. For example, the frustule may have a nanostructured transition metal oxide thereon. A second group of supercapacitors has both electrodes configured as EDLCs, each electrode comprising a frustule and carbon (e.g., carbon nanotubes) to create double-layer capacitance. For example, the frustule may have a nanostructured carbon thereon. A third group of supercapacitors, which may be referred to as hybrid supercapacitors, has one electrode configured as an EDLC and the other electrode configured as a pseudocapacitor. When included as part of a hybrid capacitor, the electrode configured as a pseudocapacitor may function as the cathode, or positively charged electrode, and the electrode configured as an EDLC may function as the anode, or negatively charged electrode. Without being bound by theory, the operating principles of these three groups of supercapacitors are described herein.

[0408] FIG. 14A shows a cross-sectional view of a supercapacitor 1400 having both electrodes configured as a double-layer capacitor. FIG. 14B shows a cross-sectional view of the supercapacitor of FIG. 14A during operation when a voltage is applied across it. FIGS. 14A and 14B show the supercapacitor 1400 in a discharged and charged state, respectively. The supercapacitor 1400 includes a first electrode 1440 that can be positively charged during operation and a second electrode 1450 that can be negatively charged during operation. The supercapacitor 1400 optionally includes a first current collector 1410 and a second current collector 1420 electrically coupled to the electrode 1440 and the electrode 1450, respectively. The first electrode 1440 and the second electrode 1450 are sandwiched between a separator 1430 and ionically connected to each other via an electrolyte 1460 that fills the gap between the first electrode 1440 and the second electrode 1450. The electrolyte 1460 comprises a mixture of positive ions 1470 and negative ions 1480 dissolved in a solvent. The surface of each electrode 1440, 1450 contacts the electrolyte 1460, forming an active interface. At the active interface between the electrodes 1440, 1450 and the electrolyte 1460, a double layer capacitance effect occurs.

[0409] Referring to FIG. 14A , in a discharged state, positive ions 1470 and negative ions 1480 may be randomly dispersed. In operation, referring to FIG. 14B , when a voltage is applied across the first electrode 1440 and the second electrode 1450, for example, by negatively charging the second current collector 1420 relative to the first current collector 1410 and / or positively charging the first current collector 1410 relative to the second current collector 1420, both electrodes 1440, 1450 generate an electric double layer. Each electric double layer includes two layers of charge, as shown in FIG. 14B . Without being bound by theory, for example, a layer of electrostatic charge, e.g., a sheet of negative electronic charge, may form on the surface of the second electrode 1450, e.g., on the surface of the surface active material, and an opposing layer of electrostatic charge, e.g., a sheet of positive ionic charge, may form adjacent the surface of the electrode 1450 in the electrolyte 1460. These two charge sheets are separated by a layer 1490 (e.g., a monolayer) of solvent molecules of the electrolyte 1460 (sometimes referred to as the inner Helmholtz plane (IHP)). This layer 1490 of solvent molecules forms a first capacitance (C d1 ) on the side of the first electrode 1440. Similarly, a layer 1500 of solvent molecules forms between a layer of electrostatic charge (e.g., positive electronic charges at the surface (e.g., the surface of the surface active material) of the first electrode 1440) and an opposing layer of electrostatic charge (e.g., negative ionic charges that may form adjacent the surface of the first electrode 1440 in the electrolyte 1460). The layer 1500 of solvent molecules creates a second capacitance (C d2 ) serves as another dielectric layer.

[0410] As described herein, each of the layers 1490, 1500 of solvent molecules formed adjacent to the second electrode 1450 and the first electrode 1440, respectively, has a capacitance C d1 , C d2 The capacitor formed by the second electrode 1450 and the first electrode 1440 is electrically connected in series by the electrolyte 1460, resulting in a series supercapacitance C that can be expressed as: S Gives: 1 / CS =(1 / C d1 )+(1 / C d2 ) Equation 1

[0411] For a given solvent in the electrolyte 1460, the amount of charge stored per unit voltage in the EDLC is a function of the electrode size. Similar to classical electrostatic capacitance, the capacitance C due to the first double layer capacitor on the side of the second electrode 1450 d1 can be approximated as follows: C d1 =ε1d1Equation 2 where ε is the dielectric constant of the solvent in the electrolyte 1460, and d is the effective thickness of the layer 1490 of solvent molecules formed adjacent to the second electrode 1450. Similarly, the capacitance C due to the second double layer on the side of the first electrode 1440 d2 can be approximated as follows: C d2 =ε2d2 equation 3 where ε2 is the dielectric constant and d2 is the effective thickness of the layer 1500 of solvent molecules of the electrolyte 1460 formed near the first electrode 1440. The stored energy of each double layer is approximately linear with capacitance and corresponds to the concentration of adsorbed ions. The energy E stored in the supercapacitor can be expressed as: E=C S AV 2 / 2 expression 4 where C S is the capacitance of the supercapacitor, A is the effective surface area of ​​the electrode, and V is the voltage. The power of the supercapacitor can be expressed as: P max =V 2 / (4R) Equation 5 where R is the equivalent series resistance of the supercapacitor. According to the capacitance, energy, and power equations above, for a given electrolyte, high supercapacitor power and energy are achieved by increasing the surface area (A) of the electrodes 1450, 1440, increasing the supercapacitor voltage (V), and decreasing the equivalent resistance (R) due to the electrodes, electrolyte, and interface between the electrode material and the supercapacitor layer. The electric double layer capacitance values ​​are extremely high compared to conventional electrostatic capacitors with similar macroscopic electrode sizes, due in part to the extremely thin layers 1490, 1500 of solvent molecules (which can be as thin as a monolayer, e.g., a few angstroms (0.3–0.8 nm), or the Debye length). The active area of ​​the electrode is also very high, as noted above, due to the large surface area of ​​the frustules, which is further enhanced by the nanostructured active material formed on top of them.

[0412] Based on the mechanism of EDLCs described above, unlike battery energy storage, the process of generating electric double-layer capacitance does not involve charge transfer between electrodes using an electrolyte. While charges in conventional capacitors are transported via electrons, the capacitance of double-layer capacitors is related to the rate of ion transfer through the electrolyte and the resistive pore structure of the shell. Because no chemical changes occur within the electrodes or electrolyte, EDLCs can have a much longer cycle life than batteries.

[0413] FIG. 15 shows a cross-sectional view of a supercapacitor 1500 with electrodes configured as a pseudocapacitor. The supercapacitor 1500 may be configured similarly to the supercapacitor 1400 described above, except for the structure and composition of its electrodes. The supercapacitor 1500 includes a first electrode (not shown) that can be positively charged in operation and a second electrode 1550 that can be negatively charged in operation, although for illustrative purposes, only the second electrode 1550 is shown as a pseudocapacitor. The first electrode may be configured as another pseudocapacitor or as an EDLC described above. The surfaces of the first electrode and the second electrode 1550 are in contact with the electrolyte 1460. A pseudocapacitance effect occurs at the contact interfaces between the first electrode, the second electrode 1550, and the electrolyte 1460.

[0414] Without being bound by theory, in operation, applying a voltage across the first and second electrodes 1550 causes positive and negative ions in the electrolyte 1460 to migrate in opposite directions toward the first and second electrodes 1550, forming an electric double-layer capacitor, for example, in a manner similar to that described above with reference to FIGS. 14 and 14B. When ions in the electrolyte permeate the electric double layer and are adsorbed onto the electrode surface, as shown in FIG. 15, pseudocapacitance can be generated. This pseudocapacitance stores electrical energy through reversible Faradaic redox reactions at the electrode surface of the supercapacitor that form the electric double layer described above. Unlike the electric double-layer capacitance effect, pseudocapacitance involves electronic charge transfer between the electrolyte 1460 and the adsorbed ions. This Faradaic charge transfer results from an ultrafast sequence of reversible redox, intercalation, or electrosorption processes. The ability of an electrode to exhibit pseudocapacitance depends on the chemical affinity of the electrode material for ions adsorbed on the electrode surface, its structure, and the electrode structure. Transition metal oxides are suitable materials for use as electrodes in pseudocapacitors, as they exhibit redox behavior. The pseudocapacitance can be expressed as the amount of stored charge (q) divided by the applied potential (V), or in other words, as follows: C=dq / dV Equation 6

[0415] Similar to double-layer capacitance, pseudocapacitance or electrochemical capacitance occurs on the surface of the electrode, for example, on the surface of the surface active material formed on the frustule. As a result, the specific surface area is directly proportional to the number of active sites for redox reactions, i.e., the magnitude of the pseudocapacitance. This faradaic energy storage with fast redox reactivity charges and discharges much faster than batteries.

[0416] The faradaic pseudocapacitance occurs together with the static double layer capacitance, and depending on the nature and structure of the electrodes, its magnitude can exceed the value of the double layer capacitance by several orders of magnitude for the same surface area.

[0417] Various embodiments of supercapacitors are disclosed below. Although not necessarily described in detail, the frustules of various embodiments can have any structure and be prepared using any method described throughout this application, including, but not limited to, those shown in Figures 1-5X and related descriptions. Various nanostructures, such as zinc oxide, manganese oxide, and carbon nanostructures, of various embodiments can have any structure, such as that shown in Figure 5, and can be prepared using any method described throughout this application, including, but not limited to, those shown in Figures 1-5X and related descriptions.

[0418] [Supercapacitor electrode having a shell of active material formed thereon] As discussed above, the interface between the electrode's surface active material and the electrolyte provides sites for energy storage. Various surface active materials configured to create pseudocapacitance are described below. As described herein, the surface active material can form a coating on the frustule, e.g., on the surface of the frustule. The coating can be in the form of a nanostructured surface active material and can be formed as part of one or more electrodes of a supercapacitor, for example, according to the related methods described herein.

[0419] In some embodiments, the nanostructured surface active material formed on the frustule surface comprises one or more metal oxides, such as zinc oxide (ZnO), manganese dioxide (MnO), manganese(II,III) oxide (MnO), manganese(II) oxide (MnO), manganese(III) oxide (MnO), mercury oxide (HgO), cadmium oxide (CdO), silver(I,III) oxide (AgO), silver(I) oxide (AgO), nickel oxide (NiO), lead(II) oxide (PbO), lead(II,IV) oxide (Pb2O3), lead dioxide (PbO2), vanadium(V) oxide (V2O5), copper oxide (CuO), molybdenum trioxide (MoO3), iron(III) oxide (Fe2O3), iron(II) oxide (FeO), iron(II,III) oxide (Fe3O4), rubidium(IV) oxide (RuO2), titanium dioxide (TiO2), iridium(IV) oxide (IrO2), cobalt(II,III) oxide (Co3O4), tin dioxide (SnO2), niobium oxide (Nb2O5), and combinations thereof.

[0420] In some embodiments, the nanostructured surface active material formed on the frustule surface comprises one or more metal-containing compounds, such as manganese(III) oxyhydroxide (MnOOH), nickel oxyhydroxide (NiOOH), nickel silver oxide (AgNiO), lead(II) sulfide (PbS), silver lead oxide (AgPbO), bismuth(III) oxide (BiO), silver bismuth oxide (AgBiO), silver vanadium oxide (AgVO), copper(I) sulfide (CuS), iron disulfide (FeS), iron sulfide (FeS), lead(II) iodide (PbI), nickel sulfide (N i3S2), silver chloride (AgCl), silver chromium oxide or silver chromate (Ag2CrO4), copper(II) oxide phosphate (Cu4O(PO4)2), lithium cobalt oxide (LiCoO2), metal hydrides (e.g., LaCePrNdNiCoMnAl), lithium iron phosphate (LiFePO4, LEP), lithium permanganate (LiMn2O4), lithium manganese dioxide (LiMnO2), Li(NiMnCo)O2, Li(NiCoAl)O2, cobalt oxyhydroxide (CoOOH), titanium nitride (TiN), and combinations thereof.

[0421] In some embodiments, the nanostructured surface active material formed on the frustule surface comprises mixed transition metal spinels and binary metal oxides, such as MnFe2O4, NiCo2O4, CuCo2O4, ZnCo2O4, Zn2SNO4, NiMoO4, combinations thereof, and the like.

[0422] In some embodiments, the nanostructured surface active material formed on the frustule surface comprises a metal hydroxide, such as Ni(OH)2, Co(OH)2, H2Ti3O7, combinations thereof, or the like.

[0423] According to other embodiments, the nanostructured surface active material formed on the frustule surface may comprise a mixture of the above materials. For example, a combination of materials that can coat the frustule may include Mn x O y -Co x O y , MnO2‐NiO / Ni(OH)2, Mn x O y -TiO2, Mn x O y -ZnO, etc.

[0424] In addition to the surface active material that forms an interface with the electrolyte, which provides sites for energy storage, the supercapacitor electrode also includes a conductive material. In addition to providing electrical conductivity to the frustule, which may be electrically insulating, enabling the electric double layer capacitance and pseudocapacitance described above, the conductive material can also reduce internal resistance for high power applications, as described above. One or more of the above compounds can be coated onto the frustule along with one or more conductive materials. The conductive material can be carbon-based in some embodiments. For example, the conductive material can comprise one or more of various carbon compounds, such as graphene, graphite, carbon nanotubes (CNTs), fullerenes, carbon nanofibers, and / or carbon aerogels.

[0425] The conductive material can be metal-based in some embodiments. For example, the conductive material can comprise a metallic element or compound, such as Ag, Au, stainless steel, Mn, Cu, Ni, and / or Al. In some embodiments, the conductive material can comprise a conductive polymer, such as polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, and / or related polymers.

[0426] Although various embodiments are described in which the surface active material and conductive material may be formed on the surface of each frustule, not all embodiments necessarily include these features. In some embodiments throughout this application, the surface active material and conductive material may be formed on the frustule layer or between frustules within the frustule layer, in addition to or instead of being formed on the surface of each frustule.

[0427] Although various embodiments are described in which the active material is nanostructured, not all embodiments necessarily include this feature. In some embodiments throughout this application, the surface active material may form a continuous or adjacent network of thin films of surface active material.

[0428] [Supercapacitor electrode with manganese oxide as surface active material and a frustule formed thereon] The surface active material for a supercapacitor electrode (e.g., an electrode configured to produce pseudocapacitance) can include one or more of the manganese-containing compounds described above, such as manganese oxide. The manganese-containing compound can have, for example, the composition described herein and can be prepared using the associated methods. According to some embodiments, one or more electrodes can include manganese oxide (Mn) as the surface active material. x O y), e.g., a frustule having manganese oxide nanostructures formed thereon. In some embodiments, the frustule has a surface coated with manganese oxide nanostructures by the methods described herein. The manganese oxide, e.g., manganese oxide nanoparticle coating, can comprise approximately 50-95 wt%, 55-85 wt%, 60-80 wt%, 65-75 wt%, or a value within a range defined by these values, e.g., approximately 70 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode).

[0429] One or more electrodes comprising manganese oxide may additionally comprise a conductive material, as described above. The conductive material may include conductive carbon in an amount of approximately 0.1-15 wt %, 1-13 wt %, 3-11 wt %, 5-9 wt %, 6-8 wt %, or for example, approximately 7 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The conductive carbon forms part of the electrode to provide electrical conductivity, as described above. The conductive carbon can improve the printability of the ink. The conductive carbon can improve the flexibility of the resulting supercapacitor. One example of a conductive carbon that may be included as part of one or more electrodes is Timcal Super65®, manufactured by Timcal Graphite & Carbon, Switzerland.

[0430] One or more electrodes comprising manganese oxide may additionally comprise carbon nanotubes in an amount of approximately 0.1 to 15 wt %, 1 to 13 wt %, 3 to 11 wt %, 5 to 9 wt %, 6 to 8 wt %, for example, approximately 7 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The carbon nanotubes function as part of the electrode to provide electrical conductivity. The carbon nanotubes can improve the printability of the ink. The carbon nanotubes can improve the flexibility of the resulting supercapacitor. One example of carbon nanotubes that may be included as part of one or more electrodes is multi-walled carbon nanotubes manufactured by Cheap Tubes, Inc., USA.

[0431] One or more electrodes comprising manganese oxide can additionally comprise a polymer binder in an amount of about 0.1-15 wt%, 0.5-12 wt%, 1-9 wt%, 2-6 wt%, 3-5 wt%, e.g., about 4 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The polymer binder promotes adhesion to the substrate or other layers and promotes layer integrity (e.g., holds particles together). One example of a polymer binder that can be included as part of one or more electrodes is polyvinylidene fluoride (PVDF) available from Belgium under the name Solef 5130.

[0432] One or more electrodes comprising manganese oxide can additionally comprise an electrolyte comprising an ionic liquid. The ionic liquid can be present in an amount of approximately 5-30 wt%, 8-27 wt%, 11-24 wt%, 14-21 wt%, 17-20 wt%, e.g., approximately 18 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The ionic liquid can function as the electrolyte or as part of the electrolyte. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany.

[0433] One or more electrodes comprising manganese oxide can additionally comprise a salt, which can be dissolved in a solvent or ionic liquid in an amount of approximately 0.1-5 wt %, 1-5 wt %, 1.5-4.5 wt %, 2.0-4.0 wt %, 2.5-3.5 wt %, or about 3 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The salt functions as an additive to improve ionic conductivity. The salt can promote high capacitance by contributing to the interfacial structure. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany. The salt and ionic liquid that can be included as part of one or more electrodes can be any of the salts and ionic liquids described herein.

[0434] In some embodiments, one or more electrodes comprising manganese oxide in addition to an ionic liquid, or a combination of an ionic liquid and a salt, may comprise a solvent for the electrolyte that may remain after drying.

[0435] In some embodiments, one or more electrodes comprise a gel that acts as a medium for ion transport. The gel can include an electrolyte and can include one or more of a solvent, a salt, an ionic liquid, or a suitable gel-forming or gelling polymer, as described herein.

[0436] In some embodiments, the gel can at least partially fill the pore network of the frustule. If the gel nearly completely fills the pore network, the resulting electrode can be substantially free of pores containing voids. On the other hand, if the gel only partially fills the pore network, the resulting separator can contain some pores containing voids. The voids, if present, can be filled with electrolyte.

[0437] In some embodiments, once the gel fills the pore network of the frustule, the electrolyte-containing gel may be relatively localized rather than freely moving through the pore network of the frustule.

[0438] [Supercapacitor electrode with a frustule and zinc oxide as a surface active material] Active materials for supercapacitor electrodes (e.g., electrodes configured to produce pseudocapacitance) include one or more zinc-containing compounds described above, e.g., zinc oxide. The zinc-containing compounds may have compositions, for example, as described herein and may be prepared using related methods. According to some embodiments, one or more electrodes may contain zinc oxide (Zn) as a surface active material. x O y, e.g., ZnO), e.g., zinc oxide nanostructures, are formed thereon. In some embodiments, the frustule has a surface coated with zinc oxide nanostructures by the methods described herein. The zinc oxide, e.g., zinc oxide nanoparticle coating can comprise approximately 25-90 wt.%, 30-80 wt.%, 35-70 wt.%, 40-60 wt.%, 45-50 wt.%, or a value within a range defined by these values, e.g., approximately 46 wt.%, based on the total weight of the electrode (e.g., the as-printed and dried electrode).

[0439] One or more electrodes comprising zinc oxide may additionally comprise a conductive material, as described above. The conductive material may include conductive carbon in an amount of approximately 0.1 to 15 wt %, 2 to 14 wt %, 4 to 13 wt %, 6 to 12 wt %, 8 to 11 wt %, or 10 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The conductive carbon may form part of the electrode to provide electrical conductivity. The conductive carbon may improve the printability of the ink. The conductive carbon may improve the flexibility of the resulting supercapacitor. The conductive carbon may function as part of the electrode to provide electrical conductivity, as described above. The conductive carbon may improve the printability of the ink. The conductive carbon may improve the flexibility of the resulting supercapacitor. An example of a conductive carbon that may be included as part of one or more electrodes is Timcal Super65®, manufactured by Timcal Graphite & Carbon, Switzerland.

[0440] One or more electrodes comprising zinc oxide may additionally comprise carbon nanotubes in an amount of approximately 0.1 to 15 wt %, 0.1 to 11 wt %, 0.1 to 7 wt %, 0.1 to 5 wt %, 1 to 3 wt %, for example, approximately 2 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The carbon nanotubes function as part of the electrode to provide electrical conductivity. The carbon nanotubes can improve the printability of the ink. The carbon nanotubes can improve the flexibility of the resulting supercapacitor. One example of carbon nanotubes that may be included as part of one or more electrodes is multi-walled carbon nanotubes manufactured by Cheap Tubes, Inc., USA.

[0441] One or more electrodes comprising zinc oxide can additionally comprise a polymer binder in an amount of about 0.1-15 wt%, 0.5-13 wt%, 1-11 wt%, 2-9 wt%, 3-7 wt%, e.g., about 5 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The polymer binder can promote adhesion to a substrate or other layers and promote layer integrity (e.g., holding particles together). One example of a polymer binder that can be included as part of one or more electrodes is polyvinylidene fluoride (PVDF) available from Belgium under the name Solef 5130.

[0442] One or more electrodes comprising zinc oxide can additionally comprise an electrolyte comprising an ionic liquid. The ionic liquid can be present in an amount of approximately 10-50 wt%, 15-50 wt%, 20-45 wt%, 25-40 wt%, 30-35 wt%, e.g., 34 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The ionic liquid can function as the electrolyte or as part of the electrolyte. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany.

[0443] One or more electrodes comprising zinc oxide can additionally comprise a salt, which can be dissolved in an ionic liquid in an amount of approximately 0.1-5 wt %, 1-5 wt %, 1.5-4.5 wt %, 2.0-4.0 wt %, 2.5-3.5 wt %, or approximately 3 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The salt can function as an additive to improve ionic conductivity. The salt can promote high capacitance by contributing to the interfacial structure. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany.

[0444] In some embodiments, one or more electrodes comprising zinc oxide in addition to an ionic liquid, or a combination of an ionic liquid and a salt, may comprise a solvent for the electrolyte that may remain after drying.

[0445] [Supercapacitor electrode having a shell of carbon nanostructures formed thereon as a surface active material] Active materials for supercapacitor electrodes (e.g., electrodes configured to form EDLCs) include one or more carbon nanostructures, such as CNTs, as described above. The carbon nanostructures can have compositions and be prepared using the associated methods described herein. According to some embodiments, one or more electrodes comprise carbon structures, e.g., frustules, as surface active materials, on which carbon nanostructures are formed. In some embodiments, the frustules have surfaces coated with carbon nanostructures, e.g., CNTs, using methods described herein. One or more electrodes comprise CNTs in an amount of approximately 1-50 wt%, 1-40 wt%, 1-30 wt%, 1-20 wt%, 5-15 wt%, e.g., approximately 11 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). Carbon nanotubes can function as part of the surface active material. Carbon nanotubes can provide printability for inks. Carbon nanotubes can improve the flexibility of the resulting supercapacitor. One example of carbon nanotubes that can be included as part of one or more electrodes is multi-walled carbon nanotubes manufactured by Cheap Tubes, Inc., USA.

[0446] One or more electrodes comprising carbon can additionally comprise a conductive material, as described above. The conductive material can include conductive carbon in an amount of approximately 1-50 wt %, 1-40 wt %, 1-30 wt %, 1-20 wt %, 5-15 wt %, e.g., 11 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The conductive carbon can form part of the surface active material. The conductive carbon can provide printability for the ink. The conductive carbon can improve the flexibility of the resulting supercapacitor. One example of a conductive carbon that can be included as part of one or more electrodes is Timcal Super65®, manufactured by Timcal Graphite & Carbon, Switzerland.

[0447] One or more electrodes comprising CNTs can additionally comprise a polymer binder in an amount of about 0.1-15 wt%, 1-13 wt%, 3-11 wt%, 5-9 wt%, e.g., about 7 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The polymer binder can promote adhesion to a substrate or other layers and promote layer integrity (e.g., holding particles together). One example of a polymer binder that can be included as part of one or more electrodes is polyvinylidene fluoride (PVDF) from Belgium, Solef 5130.

[0448] One or more electrodes comprising CNTs can additionally comprise an ionic liquid in an amount of approximately 10-90 wt%, 30-85 wt%, 50-80 wt%, 70-75 wt%, e.g., 71 wt%, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The ionic liquid can function as an electrolyte or as part of the electrolyte. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany.

[0449] One or more electrodes comprising CNTs can additionally comprise a salt, which can be dissolved in an ionic liquid in an amount of approximately 0.1-5 wt %, 1-5 wt %, 1.5-4.5 wt %, 2.0-4.0 wt %, 2.5-3.5 wt %, or approximately 3 wt %, based on the total weight of the electrode (e.g., the as-printed and dried electrode). The salt functions as an additive to improve ionic conductivity. The salt can promote high capacitance by contributing to the interfacial structure. One example of an ionic liquid that can be included as part of one or more electrodes is 1-ethyl-3-methylimidazolium tetrafluoroborate (C2mimBF4) manufactured by IoLitec, Germany. The salt and ionic liquid that can be included as part of one or more electrodes can be any of the salts and ionic liquids described herein.

[0450] In some embodiments, in addition to the ionic liquid, or the combination of an ionic liquid and a salt, one or more electrodes comprising CNTs can comprise a solvent for the electrolyte that may remain after drying.

[0451] [Supercapacitor separator] According to various embodiments, the supercapacitor further comprises a separator. The separator may be interposed between the electrodes and may reduce or prevent short circuits resulting from direct contact between the electrodes. The separator may include a frustule. The separator may be configured to function as a permeable membrane for ion transport. A frustule-containing separator may provide low electrical resistance, chemical stability, and / or a relatively thin thickness. The frustule functions as a separator filler and improves printability, for example, reducing or preventing holes during printing that could short the electrodes.

[0452] The frustule-containing separator can have any of the structures and compositions described herein and can be prepared using any of the methods described herein.

[0453] 14A, 14B, and 15, each supercapacitor 1400, 1500 includes a separator 1430 having a frustule, e.g., a refined frustule, which occupies approximately 10-70 wt%, 13-55 wt%, 16-45 wt%, 19-35 wt%, 20-25 wt%, or a range defined by these values, e.g., approximately 22 wt%, based on the total weight of the separator (e.g., the separator as printed and dried). The process for forming the refined frustule and forming the separator therefrom, and various properties thereof, are described above.

[0454] The separator 1430 including the shell can additionally include a thermally conductive additive in an amount of approximately 0.1 to 5 wt %, 0.5 to 4 wt %, 1 to 3 wt %, 1.5 to 2.5 wt %, or approximately 2 wt %, based on the total weight of the separator (e.g., the as-printed and dried separator). The thermally conductive additive can function as a separator filler. The thermally conductive additive can function as a heat absorbing and / or thermally conductive agent, for example, as a near-infrared (NIR) absorber. In this application, NIR radiation can have a wavelength of 0.7 μm to 2.5 mm. The thermally conductive additive can efficiently absorb and / or conduct heat during manufacturing, for example, during a drying process using near-infrared (NIR). The thermally conductive additive can improve power by reducing the internal resistance of the supercapacitor. The thermally conductive additive can be, for example, a good heat absorber, a good thermal conductor, or a relatively good electrical insulator. One example of such a thermally conductive additive that can be included as part of the separator is graphene oxide (GO) manufactured by Cheap Tubes, Inc., USA. The inventors have found that adding graphene oxide to inks for printing separators can result in the resulting ink exhibiting improved printability, excellent thermal conductivity during drying (reducing drying time), and relatively low internal resistance of the supercapacitor, although not all of these benefits are essential. Thermally conductive additives such as GO can also be excellent electrical insulators, thereby advantageously maintaining electrical insulating properties of the separator. In some embodiments, GO comprises multiple GO sheets in contact with each other, forming a network of adjacent GO sheets. The inventors have found that when GO is included as part of a printed layer, such as a printed separator layer, it can reduce drying time by an order of magnitude, e.g., from tens of minutes to tens of seconds.

[0455] A separator with a furring shell can additionally comprise a polymer binder in an amount of approximately 5-20 wt%, 5-15 wt%, 5-10 wt%, 6-8 wt%, e.g., 7 wt%, based on the total weight of the separator (e.g., the as-printed and dried separator). The polymer binder can promote adhesion to a substrate or other layer and promote layer integrity (e.g., holding particles together). One example of a polymer binder that can be included as part of the separator is polyvinylidene fluoride (PVDF) available from Belgium under the trade name Solef 51...

Claims

1. A supercapacitor configured to charge and discharge via an electrochemical process, comprising: A pair of electrodes in contact with an electrolyte; One of the pair of electrodes comprises a diatom frustule coated with a plurality of carbon nanotubes; A supercapacitor, wherein the other electrode of the pair of electrodes comprises diatom frustules coated with an active material.

2. The supercapacitor of claim 1, wherein the active material comprises a transition metal oxide.

3. The supercapacitor of claim 2, wherein the transition metal oxide comprises zinc oxide.

4. The supercapacitor of claim 2, wherein the transition metal oxide comprises manganese oxide.

5. The supercapacitor of claim 4, wherein the manganese oxide comprises one or more of manganese dioxide (MnO2), manganese (II,III) oxide (Mn3O4), manganese (II) oxide (MnO), and manganese (III) oxide (Mn2O3).

6. The supercapacitor of claim 1, wherein ionic transport does not occur between the pair of electrodes as part of the electrochemical reaction during charging and discharging.

7. The supercapacitor of claim 1, wherein the electrolyte comprises an ionic liquid.

8. The supercapacitor of claim 7, wherein the ionic liquid comprises one or more cations selected from the group consisting of butyltrimethylammonium, 1-ethyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-methyl-3-propylimidazolium, 1-hexyl-3-methylimidazolium, choline, ethylammonium, tributylmethylphosphonium, tributyl(tetradecyl)phosphonium, trihexyl(tetradecyl)phosphonium, 1-ethyl-2,3-methylimidazolium, 1-butyl-1-methylpiperidinium, 1-ethyl-3-methylimidazolium, 1-methyl-1-propylpiperidinium, 1-butyl-2-methylpyridinium, 1-butyl-4-methylpyridinium, 1-butyl-methylpyrrolidinium, diethylmethylsulfonium, and combinations thereof.

9. The supercapacitor of claim 8, wherein the ionic liquid comprises one or more anions selected from the group consisting of tris(pentafluoroethyl)trifluorophosphate, trifluoromethanesulfonate, hexafluorophosphate, tetrafluoroborate, ethyl sulfate, dimethyl phosphate, methanesulfonate, triflate, tricyanomethanide, dibutyl phosphate, bis(trifluoromethylsulfonyl)imide, bis-2,4,4-(trimethylpentyl)phosphinate, iodide, chloride, bromide, nitrate, and combinations thereof.

10. A supercapacitor configured to charge and discharge via an electrochemical process, comprising: A pair of electrodes in contact with an electrolyte; Each of the pair of electrodes comprises a plurality of diatom frustules; A supercapacitor, wherein one electrode of the pair of electrodes comprises carbon nanotubes coating diatom frustules, and the other electrode of the pair of electrodes does not comprise carbon nanotubes coating diatom frustules.

11. A supercapacitor as described in claim 10, wherein at least a portion of the multiple diatom frustules of one of the electrodes are individually coated with multiple carbon nanotubes.

12. A supercapacitor as described in claim 10, wherein one or more transition metal oxides are formed on the diatom frustules of the other electrode or on the diatom frustules of both of the pair of electrodes.

13. The supercapacitor of claim 12, wherein the one or more transition metal oxides comprise zinc oxide.

14. The supercapacitor of claim 12, wherein the one or more transition metal oxides comprise manganese oxide.

15. The supercapacitor of claim 14, wherein the manganese oxide comprises one or more of manganese dioxide (MnO2), manganese (II,III) oxide (Mn3O4), manganese (II) oxide (MnO), and manganese (III) oxide (Mn2O3).

16. The supercapacitor of claim 10, wherein ionic transport does not occur between the pair of electrodes as part of the electrochemical reaction during charging and discharging.

17. The supercapacitor of claim 10, wherein the electrolyte comprises an ionic liquid.

18. A supercapacitor configured to charge and discharge via an electrochemical process, comprising: A pair of electrodes in contact with an electrolyte; One of the pair of electrodes comprises a plurality of diatom frustules and a plurality of carbon nanotubes; A supercapacitor, wherein the one electrode is substantially configured as an electric double layer capacitor, and the other electrode of the pair of electrodes is substantially configured as a pseudocapacitor.

19. A supercapacitor as described in claim 18, wherein the diatom frustules of one of the electrodes are individually coated with carbon nanotubes.

20. A supercapacitor as described in claim 18, wherein the diatom frustules of the other electrode are individually coated with a transition metal oxide.

Citation Information

Patent Citations

  • Printable Composition of a Liquid or Gel Suspension of Diodes

    US20120161195A1

  • Printed energy storage device

    US20140302373A1

  • Nickel INKS and oxidation resistant and conductive coatings

    WO2014106088A1

  • Diatomaceous energy storage devices

    WO2016209655A1

  • Capacitors, electrodes, reduced graphene oxide and methods and apparatuses of manufacture

    WO2018039710A1